FpNuc1α regulates phosphate signaling and pathogenicity in Fusarium proliferatum infection of jujube fruit by targeting FpGit1 via a novel BSN motif - Yizhou Gao; Yitong Wang; Zenghui Yang; Jian Lou; Lingling Liu; Jinghe Sun; Orelvis Portal Villafaña; Zhihong Wu; Xiaofang Zheng; Jun Li; Zhaojun Ban; Li Li (Food Microbiology, 2027)

Inactivation kinetics of Enterococcus faecium, a pathogen surrogate, by aqueous ozone in purified water at different salt contents, pH, and treatment temperatures - David R. Kasler; Yuqian Lou; Jason Parcon; Zhen Li; Ahmed E. Yousef (International Journal of Food Microbiology, 2026)

Real-world impacts of SCR deterioration on NOx emissions from China VI heavy-duty diesel vehicles: Insights from PEMS-based urea mass fraction deterioration tests - Yunpeng Li; Xin Lou; Tao Li; Lanlin Qin; Yingwen Yang; Jinzhu Cao; Dan Zhou; Chaojie Fan; Yong Peng (Fuel, 2026)

Knockdown of Transthyretin ameliorates ferroptosis in myocardial ischemia-reperfusion injury - Gege Liao; Yuxin Li; Jian Xu; Zekun Lou; Yang Liu; Yanfeng Ma; Dongye Li; Feng Wang; Tongda Xu (Molecular Biology Reports, 2026)

Prediction of chemoresistance in ovarian cancer based on deep learning with pathological images - Leyan Niu; Xiang Li; Zhiquan Mao; Fen Fu; Mingjie Wang; Hengbin Zhang; Le Chen; Qing Zhang; Xiaoli Tang; Weiming Lou (Functional & Integrative Genomics, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

BPAF-induced inflammatory response via estrogen signaling: insights from in vivo and in vitro evidence - Jiaying Li; Mengjie Yu; Xiaoyu Lu; Junmei Xia; Fen Lu; Shufang Lou; Bingli Lei (Food and Chemical Toxicology, 2026)

Janus membranes in membrane distillation: Unveiling the anti-wetting behavior and mechanisms in the presence of nanoplastic-surfactant complexes - Yubin Zhang; Chen Li; Chenchang Liu; Mengmeng Lou; Shengyang Zheng; Lijun Meng; Manhong Huang (Desalination, 2026)

Engineered small extracellular vesicles–integrated multifunctional hydrogel reprograms the wound immune microenvironment for accelerated skin repair - Zhong Liu; Xinyu Zhu; Jun Cheng; Kewei Li; Yang Lou; Xiaopeng Sun; Yuhong Fan; Min Wang; Hui Qian; Yanbin Liu; Hua Ding; Song Guo; et al. (Chemical Engineering Journal, 2026)

Comprehensive low-damage mechanical weeding technology considering the spatial distribution of crop roots: A case study of maize farmland - Deng Sun; Longzhe Quan; Zhaoxia Lou; Guoxiang Zhang; Chen Ru; Xiaojie Li; Zhiming Guo; Jinbin He; Chuan Wang; Yongheng Wang (Computers and Electronics in Agriculture, 2026)

Corrigendum to “A rapid method to generate an all-female population in common carp (Cyprinus carpio) using the neomale carp of F0 population with targeted aromatase mutations” Aquaculture, Volume 612, Part 1, 15 January 2026, 743185 - Yuting Xie; Hongfei Bao; Guanghui Chen; Xuehui Li; Yonglin Ruan; Qiyong Lou; Xia Jin; Jiangyan He; Tianshu Zhang; Jian Wang; Xueqiao Qian; Gang Zhai; et al. (Aquaculture, 2026)

Damping-enhanced tire-pavement noise mitigation of thermoplastic polyurethane/crumb rubber composite-modified asphalt pavements - Zehua Zhu; Keke Lou; Peng Xiao; Jun Zhou; Chenying Li (Transportation Research Part D: Transport and Environment, 2026)

Compressive bearing capacity field test of a vertical-inclined combined core high-pressure jet grouting pile group foundation - Meilin Li; Gang Zheng; Qiang Lou; Yu Zhao; Haizuo Zhou; Weiguo Jiao; Hong Wang; Fei Gan (Transportation Geotechnics, 2026)

Three-dimensional integrated bidirectional coupled model and dynamic response of the deepwater drilling riser system - Min Lou; Dexing Yang; Yu Wang; Yaokang Luo; Lianjie Gao; Gezhanpeng Li; Yangyang Wang (Ocean Engineering, 2026)

Piezoelectric-enhanced dynamic membrane with ultrasound irradiation: active anti-fouling mechanism, synergistic degradation and process optimization - Jianping Yu; Yanqing Zhang; Yuxiang Liang; Hui Jiang; Chenxuan Lou; Wei Sun; Yao Feng; Wei Chen; Jionghui Li (Journal of Water Process Engineering, 2026)

Mechanisms of arsenic retention on titanosilicate sitinakite: A spectro-computational study - Hanwen Luan; Meifen Qin; Yongqiang Li; Kangqi Chang; Hu Liu; Ningning Shao; Yuan Luo; Zhijun Dong; Xiang-Yang Lou (Journal of Water Process Engineering, 2026)

A synergetic framework for land-atmosphere coupling-based remote sensing inversion of evapotranspiration, surface resistance, and aerodynamic resistance - Xiaowei Wang; Yazhen Jiang; Huanyu Zhang; Yitao Li; Menglin Si; Yunsheng Lou; Zhao-Liang Li (Journal of Hydrology, 2026)

Precipitation water conversion rate variations and driving mechanisms in the Yangtze-Huang-Huai-Hai river basin over the past 60 years - Haodong Deng; Yu Wang; Qingming Wang; Chaoqun Li; Fusheng Li; Dengming Yan; Xiaoxue Chen; Dongqing Zhang; Kai Hou; Benxing Lou; Lichuan Wang (Journal of Hydrology, 2026)

Integrative molecular sensory science and untargeted metabolomic analysis reveal the flavor formation of fermented wheat bran - Yue Li; Yuxia Yang; Renyong Zhao; Shuangqi Tian; Xinwei Wang; Zhanpeng Liu; Haiwei Lou (Food Research International, 2026)

Impact of nonthermal plasma on the nutritional and phenolic bioaccessibility characteristics of wheat bran - Reham Ahmed Khashaba; Yue Li; Bowen Cai; Saeed Hamid Saeed Omer; Xunda Wang; Yunfei Yang; Haiwei Lou; Renyong Zhao (Food Chemistry, 2026)

The underappreciated diversity of functional pigments in red yeast rice revealed by an integrated multi-engine mining strategy (IMMS) - Yujuan Ban; Wen Miao; Xinyang Jin; Siyuan Chen; Xiaoer Lou; Jian-Lin Wu; Na Li (Food Chemistry, 2026)

Ultra small RuNi clusters synergistically promotes water dissociation and hydrogen adsorption for efficient hydrogen evolution in AEM water electrolyzers - Hongwei Zhao; Hongyi Li; Tianjiao Lou; Guangshun Ran; Hui Song; Xing Cheng (Chemical Engineering Journal, 2026)

A bioinspired flavin-based catalytic construct enabling intracellular NAD+/NADH redox regulation for mitigating skin aging - Jiani Xiang; Qian Ling; Li Yan; Ying Xia; Peizhen Lou; Zhen-Gang Wang; Ting Li; Huiling Wu (Chemical Engineering Journal, 2026)

Spatially confined skeleton-skin composite aerogels with dual-defense salt resistance for high-salinity wastewater concentration - Yong Bai; Jiaonan Cai; Qi Pan; Chuanxin Hou; Xiaowei Zhu; Mengmeng Lou; Dengxin Li; Fang Li (Chemical Engineering Journal, 2026)

Scaling up bioethanol autothermal reforming to a 200 Nm3/h pure hydrogen plant with in-situ regeneration - Xue Han; Yuyao Lou; Tianxiang Li; Xiaochen Liu; Haixin Guo; Jiameng Tang; Qinghe Yu; Jing Mi; Lei Hao; Yafei Wang (Chemical Engineering Journal, 2026)

Novel environmental contaminant 6PPD-quinone promotes malignant phenotypes in colorectal cancer cells and identifies candidate response-associated genes - Shuangyan Su; Yuxing Liao; Bihua Wu; Yuwei Li; Fenglin Lou; Zhenghao Mei; Le Guo (Chemico-Biological Interactions, 2026)

Developing a hand thermophysiological model to evaluate contact thermal sensation - Yicong Li; Jinyuan Lou; Yi Gao; Xiang Zhou; Maohui Luo (Building and Environment, 2026)

Da chuanxiong formula improves vascular remodeling via promoting angiogenesis and vasodilation mediated by PI3K/Akt/eNOS signaling - Jiale Gao; Tianyu Lou; Beibei Huang; Xiuying Guo; Hao Wu; Jie Liu; Yueting Li; Menghan Feng; Lirong Liu; Hongbin Xiao (Metabolic Brain Disease, 2026)

Near-complete phosphorus valorization from sewage sludge: Cost-effective co-production of vivianite and bioavailable detoxified hydrochar via a recyclable citric acid-mediated hydrothermal process - Xiaohan Cui; Yumeng Jin; Jian Zhu; Zhiyi Sun; Changkai Yin; Changfu Yang; Meifang Li; Long Kong; Chuansheng Chen; Zhihang Yuan; Ziyang Lou (Water Research, 2026)

Freeze-thaw damage evolution and crack propagation failure mechanism of red sandstone under non-uniform water distribution conditions - Li Wenbo; Sun Jielong; Chen Rui; Wang Yu; Wen Ziyi; Lou Bing (Transportation Geotechnics, 2026)

Metarhizium anisopliae infection-associated metabolites act upon LmOBP2 to suppress locust feeding - Chen Jia; Amr Mohamed; Rasha Al-Akeel; Weiyujie Tian; Xiang Li; Yulu Lou; Ioannis Eleftherianos; Nemat O. Keyhani; Wei Zhang (Pesticide Biochemistry and Physiology, 2026)

Post-peak dynamics and epidemic overshoot in SIR-type frameworks - Zhimin Li; Yijun Lou; Zhen Jin (Mathematical Biosciences, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Erratum to “From foodborne to environmental Yersinia enterocolitica: Comparative insights into antimicrobial resistance and virulence for food safety” [Food Res. Int. 238 (2026) 119442] - Xiuqin Lou; Juran Mao; Yue Wu; Yahong Xia; Wei Zhang; Jiajia Gao; Yiyi Wang; Jiaqi Yan; Xiao Xiao; Jun Li; Zhiguo Fang (Food Research International, 2026)

Enhancing flavor quality in low-salt dried large yellow croaker (Pseudosciaena crocea) through secondary fermentation: insights into microbial drivers - Zhihan Zheng; Jiawei Yang; Mohammad Rashedi Ismail-Fitry; Jiayu Wang; Shiqian Fu; Huicheng Yang; Liqing Wu; Yongjiang Lou; Yongyong Li (Food Chemistry, 2026)

Extracellular vesicles from fermented foods: sources, characteristics, functionalities, and future applications - Xiaoyi Liu; Joe-Hui Ong; Yihang Lou; Peihuan Luo; Xusheng Li; Yongjun Wei; Jose L. Quiles; Paul de Vos; Weibin Bai; Lingmin Tian (Food Chemistry, 2026)

Hazard prediction of backfill and dumping zones of open-pit mining areas using InSAR and multi-factor ensemble modeling - Jianqi Lou; Chaoying Zhao; Guangrong Li (Engineering Geology, 2026)

Achieving 96.6% energy-storage efficiency in Nd-doped tungsten-bronze ceramics through A-site vacancy engineering - Zhihong Wang; Yangfei Gao; Bian Yang; Mei Bai; Xiangran Pei; Hai Ci; Ruirui Kang; Junbo Xu; Yingying Zhao; Mengyao Guo; Fei Li; Xiaojie Lou (Chemical Engineering Journal, 2026)

RETRACTED ARTICLE: Molecular mechanisms of flower color variation in Impatiens uliginosa: insights from transcriptome sequencing and functional analysis of the IuMYB1 gene in anthocyanin biosynthesis and pigmentation - Baiyang He; Yuteng Xue; Shanman Li; Xue Hu; Xiaoli Lou; Jiwei Wang; Huang Deng; Shunming Zhang; Chao Luo; Yuhong Rong (Physiology and Molecular Biology of Plants, 2026)

Optimized fast desensitized Kalman filter - Tai-shan Lou; Liang Ma; Li-ying Jiang; Yu-zhao Jiao; Liang-Yu Zhao; Ren-long Qi (Advances in Space Research, 2026)

Altered amplitude of low-frequency fluctuations in herpes simplex encephalitis: a resting-state fMRI study and associations with anxiety - Hongxia Bai; Qi Zhou; Hui Li; Cailing Zhao; Ying Bai; Yangli Yu; Jueyue Yan; Lingli Lou (Brain Imaging and Behavior, 2026)

SS-MambaUnet for fault segmentation in multi-source remote sensing images - Xinshuo Wang; Li Lou (International Journal of Remote Sensing, 2026)

Socioeconomic affluence and land-use patterns shape urban plant diversity in Jinan, China - Wei Wang; Qi Lou; Zongshan Zhao; Hai-Li Zhang (Urban Forestry & Urban Greening, 2026)

Physics-informed model predictive control for active heave compensation of electrical winches - Ruhua Zhang; Wenhua Li; Shanying Lin; Gen Li; Haoran Ye; Xingjian Lou (Ocean Engineering, 2026)

Multi-omics analysis of the gill–gut axis in Scylla paramamosain under acute low-salinity stress: Implications for ion and osmotic regulation - Yiming Li; Yucong Ye; Lang Lou; Zongli Yao; Yanwu Ma; Yonghui Feng; Wei Liu; Hui Wu; Zhen Sun; Zihe Cheng; Yunlong Zhao; Qifang Lai (Marine Environmental Research, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Refining Wildland–urban interface delineation: A building-level exposure assessment framework - Zimeng Wang; Wenrui Li; Lingyu Wang; Yuanhong Liao; Shuhan Lou; Zhou Chen; Mingrun Zang; Yuqi Bai (Journal of Environmental Management, 2026)

Mechanistic insights into KOH-regulated biochar derived from waste Myriophyllum aquaticum biomass for 1O2-mediated degradation of 2,4,6-trichlorophenol - Guangya Zhou; Dong Zhang; Zhengzheng Lou; Miaomiao Zhao; Dihua Wu; Suling Zhang; Ying Pan; Ting Lü; Hongting Zhao; Jun Lin; Li Lu; Ming Zhang (Journal of Environmental Management, 2026)

Spatial-temporal traits and multimedia transport of tetrabromobisphenol A and its 20 analogs in Arctic aquatic ecosystems: from seawater to deep sediment archives - Yitong Liu; Minggang Zheng; Ling Wang; Xinyu Li; Aifeng Liu; Lei Shi; Yinghua Lou; Jiapeng Yuan (Journal of Environmental Sciences, 2026)

From foodborne to environmental Yersinia enterocolitica: Comparative insights into antimicrobial resistance and virulence for food safety - Xiuqin Lou; Juran Mao; Yue Wu; Yahong Xia; Wei Zhang; Jiajia Gao; Yiyi Wang; Jiaqi Yan; Xiao Xiao; Jun Li; Zhiguo Fang (Food Research International, 2026)

Molecular mechanisms of aroma quality improvement of Enshi Yulu green tea through yellow light treatment - Xianglin Kong; Yage Wang; Mengke Yuan; Ruixin Lou; Liangji Wu; Luqing Li; Tao Hou; Kaikai Li (Food Chemistry, 2026)

Self-assembled carrier-free Cur@EGCG-Cu rescue inflammatory senescence and restore autophagy in tendinopathy - Yu Zhang; Qiqi Lou; Ran Yang; Xiang Li; Xiangkai Kong; Ruolin Cui; Ni Ni; Lilun Jin; Weiran Teng; Ping Gu (Chemical Engineering Journal, 2026)

Electric field polarity governs fouling control in anaerobic dynamic membranes via structure-function coupling - Yuxiang Liang; Yanqing Zhang; Mengfan Yu; Dongqing Zhan; Pingli Li; Chenxuan Lou; Yangcheng Ding; Huajun Feng (Chemical Engineering Journal, 2026)

Context-dependent responses of soil organic carbon to liming: a meta-analysis - Yang Li; Shuang Fu; Marta Camps-Arbestain; Zhonghui He; Feicen Li; Tao Wang; Qinhua Shen; Youlin Lou; Xuesong Gao; Dagang Yuan (CATENA, 2026)

Pure monoterpenes as precision tools against soft rot: Fast susceptibility screening of Pectobacterium carotovorum with relevance to crop protection - Miroslava Kačániová; Zhaojun Ban; Li Li; Jian Lou; Joel Horacio Elizondo-Luevano; Anis Ben Hsouna; Rania Ben Saad; Alessandro Bianchi; Stefania Garzoli (Biocatalysis and Agricultural Biotechnology, 2026)

Hybrid advantage in largemouth bass: Mechanisms of enhanced thermal tolerance through balanced glycolipid metabolism and efficient cellular protection - Jinxing Du; Wenhui Lou; Hongmei Song; Tao Zhu; Jing Tian; Caixia Lei; Shengjie Li (Aquaculture, 2026)

Edge Loading and Wear Risk Analysis of a Marine Water-Lubricated Stern Bearing Considering Shaft-Deflection-Induced Journal Tilting - Xianyi Li; Jingjun Lou; Zhimin Chen; Maoting Tan; Ming Yang; Binbin Qiu; Haibo Wan (Journal of Marine Science and Engineering, 2026)
Classical hydrodynamic lubrication studies of journal bearings routinely invoke two simplifying assumptions: the axially rigid–straight journal assumption and the structure–lubrication decoupling assumption. For marine water-lubricated stern bearings, propeller overhung loading induces non-negligible shaft deflection across the bearing length, and the multi-support shafting makes the stern-bearing reaction force impossible to determine from rigid-body statics alone. Both assumptions must be removed within a single analysis framework. This study develops a coupled lubrication–rotor framework that combines a two-dimensional steady Reynolds solver with groove masking, a Winkler elastic liner, and a ROSS-based Timoshenko rotor finite element model through bidirectional reaction-force–tilt feedback. A normalised axial load distribution indicator Iw(z), defined from the axial film-pressure profile, is introduced as a scalar boundary quantity linking the elastohydrodynamic lubrication solution to downstream wear evolution models. Condition decomposition and open-loop tilt sweeps show that the coupled-convergence tilt reduces hmin by 65.7%, raises pmax by 84.5%, and shifts the axial reaction-force distribution and Iw(z) peak toward the stern end. Axial non-uniformity intensifies monotonically with the increase in tilt angle, and beyond a threshold tilt, the HD/EHL solver no longer converges for a hard phenolic liner, establishing the applicability upper bound of the framework.

Two oleanane triterpenoids with a C-4 methyl substitution from Camellia oleifera Abel and their anti-inflammatory activities - Qing Li; Yijie Li; Chengqin Liang; Qijun Fan; Rui Huang; Binghai Lou; Jiangke Qin (Natural Product Research, 2026)

PLX3397 Reshapes Hepatic Lipid Metabolism Independent of Microglial Depletion - Jiahui Lyu; Wang Cheng; Chun-Yue Li; Jiayan Wang; Xiaorong Zhang; Huifang Lou; Yalin Hu; Zhihua Gao; Shumin Duan; Kelei Cao (Neuroscience Bulletin, 2026)
Colony-stimulating factor 1 receptor (CSF1R) inhibitors, such as PLX5622 and PLX3397 (pexidartinib), are widely used for in vivo microglial depletion and for investigating microglial functions and therapeutic potential. Although CSF1R inhibitor-based studies have uncovered important roles for microglia in processes, such as anesthesia, addiction, and obesity, whether the resulting phenotypes reflect microglial depletion alone remains increasingly debated. Our previous work has shown that PLX5622 activates hepatic constitutive androstane receptor (CAR)-dependent xenobiotic metabolism, altering the metabolism of anesthetics and addictive drugs, and amplifying apparent microglial phenotypes. Whether other CSF1R inhibitors, particularly the FDA-approved PLX3397, exert systemic metabolic effects that may influence the interpretation of brain phenotypes remains unknown. Here, we demonstrate that PLX3397 exerts hepatic metabolic effects that are mechanistically distinct from those induced by PLX5622. Although PLX3397 only weakly affects xenobiotic metabolism, it markedly enhances endogenous hepatic lipid metabolism, inducing a fasting-like state characterized by increased lipid utilization and ketogenesis despite the absence of nutrient deprivation. By uncovering previously unrecognized peripheral effects of PLX3397, our findings identify brain-periphery interactions as a potential source of confounding in studies of microglial function. These results suggest that systemic metabolic effects should be carefully considered when interpreting neural or behavioral phenotypes in pharmacological microglia depletion paradigms.

Two new five-membered heterocyclic compounds isolated from Polygonum tinctorium - Pei-yuan Yang; Wei-qi Zhang; Ya-jie Yuan; Li-li Lou; Xiao-xiao Huang; Shao-jiang Song (Natural Product Research, 2026)

Integrating global and local features for multisource remote sensing image classification with 2D Selective Scan Fusion - Leiquan Wang; Guixiang Lou; Xin Li; Xueqing Yang; Chunlei Wu; Zhongwei Li (International Journal of Remote Sensing, 2026)

Structure-aware prediction of functional non-synonymous variants in a maize EMS mutant library - Li Qin; Xiaolong Guo; Fan Xia; Fugui Xie; Yu Bao; Manzhu Jiang; Tianhao Wu; Yuxuan Lou; Xiangfeng Wang; Xuerong Yang; Xiaoduo Lu (Molecular Plant, 2026)

Micro-nano biochar interfaces promote adsorption-reduction coupling to accelerate bioelectrodechlorination in groundwater - Zena Zhang; Miao Lv; Rui Wang; Bo Wang; Ruoyu Du; Yuxuan Lou; Chunlin Wang; Xiaodun Jiang; Hai Hou; Zhiling Li; Fan Chen (Journal of Hazardous Materials, 2026)

Anchorage performance of large-diameter high-strength steel bar grouted corrugated duct connections: Experimental study, numerical simulation, and reliability analysis - Cexiang Lou; Junsheng Su; Feihong Xin; Hao Gao; Yongkang Miao; Jiajun Li; Zhong-Xian Li (Engineering Structures, 2026)

Artificial cell-free pathway for carbon-efficient glycerol-HCO3− conversion to l-aspartate with ATP and cofactor trade-offs - Long-wei Lou; Zi-hang Xi; Zong-lin Li; Zhi-min Li (Bioresource Technology, 2026)

Deciphering chemical composition of Eucalyptus globulus essential oil and its bioactivities compared with 1,8-cineole and α-pinene: in vitro and in situ antimicrobial, antibiofilm, and insecticidal perspectives - Miroslava Kačániová; Stefania Garzoli; Minhang Qiao; Zhaojun Ban; Li Li; Jian Lou; Joel Horacio Elizondo-Luevano; Wissem Mnif; Rania Ben Saad; Anis Ben Hsouna; Alessandro Bianchi (Biocatalysis and Agricultural Biotechnology, 2026)

ATP-dependent binding cassette transporter ClABCI6 promotes the expression of citrus yellow vein clearing virus via inhibiting salicylic acid pathway - Yaqin Song; Wen Ge; Cuiyun Lei; Yijie Li; Yang Han; Jiedan Xiao; Xinghua Qiao; Shixue Hu; Yan Zhou; Binghai Lou (Journal of Plant Research, 2026)

Dual-stream feature-decoupling network for rapid and robust rice traceability using handheld Raman spectroscopy - Zhenfang Liu; Jing Li; Jungang Lou; Zhen Bi; Qing Shen; Kang Zhao (Analytica Chimica Acta, 2026)

Leguminous green manure drives SOC pool accumulation by regulating microbial activity and C-degrading genes in tropical soils - Long Jia; Peng Li; Tong Su; Zhuochen Lou; Jiale Ye; Ruiyun Yang; Jiaguo Jiao; Huixin Li; Feng Hu (Biology and Fertility of Soils, 2026)

HILPDA, Regulated by WTAP in an m6A-Dependent Manner, Enhances Osteosarcoma Development by Inhibiting Ferroptosis and Promoting Glycolysis - Yong Jing; Guoyong Zhang; Chenghui Sun; Yawei Pan; Jun Tuo; Zhi Li; Chengji Jiang; Zejian Qiu; Qin Lou (Biochemical Genetics, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

An integrated assessment of water and carbon footprints with energy evaluation in the cinnamon soil region of Northeast China - Yidong Zhao; Baoqing Chen; Yisheng Lou; Na Li; Lu Hua; Hongyan Gao; Qian Cai; Wei Bai; Wenyi Dong; Zhe Zhang (Environment, Development and Sustainability, 2026)

The intergenerational transmission of instrumental, relational, and intrinsic environmental values - Xiaobin Lou; Weiwei Xia; Liman Man Wai Li (Sustainability Science, 2026)

Performance evaluation and optimal design of inclined alternating rigid-core high-pressure jet grouting piles slope retaining structure: A case study in Guiyang, China - Junhao Liu; Fei Gan; Gang Zheng; Meilin Li; Licheng Wu; Wei Bao; Yu Ren; Xudong He; Qiang Lou; Hong Wang (Transportation Geotechnics, 2026)

Silica-induced telomere dysfunction promotes pulmonary fibrosis through the activation of the cGAS-STING pathway - Qiuqian Qian; Simiao Pan; Xiaodong Li; Xiaoxue Gong; Zhaoqiang Jiang; Xing Zhang; Jianlin Lou; Lingfang Feng (Toxicology, 2026)

Improving the sustainability of China's wheat production through a life-cycle food-energy-water-carbon nexus framework - Weijie Song; Shangkun Liu; Shirui Li; Ruitao Lou; Qingguan Wu; Zhiming Qi; Yu Tang; Yong He; Qianjing Jiang (Sustainable Production and Consumption, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Influence of sand particle size on fire suppression performance of oil well fires in desert - Zhen Lou; Guangchao Sun; Kai Wang; Xinyu Chang; Hengjie Qin; Sen Li; Nian Jiang; Haowei Yao (Process Safety and Environmental Protection, 2026)

Xylaricins A–I: Dearomatic xanthone derivatives from endolichenic fungus Xylaria sp. LCSS1a - Wenge Zhang; Lihua Zhu; Kunkun Zhang; Ke Xu; Xiaoyi Luan; Jiabo Sun; Hehe Li; Wenzhuo Tan; Jiaozhen Zhang; Xiuyun Li; Hongxiang Lou (Phytochemistry, 2026)

Research on a far-field acoustic radiation prediction method for underwater vehicles based on the superposition of prolate spheroidal wave functions - Jinfang Lu; Jingjun Lou; Ronghua Li; Shuyong Liu (Ocean Engineering, 2026)

Thioglycolic acid-modified polysilicate aluminum titanium for high-efficiency Cu2+ removal - Sifan Liu; Jiatong Li; Yurong Zhang; Yongwei Ji; Dawei Lou (Journal of Water Process Engineering, 2026)

Indole metabolites produced by Lactobacillus acidophilus impedes bisphenol F- aryl hydrocarbon receptor interaction and ameliorates bisphenol F induced depression-like changes - Miaoyang Hu; Ayiguzaili Manglike; Xiaozhu Li; Jin Wei; Xinyu Lou; Jing Liu; Zhiru Tang; Weiping He; Guixiang Ji; Wenjuan Wang; Tengfei Ma; Rong Gao; et al. (Journal of Hazardous Materials, 2026)

Overcoming spatiotemporal attenuation: A deep learning model for collaborative prediction of PM2.5 and O3 in Beijing urban areas - Xiaoyang Liu; Yuyao Lou; Ao Li; Yunfeng Li; Feng Zhou; Jingming Qi; Haixin Guo; Yafei Wang (Journal of Environmental Chemical Engineering, 2026)

Novel reuterin-loaded chitosan–gelatin composite film and its application in chicken preservation - Mengxue Lou; Shuaiqi Ji; Kaixin Cao; Jingjing Li; Meichao Luo; Yilin Chou; Xinyi Zhang; Wenqian Li; Xiaoyun Wang; Rina Wu; Junrui Wu (Food Packaging and Shelf Life, 2026)

Immunomodulatory and anti-apoptotic effects of heme oxygenase-1 in hypoxia stress of small yellow croaker (Larimichthys polyactis) - Yang Liu; Qiaoling Yang; Xuebin Zheng; Li Wang; Jingqian Wang; Congcong Hou; Feng Liu; Junquan Zhu; Bao Lou (Fish & Shellfish Immunology, 2026)

Effects of legume-grass mixtures and systematic pasture management practices on forage yield, nutritive quality and resource use efficiency in an arid region - Muhammad Bilal Hafeez; Weiqi Jiang; Lan Li; Jiao Ning; Adilbek Nogayev; Shanning Lou; Shree Prakash Pandey; Fujiang Hou (Field Crops Research, 2026)

Fire resistance of steel-plate concrete composite panels: Experimental, numerical, and analytical investigations - Xiaofeng Zheng; Guo-Qiang Li; Guobiao Lou (Engineering Structures, 2026)

Hyperbranching enhanced antibacterial and antibiofouling performance of peptide dendrimers on aluminum surfaces - Tong Lou; Chiyuan Yu; Xueqiang Zhuang; Jiangfan Chang; Yali Gao; Yanan Li; Haotian Wu; Chengqing Yuan; Xiuqin Bai; Pan Cao (Chemical Engineering Journal, 2026)

Uncovering the synergistical roles of interfacial catalysis and wettability of Janus membranes for anti-wetting and anti-fouling of membrane distillation - Xinyu Ye; Mengmeng Lou; Xiangming Xu; Lijun Meng; Baowei Hu; Fang Li (Chemical Engineering Journal, 2026)

Spatial confinement effect enhances the activity and thermal stability of Pt/CeO2 for CO oxidation via coating cobalt nitride layer - Min Li; Bifeng Zhang; Lijun Ni; Qi Zhang; Jing Xu; Ying Zhang; Chengsi Pan; Wei Tan; Yongfa Zhu; Fudong Liu; Yang Lou (Chemical Engineering Journal, 2026)

A wearable sonodynamic therapy platform with a piezocatalytic nanocomposite hydrogel for diabetic wound healing - Jinyu Lin; Moxu Wang; Hongchao Li; Yuxin Wang; Jie Xu; Xiandi Jin; Xiaoming Lou; Tao Liu; Zhixuan Liu; Wenwu Cao; Hua Yuan; Xiaohua Jian (Chemical Engineering Journal, 2026)

Illicium verum essential oil versus (R)-(+)-Limonene: A comparative study of antimicrobial and insecticidal properties - Miroslava Kačániová; Minhang Qiao; Guiguo Zhang; Alessandro Bianchi; Joel Horacio Elizondo-Luevano; Anis Ben Hsouna; Rania Ben Saad; Zhaojun Ban; Li Li; Jian Lou; Maciej Ireneusz Kluz; Stefania Garzoli (Biocatalysis and Agricultural Biotechnology, 2026)

Unveiling seasonal dynamics of nitrate aerosols: A crucial step in understanding atmospheric pollution - Qinghong Wang; Jialin Shi; Mingzhe Li; Wenfei Zhu; Liping Qiao; Jun Chen; Shengrong Lou (Atmospheric Pollution Research, 2026)

Astrocyte-Driven Modulation of Whole-Brain Functional Networks and BOLD Signals Revealed by Optogenetic-fMRI - Zhuang Liu; Li Wang; Tiangang Lou; Ziyue Zhao; Hongying Du; Juxiang Chen; Hongchun Zeng; Jie Wang; Kun Wang (Neuroscience Bulletin, 2026)

Halotolerant plant growth-promoting bacteria Enterobacter sp. Av16 and Acinetobacter sp. Av23 enhance seed germination and seedling photosynthesis of Apocynum pictum under salt stress - Xue Wang; Li Jiang; Yao Ge; Yiping Zou; Qingsheng Cai; Yan Xia; Laiqing Lou (Journal of Zhejiang University-SCIENCE B, 2026)

Synergistic organic amendments show broad potential for context-specific regulation of soil available iron in croplands - Hongyu Yu; Bingyue Yu; Erxu Xue; Chen Fu; Jing Chen; Ruiqi Yao; Pengfei Liu; Binggan Lou; Qingxu Ma; Li Chen; Kuan Xu; Jiuzhou Chen; et al. (Applied Soil Ecology, 2026)

Characterization of the corticotropin‐releasing hormone family in largemouth bass and their expression profiles in response to feeding and acute and chronic heat stress - Jinxing Du; Wenhui Lou; Tao Zhu; Hongmei Song; Caixia Lei; Jing Tian; Shengjie Li (Journal of Fish Biology, 2026)
Elevated cortisol levels reduce appetite and inhibit growth in fish, a process mediated by corticotropin‐releasing hormone (CRH) family members. However, the specific role of CRH members in appetite regulation in largemouth bass ( Micropterus nigricans ) remains unclear. In this study, we identified the CRH family members in bass and analysed their expression profiles in response to feeding, acute heat stress and chronic heat stress conditions. Five CRH members (Crha, Crhb, Uts1, Ucn2 and Ucn3) were identified in bass. These genes were highly expressed in the brain and intestinal tissues. Within 24 h of feeding, hypothalamic expression of chra decreased initially, reaching a minimum at 3 h post‐feeding, then increased. In contrast, crhb , uts1 and ucn3 expression rose initially, peaking at 3 h, then declined. Ucn2 expression declined significantly throughout a 24‐h period. During 24‐h acute heat stress, serum cortisol levels and hypothalamic expression of crhb , uts1 and ucn3 increased significantly, peaking after 3 h at 33°C, then declining after heating ceased. Conversely, crha and ucn2 expression decreased. After 8 weeks of chronic heat stress, serum cortisol levels were significantly higher in the 33°C group than in the 25°C group. Hypothalamic expression of crhb and ucn3 significantly upregulated, ucn2 was downregulated, while crha and uts1 remained unchanged. Taken together, the coordinated upregulation of hypothalamic crhb and ucn3 with elevated serum cortisol levels under both acute and chronic heat stress, coupled with their expression patterns, is consistent with a potential anorexigenic role for these peptides. Conversely, the downregulation of ucn2 under these conditions aligns with a potential orexigenic function. This study provides insights for future breeding of heat‐tolerant varieties of largemouth bass.

A novel index for the comprehensive assessment of competitive relationships in maize–weed communities using UAV-based hyperspectral data - Caixia Wang; Longzhe Quan; Fei Wang; Jian Xu; Guoxiang Zhang; Xiaojie Li; Chen Ru; Zhaoxia Lou; Chuan Wang; Zhiming Guo (Computers and Electronics in Agriculture, 2026)

Occurrence characteristics, cross-media behavior, and influencing factors of antibiotics and ARGs in typical rivers around the Bohai Sea - Hui Gao; Bing Li; Ruijing Li; Yingbin Lou; Xuan Jia; Shuang Zhang; Ziwei Yao (Marine Pollution Bulletin, 2026)

Improved masculinization effect induced by letrozole via suppression of the feminization through AMH signaling in mandarin fish (Siniperca chuatsi) - Kai Yang; Xing Chen; Jiankang Bao; Gang Zhai; Xuehui Li; Hongfei Bao; Xia Jin; Jiangyan He; Huijie Wei; Yin-ai Gao; Zhan Yin; Qiyong Lou (Aquaculture, 2026)

Employing Bio-LOHAS strategy for ammonia-laden tetracycline-rich wastewater treatment - Zhenhao Wang; Wei Lou; Jiale Wang; Zili Zhou; Hao Yin; Zhaowei Huang; Hong Li; Feixiang Zan; Juan Mao; Xiaohui Wu; Xiejuan Lu (Journal of Water Process Engineering, 2026)

A Data-driven framework for temperature prediction and control of megawatt alkaline electrolyzers based on LSTM-Transformer hybrid model - Shuyuan Wang; Xinying Duan; Hongwei Zhan; Jing Zhang; He Chen; Lei Zhang; Guizhi Xu; Jie Song; Qinghui Lou; Yanlong Li; Yu Yang; XiangJian Shi; et al. (Fuel, 2026)

Dynamic thermal response and sensation prediction under different showering temperatures and flow rates with cold ambient environment - Yi Gao; Xiaojing Li; Jinyuan Lou; Yange Lang; Shiyi Hong; Xiang Zhou; Maohui Luo (Energy and Buildings, 2026)

Surface modification enables high calendar aging performance of prelithiated SiOx anode for long-lifespan lithium ion batteries - Zhaolin Li; Yanqin Lou; Yihong Yao; Jie Wang; Hailei Zhao (Chemical Engineering Journal, 2026)

Photo-induced in-situ synthesized nanocellulose-based SERS substrate integrated with molecularly imprinted polymer for selective detection of pesticide residues - Xingyue Liu; Liucheng Meng; Wen Deng; Yuzhou Yang; Yanling Lou; Jianfeng Xi; Peng Li; Lei Zhang; Weibing Wu (Carbohydrate Polymers, 2026)

Sex and age disparities in goserelin safety: a global pharmacovigilance study - Zizhen Liu; Han Qu; Zuan Li; Shuowen Wang; Zhenghua Wu; Xin Zhao; Guorong Fan; Yuefen Lou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Expression，co-localization and interaction analysis of mitochondrial membrane proteins prohibitin and stomatin-like protein 2 during spermatogenesis in Larimichthys polyactis - Li Wang; Wenying Dai; Yang Liu; Shifan Chu; Yiner Chen; Congcong Hou; Feng Liu; Junquan Zhu; Bao Lou (Animal Reproduction Science, 2026)

Augmentation of dmrt1 leads to gonadal differentiation towards testis in cyp17a1−/−;XX common carp - Shengchi Shi; Xinyi Wang; Jingyi Jia; Guanghui Chen; Hongfei Bao; Xuehui Li; Qiyong Lou; Qingyun Yuan; Jiangyan He; Jian Wang; Xueqiao Qian; Gang Zhai; et al. (Aquaculture, 2026)

Recent advances in metal-phenolic networks for delivery and removal: properties, applications, and future perspectives - Xin Zhang; Ikram Alouk; Hui Liang; Guangjian Li; Yutao Wang; Yufei Cao; Wen-Yong Lou (Trends in Food Science & Technology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Restoration of fire-damaged high-performance concrete columns by post-fire water-CO2 cyclic curing - Hangqi Lou; Tiejun Liu; Dujian Zou; Ye Li (Engineering Structures, 2026)

Horizontal evolution characteristics of near-inertial sea surface currents induced by the tropical cyclones in the Guangdong-Hong Kong-Macao Greater Bay area - Lei Ren; Hexu Wang; Beinuo Zhou; Xiaofan Lou; Zhenglin Li; Long Bai; Fan Yang; Zhenchang Zhu; Fearghal O'Donncha; Jun Wei; Michael Hartnet (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Selenium regulates pyroptosis through the ROS-mtDNA-cGAS-STING axis to alleviate trimethyltin chloride-induced inflammation in chicken kidneys - Huiling Zheng; Xinyu Huo; Wenwen Zhang; Shuang Lou; Mingyue Li; Chenxi Huang; Kang Yang; Tong Xu; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Mitochondrial stress primed cGAS-STING activation synergized with NF-κB signaling for enhanced antitumor immunotherapy - Chengzhilin Li; Fanyu Yuan; LiHang Lou; Ziang Xu; Nianlei Zhang; Changshun Huang; Xinyu Wang; Wenyu Zhang; Tingjian Zu; Ming Xia; Runxiao Zheng (Chemical Engineering Journal, 2026)

A ROS scavenging multifunctional hydrogel crosslinked with EGCG promotes the healing of pressure injuries via Nrf2 pathway - Yingying Pan; Jiaying Lou; Yuqi Wang; Rongfang Dai; Miwen Zou; Danni Ma; Shengzhang Chen; Jinghao Zhou; Binyan Chen; Xiaoqiong Jiang; Pan Huang; Huaqiong Li; et al. (Chemical Engineering Journal, 2026)

A mutation in CsBRP1, encoding a PHD-type domain-containing protein, causes semi-dwarfism in cucumber (Cucumis sativus L.) - Xiaoxu Han; Juan Yin; Xueying Jiao; Ruolin Hu; Yingjie Zhang; Fahang Chen; Biao Dong; Chunyan Cheng; Yuhui Wang; Chunhua Wang; Ji Li; Tao Wu; et al. (Theoretical and Applied Genetics, 2026)

Differential responses of soil microbial community structure and function to conventional and biodegradable microplastics - Yuhan Liu; Xue Bei; Chuanwei Zheng; Hong Lou; Huimei Tian; Wenjing Han; Wenxiao Sun; Songyan Jiao; Shuo Li; Bing Li; Lusheng Zhu; Zhongkun Du; et al. (Applied Soil Ecology, 2026)

Optical-fiber sensors for dissociation constant measurement of aptamer and rapid detection of ampicillin in river water and milk - Guangxin Zhang; Haixu Zhao; Xiaoqi Li; Yi Zhang; Haijing Jia; Qiaoqiao Zhang; Tianyu Dai; Xinhui Lou (Analytica Chimica Acta, 2026)

Cover crops potentially enhance soil organic carbon sequestration to offset greenhouse gas emissions without yield penalty towards net-zero rice agriculture - Ruitao Lou; Yong Li; Zhenghan Li; Zhifeng Xu; Yu Tang; Xiangping Jin; Junzeng Xu; Yawei Li; Yong He; Qianjing Jiang (Agriculture, Ecosystems & Environment, 2026)

Identification and full genome characterization of a novel CRESS DNA virus associated with giant freshwater prawn, Macrobrachium Rosenbergii - Qi Guo; Yiniu Ji; Weifeng Shen; Bao Lou; Sunjian Lyu; Li Liu (Archives of Virology, 2026)

Wave-Induced Seabed Pore Pressure and Forces on a Buried Pipeline Under Cross-Shore Profile Evolution - Musheng Yang; Jiaqi Xiong; Titi Sui; Youjia Li; Min Lou; Yangyang Wang (Journal of Marine Science and Engineering, 2026)
In view of the complex seabed response and pipeline force characteristics induced by wave loading and long-term cross-shore profile evolution on shoreward submarine pipelines, this study investigates the coupled effects of profile evolution, burial depth, and pipeline angle on the surrounding seabed and resulting wave-induced forces. Physical model experiments were conducted in a wave flume under irregular wave conditions. A controlled variable design was adopted, dividing the experiments into five main groups and 17 subgroups based on the pipeline angle, initial burial depth, and seabed topography at different evolution stages. Pore pressure around the pipeline and wave height were measured synchronously, and seabed topography was scanned using a laser system. The results show that increasing the initial burial depth reduces both pore pressure and forces on the pipeline. Under cross-shore profile evolution, pore pressure and forces in sedimentation zones are lower and decrease further with continued evolution, whereas the opposite trend is observed in erosion zones. Changes in pipeline angle induce an asymmetric pore pressure distribution around the pipeline, with the resultant force first decreasing and then increasing. The direction of the resultant force shows greater rotation amplitude in sedimentation zones while, in erosion zones, the direction remains more concentrated. In sedimentation zones, pore pressure decreases and force changes are relatively gradual; in erosion zones, pore pressure increases and force changes are more pronounced. Overall, the variations in force direction and magnitude exhibit distinct characteristics depending on the zone type. These findings provide a scientific basis for the rational design of shoreward pipelines, enabling stability and safety optimization through integration with cross-shore profile evolution patterns, reducing engineering risks, and enhancing the economic viability and reliability of nearshore pipeline projects.

Valorization of sauce-flavored Baijiu wastewater as a nutrient medium for enhanced production of γ-aminobutyric acid by Monascus purpureus - Xuanchen Li; Xin Yang; Mian Wang; Shuangping Liu; Yuena Luo; Shuyi Qiu; Yuangen Wu; Wangni Meng; Jian Mao; Jianli Zhou; Wenyong Lou (Journal of Environmental Management, 2026)

Microenvironment engineering for enhancing catalytic active sites for the CO oxidation reaction - Menghe Lou; Li Xiang; Guo Nie; Xueqing Luo; Renna Li; Feng Bi; Xiaole Weng; Zhongbiao Wu (Journal of Environmental Sciences, 2026)

Synergistic antibacterial activity and mechanism of surfactin and Ag NPs against Pseudomonas fluorescens - Yutong Wu; Yushuang Li; Zheyun Dong; Yongyong Li; Huicheng Yang; Liqing Wu; Yongjiang Lou; Shiqian Fu (International Journal of Food Microbiology, 2026)

Quantifying CO2 hydrate sequestration: a multi-physics simulation of megatonne-scale transport and millennial-scale trapping dynamics - Shuxia Li; Benkui Lou; Gaowei Hu; Qingtao Bu; Zhongxue Song; Lu Liu; Yang Guo (Fuel, 2026)

Towards detailed cellularization morphology and intrinsic instability analysis of ammonia/hydrogen spherical expanding flame - Cangsu Xu; Zhentao Fan; Yushuo Lou; Xiaolu Li; Francis Oppong; Niankuang Wu (Fuel, 2026)

Identification and quality evaluation of Camellia sinensis cv. Longjing 43 fresh leaves from Enshi with different altitudes based on non-targeted metabolomics combined with chemometrics - Ruixin Lou; Liangji Wu; Qiang Zhang; Kaikai Li; Tao Hou (Food Research International, 2026)

In silico discovery of a novel sheep whey protein-derived antimicrobial peptide: antimicrobial activity, mechanism of action, and application - Shuaiqi Ji; Mengxue Lou; Feiyu An; Yilin Chou; Yi Zhu; Jiawei Guo; Meichao Luo; Taowei Zhang; Wenqian Li; Xinyi Zhang; Rina Wu; Junrui Wu (Food Bioscience, 2026)

Transcriptome analysis reveals the response mechanism of largemouth bass (Micropterus salmoides) brain to MSRV infection - Qi Guo; Pengfei Wang; Bao Lou; Weifeng Shen; Mingming Han; Wenzhi Guan; Sunjian Lyu; Li Liu (Fish & Shellfish Immunology, 2026)

Deep-learning-based surrogate model for solute transport in rough-walled fractures - Haoyu Xue; Wenjie Xu; Yihuai Lou; Yingtao Hu; Wu Gao; Jinlong Li; Duanyang Zhuang; Wei Liu; Liangtong Zhan; Yunmin Chen (Computers and Geotechnics, 2026)

Localized chemotherapy through metabolic stabilization and in situ gelation for ratio-locked delivery to maximize cytotoxicity and trigger immune responses - Jiaming Zhang; Xinyu Lou; Xiaolan Xu; Yingchao Li; Chenxia Bai; Qing Yan; Yanfang Wang; Yixiu Zhai; Jingdong Xiao; Mengchi Sun; Yinghou Wang; Jin Sun; et al. (Chemical Engineering Journal, 2026)

Confined-space volume compression for ultra-thin and tough composite hydrogel films via enhanced hydrogen bond crosslinking - Minghao Lou; Zhuangzhuang Ma; Lijuan Shi; Jiale Zhang; Wanting Li; Hongqiang Wang; Lichao Jia (Chemical Engineering Journal, 2026)

Porous polybenzimidazole membrane with enhanced phosphoric acid retention derived from incorporation of confined metal organic frameworks for high-temperature proton exchange membrane fuel cells - Yaohu Li; Shiying Tu; Guoliang Liu; Hongfei Pan; Yun Jia; Wenbo Lou; Haolin Tang; Haining Zhang (Chemical Engineering Journal, 2026)

Rewiring prenyl donor supply for orthogonal synthesis of prenylated compounds in yeast - Guangjian Li; Pan Li; Zhiyao Wang; Jiayan Lyu; Mei Li; Pengsheng Yang; Jingwen Zhou; Yufei Cao; Wen-Yong Lou (Chemical Engineering Journal, 2026)

Engineering active Cu species at hydrotalcite-derived Cu-ZnO interfacial sites for boosting methanol production from CO2 hydrogenation - Guoqing Cui; Yingjie Lou; Yiyang Hu; Mingxia Zhou; Yuming Li; Yajun Wang; Lirong Zheng; Wei Wang; Guiyuan Jiang; Chunming Xu (Chemical Engineering Journal, 2026)

Calculation method for configuring a photovoltaic pumping system for the efficient use of climatic resources - Jiyi Gong; Shengtian Yang; Hezhen Lou; Baichi Zhou; Yin Yi; Chengcheng Gao; Ming Tang; Xueyong Huang; Zhirui Wen; Zihao Pan; Yifan Zhu; Cheng Feng; et al. (Irrigation Science, 2026)

COL8A1-positive cancer-associated fibroblasts are drivers of 5-fluorouracil resistance in colorectal cancer - Muzi Ding; Yue Li; Zixuan Liu; Shangshang Hu; Jinwei Lou; Yuhan Chen; Jian Qin; Mu Xu; Huiling Sun; Tao Xu; Shukui Wang; Yuqin Pan (Apoptosis, 2026)

Green Synthesis of Nitrogen-Doped Carbon Quantum Dots from Medium-Molecular-Weight Chitosan for Ultrasensitive Fe³⁺ Detection and Responsive Probe - Lulu Feng; Hainan Li; Zishuai Zhang; Shuang Pang; Zhiyu Liu; Jiahao Lin; Shiyu Wang; Zhenning Lou (Journal of Fluorescence, 2026)

The role of biological factors in nitrogen attenuation in ditch: An innovative approach through quantification of biological factors - Xulin Zhang; Gaofei Yin; Zihan Zhang; Yang Lou; Peipei Feng; Lingling Hua; Hongbin Liu; Wenchao Li (Journal of Hydrology, 2026)

Cr-doped CeO2 enables wettability-matched Pt catalysts for nearly complete lignocellulose conversion - Pingping Lu; Weichao Chou; Jun Li; Nan Shi; Lunan Wu; Bin Lou; Jing Wu; Dong Liu (Journal of Environmental Chemical Engineering, 2026)

In-situ assembly of vertically-grown SnS2 nanosheets on TiO2 microspheres for efficient photocatalytic nitrogen fixation - Huijun Liang; Xinyu Wang; Yuanyuan Ji; Xin Li; Xiang Zhen; Jianxun Dong; Feijian Lou; Hongjun Chen; Zhichao Jia; Huiran Zhou; Xiaobing Wang (Fuel, 2026)

Post-mortem analysis of degradation behavior in catalyst layers of proton exchange membrane fuel cell under near-water boiling temperature - Daijun Yang; Bo Zhou; Yirui Lu; Jiaming Lou; Bing Li; Pingwen Ming (Fuel, 2026)

Release characteristics and kinetic model of alkali metals during municipal solid waste incineration based on multipoint laser-induced breakdown spectroscopy - Nanxi Bie; Yongda Huang; Yi Huang; Shuai Li; Aijun Li; Hongyun Hu; Xian Li; Guangqian Luo; Chun Lou; Hong Yao (Fuel, 2026)

Deciphering the potential risks of Yersinia enterocolitica across multi-points in food chain: prevalence, biofilm, and cross-stage transmission routes - Zhiguo Fang; Juran Mao; Zongzong Chen; Yue Wu; Xueqin Zhao; Rui Tian; Ye Lv; Xiao Xiao; Jiaqi Yan; Xiuqin Lou; Jun Li (Food Research International, 2026)

Optimizing harvest aid applications for mechanical cotton harvesting: A meta-analysis of defoliation–yield trade-offs driven by crop physiology and environmental factors - Zhenwang Zhang; Yukun Wang; Xinghua Yu; Keke Yu; Huijie Hou; Qinghua Liao; Kexin Li; Zhijie Shi; Jianxin Dong; Guodong Chen; Sumei Wan; Shanwei Lou; et al. (Field Crops Research, 2026)

Interactive effects of enhanced-efficiency N fertilizers and fulvic acid on ammonia volatilization and inorganic N leaching in saline soil - Hui Wang; Hongtao Hao; Xiaozhen Zhao; Zhenxin Guo; Dejie Yu; Chao Li; Wenzheng Liu; Yanhong Lou; Hong Pan; Quangang Yang; Zhongchen Yang; Yajie Sun; et al. (Environmental Research, 2026)

Novel deep-blue tetradentate Pt(II) emitters via steric hindrance and alkyl ring locking for high-performance PhOLEDs with small efficiency roll-off - Miao Sun; Yunyang Yuan; Kewei Xu; Feng Zhan; Hongjian Zheng; Qingshan Chu; Weiwei Lou; Yun-Fang Yang; Yuanbin She; Guijie Li (Chemical Engineering Journal, 2026)

Mesoporous catechin nanocarriers potentiate curcumin to treat osteoarthritis via synergistic antioxidant and macrophage repolarization - Xinyu Zhang; Junyan Li; Ye Zhu; Huilin Hu; Ping Gong; Hui Xu; Ningli Guo; Quanzhou Wu; Chao Lou; Minghao Chao; Zhang Chen; Minjiang Chen; et al. (Chemical Engineering Journal, 2026)

Preparation and Characterization of Lightweight Ceramsite from Construction Waste and Coal Fly Ash - Xue Song; Weishuang Lou; Zhengqiu Li; Bopeng Zhao; Lin Wang; Xiu Li; Yuejiao Zhang; Wenjing Sun; Yingming Zhang; Yongde Liu; Hongyun Yang (Water, Air, & Soil Pollution, 2026)

A Metabolomic Study Reveals Substantial Genetic Variation in Volatile and Non-Volatile Compounds in Sugarcane Juice - Xianli Li; Hongbo Lou; Ze Lu; Lingling Dong; Lilian He; Fusheng Li (Sugar Tech, 2026)

Therapeutic Potential of MgH2 in Mitigating Cisplatin-Induced Hearing Loss - Yibing Hu; Yihuan Zhang; Shufen Li; Yuan Yu; Jingjing Wang; Zihan Lou; Boya Zhang; Yazhi Xing; Zhengnong Chen (Neuroscience Bulletin, 2026)

Organic fertilization improves activities of phosphomonoesters hydrolase in rhizosphere to facilitate phosphorus acquisition in cucumber and accumulates organic phosphorus in soil - Bingshuang Wang; Yuan Wang; Xihe Zhang; Xiaodan Hu; Shujun Li; Yifei Sun; Yang Wang; Yan Sun; Ziwei Dai; Yunsheng Lou; Rong Li; Guohua Xu; et al. (Applied Soil Ecology, 2026)

Dietary soybean isoflavones modulate reproductive hormones and immunity by altering rumen microbiota in ewes - Mengqi Lou; Xiongxiong Li; Shengguo Zhao; Jinlong Xu; Qingshan Fan; Yuzhu Sha; Jie Bai; Ting Jiao (Animal Feed Science and Technology, 2026)

Longitudinal biomarker trajectories and their prognostic utility for 21-day mortality in burn patients with sepsis: a retrospective cohort study - Jiaqi Lou; Hong Kong; Jiliang Li; Ziyi Xiang; Xiaoyu Zhu; Shengyong Cui; Neng Huang; Sida Xu; Guoying Jin; Xin Le; Youfen Fan (Inflammation Research, 2026)

Modification of Surfactin and Its Inhibition Mechanism Against Two Dominant Spoilage Bacteria in Aquatic Products - Yushuang Li; Yutong Wu; Yongyong Li; Huicheng Yang; Liqing Wu; Yongjiang Lou; Shiqian Fu (Journal of Aquatic Food Product Technology, 2026)

A rapid method to generate an all-female population in common carp (Cyprinus carpio) using the neomale carp of F0 population with targeted aromatase mutations - Yuting Xie; Hongfei Bao; Guanghui Chen; Xuehui Li; Yonglin Ruan; Qiyong Lou; Xia Jin; Jiangyan He; Tianshu Zhang; Jian Wang; Xueqiao Qian; Gang Zhai; et al. (Aquaculture, 2026)

Interplay of charge composition and nanochannel confinement in ion separation through graphene oxide membranes - Xiaowei Zhu; Kecheng Guan; Feidong Yang; Chuang Li; Ryosuke Takagi; Liheng Dai; Yanyan Liu; Xueru Yan; Mengmeng Lou; Fang Li; Hideto Matsuyama (Water Research, 2026)

BoLrgB promotes programmed cell death of postharvest broccoli through regulating antioxidant pathways under oxidative stress - Jiacheng Li; Jiajun Lou; Jiahui Chen; Shifeng Cao; Yi Chen; Yingying Wei; Xingfeng Shao; Feng Xu (Postharvest Biology and Technology, 2026)

Study on the influence of ducted parameters on hydrodynamic performance of ducted propellers for underwater cage cleaning robots - Chengze Xu; Junhua Chen; Yinghou Lou; Hao Li (Ocean Engineering, 2026)

Nonlinear affine transformations for correlation-based terrain matching navigation - Tian Lan; Ding Li; Qixin Lou; Chao Liu; Huiping Li; Yi Zhang; Xudong Yu (Ocean Engineering, 2026)

Dissection of the genetic basis of 1392 rice landraces and 770 hybrid combinations reveals great potential of rice landraces in hybrid rice improvement - Yinting Wang; Zixuan Li; Bi Wu; Xueqiang Wang; Wenyan Yang; Danjing Lou; Jinyue Ge; Ziran Liu; Wenlong Guo; Neng Zhao; Jun Yang; Weiya Fan; et al. (Molecular Plant, 2026)

Simulated Microgravity affects immune reaction to infection through altering lymphocyte differentiation, cytokine secretion, and macrophage polarization - Hongyan Cai; Rui Jia; Huimin Chen; Yingying Wu; Yaya Qin; Shaoyan Si; Lei Zhu; Xiaotong Lou; Xiangru Li (Life Sciences in Space Research, 2026)

Associations between concentrations of microplastics in follicular fluid and the risk of diminished ovarian reserve - Yuanyuan Zhou; Yijie Lu; Yujia Luo; Jingping Li; Weikang Chen; Yingming Zheng; Wenshan Zeng; Hangying Lou (Journal of Hazardous Materials, 2026)

Advancing image super-resolution techniques in remote sensing: A comprehensive survey - Yunliang Qi; Meng Lou; Yimin Liu; Lu Li; Zhen Yang; Wen Nie (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Enhanced melanin production in Inonotus hispidus by the use of agricultural straw - Hu Lou; Tianyi Long; Enze Yu; Yurong Liang; Weizhi Wang; Tuo Li; Jie Zhang; Guocai Zhang (Food Chemistry, 2026)

Post-mortem analysis of the degradation behavior of the fuel cell gas diffusion layer under near to water boiling point conditions - Yirui Lu; Daijun Yang; Jiaming Lou; Bo Zhou; Xiangyang Zhou; Xiangmin Pan; Bing Li; Pingwen Ming (Chemical Engineering Journal, 2026)

A pH/glucose dual-responsive Janus dressing with optimized gradient modulus/tissue adhesion promotes diabetic wound healing by dynamic drug-payload release - Huabiao Ye; Ting Dong; Ruoxuan Li; Lihua Fang; Kaifang Xie; Guangting Han; Que Chen; Shan Chi; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2026)

Photothermal-pancaking synergy in interfacial absorption enables rapid purification of viscous oil-in-water emulsions - Ruoxuan Li; Chaofan Zhu; Ching-Wen Lou; Kaifang Xie; Jia-Horng Lin; Guangting Han; Que Chen; Ting Dong (Chemical Engineering Journal, 2026)

A Heteroplasmic MT-CO2 m.8024G > A Variant Is Associated with Mitochondrial Bioenergetic Deficiency and Optic Atrophy - Jing Wu; Cunhui Pan; Ruowei Zhu; Xi Huang; Xiaoting Lou; Li Yang (Molecular Neurobiology, 2026)

Dispersive liquid-liquid microextraction combined with capillary electrophoresis for simultaneous determination of five fluoroquinolone antibiotics in marine crude drugs, seawater, and seafood samples - Yingying Lou; Guangli Zhao; Jingyi Yan; Dani Sun; Jinmao You; Huiquan Xiao; Huitao Liu; Guisheng Li; Jinhua Li (Journal of Oceanology and Limnology, 2026)

Optimized Design and Experimental Evaluation of a Vibratory Screening Unit for Mactra veneriformis Harvesting on Intertidal Mudflats Based on the Discrete Element Method - Bin Xu; Shuyuan Liang; Yuzhong Lou; Jixuan Zhao; Hangqi Li; Yizhi Chang; Hao Wu; Guangcong Chen; Gang Mu (Fishes, 2025)
To enhance shell–mud separation and overall harvesting efficiency for Mactra veneriformis under intertidal mudflat conditions, a vibratory harvesting device driven by a crank–rocker mechanism that produces approximately rectilinear simple-harmonic motion was developed. Dynamic analysis of clam motion on the screen deck identified vibration amplitude, vibration frequency, excitation direction angle, and screen deck inclination angle as key determinants of screening performance. Single-factor tests, a Plackett–Burman design, a steepest-ascent experiment, and response surface methodology (RSM) optimization were conducted. Their influences on forward travel speed ranked as follows: screen deck inclination angle > excitation direction angle > vibration amplitude > vibration frequency. The optimized settings were vibration amplitude of 8.5 mm, excitation direction angle of 45°, screen deck inclination angle of 11°, and vibration frequency of 10 Hz. Intertidal mudflat trials yielded a harvesting efficiency of 342 kg/h and a clam breakage rate of 4.6%, meeting the design targets. After harvesting, the shear strength of the mudflat decreased, with disturbance mainly confined to the surface layer, thereby meeting the low-disturbance requirement and enabling ecologically friendly harvesting. These results provide a basis for the design and optimization of M. veneriformis harvesting machinery.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Welding surface epitaxial layer enables high-loading sulfide all-solid-state batteries - Zhuomin Qiang; Yanbin Ning; Wei Zhao; Yajie Song; Chaoqun Zhang; Shengwei Dong; Yifei Zhao; Yan Zhang; Yinyong Sun; Biao Deng; Xudong Li; Geping Yin; et al. (Science Bulletin, 2025)

Preliminary safety risk assessment of parabens in children's cosmetics sold in China - Ren Wang; Cen Chen; Qiaoyuan Cheng; Yuanyang Wu; Linqi Yan; Zhen Xie; Zehua Li; Shanshan Liu; Yongjun Lou (Regulatory Toxicology and Pharmacology, 2025)

Structural analysis of a 15 MW floating offshore wind turbine platform based on a novel fully-coupled framework - Debang Nie; Shuai Li; Yangtian Yan; Yandong Lou; Jiaqing Yin; Jungang Hao; Yajun Ren; Fuqiang Wang; Chuangchuang He; Yang Yang (Ocean Engineering, 2025)

Behavior and mechanism of impurity removal in the process of producing ultra-low ash coal from long-flame coal by low-temperature alkali melting and acid step leaching - Xiaowei Deng; Jinwen Wu; Le Chen; Ruixue Lou; Guolong Zhong; Yihong Jia; Chaojun Fang; Hongxiang Xu; Gen Huang; Zhijun Zhang; Guosheng Li (Fuel, 2025)

Biocontrol potential of Bacillus subtilis Sjb3 against Rosa chinensis and apple diseases - Xiyan Lou; ManYu Chen; Ping Li; Yixue Cui; Chunhua Zhu; Dongdong Yu; Muhammad Anwar; Dongli Pei (Fungal Biology, 2025)

Effect of different emulsification parameters on soy-based cheese: Evaluation of textural, rheological, aroma and sensory properties - Huaixiang Tian; Juan Cheng; Li Li; Chen Chen; Xinxin Ma; Haiyan Yu; Xinman Lou (Food Chemistry, 2025)

The probiotic characteristics and antimicrobial mechanisms of Lactiplantibacillus plantarum ZFM55 - Shiying Wu; Jiayi Fan; Yi Xu; Yuenuo Luo; Luying Xie; Mingyang Hu; Yongqiang Chen; Fangtong Wei; Yuqing Lou; Ping Li; Qing Gu (Food Bioscience, 2025)

Interpretable data-driven models for the shear strength of perfobond rib shear connectors - Junbin Lou; Yixuan Li; Hao Meng; Rongqiao Xu (Engineering Structures, 2025)

Sequentially squeezed capacitive pressure sensor based on baguette-inspired porous ionic gel foams - Jian Cheng; Qingzheng Lei; Qibiao Yang; Lie Chen; Deyuan Lou; Qing Tao; Qianliang Li; Zhongsheng Zhai; Dun Liu (Chemical Engineering Journal, 2025)

Single-crystal layered oxide cathodes for sodium ion batteries: Mechanical failure and stabilized strategies - Kun Lin; Zhuomin Qiang; Shengwei Dong; Lin Zhou; Yanbin Ning; Yuqi Dong; Zhenxiang Xu; Dalong Li; Li Guan; Shuaifeng Lou (Chemical Engineering Journal, 2025)

Elucidation of Pt-Co synergistic effects in Pt30-Co50@WNxC1−x/W electrodes via operando DRT for enhanced HER kinetics - Yinquan Zhang; Hui Song; Tianjiao Lou; Wenqing Liu; Chunxia Lin; Jiangwen Xu; Guangshun Ran; Jinxu Song; Yukun Chang; Hongyi Li; Jinshu Wang (Chemical Engineering Journal, 2025)

High pressure torsion technology applied to ZnO nanomaterials for enhancing the room-temperature HCl sensing performance - Shuting Wei; Dan Yang; Renquan Guan; Peng Xu; Yuxin Wang; Yingmin Teng; Aicen Li; Junkai Zhang; Huaqiao Tan; Lili Wang; Zheng Lou; Wenjuan Zhang; et al. (Chemical Engineering Journal, 2025)

Supermolecule-engineered nanogap hotspots: Ultra-selective and sensitive SERS detection and intracellular imaging - Yuanjie Teng; Pei Xu; Zihang Zhou; Ning Xu; Jiayi Qiu; Yi Zhong; Jie Li; Haimin Shen; Zaifa Pan; Tianyu Hu; Xingchen Zhang; Yantao Lou (Chemical Engineering Journal, 2025)

In situ fabrication of bacterial cellulose-based CB@Poly(ionic liquid) membranes via surfactant-free ionic liquid microemulsion: Enhanced conductivity and mechanical flexibility - Na Gao; Caiyang Zhang; Minxin Song; Jiaxing Fan; Jinyue Li; Shunjie Li; Nan Lou; Guangshun Wu; Yuyang Liu; Jian Xue; Aili Wang (Carbohydrate Polymers, 2025)

Environmental chromium and cadmium co-exposure induces GADD45A-mediated rDNA instability in human cohorts and cell models - Yongxin Li; Yao Qin; Chuyan Zhang; Chan Ding; Minqian Feng; Yifan Dou; Xinran Wang; Xia Rao; Xiaoxue Gong; Zhaoqiang Jiang; Jianlin Lou; Huadong Xu (Chemico-Biological Interactions, 2025)

Novel compound bacterial agent effects on pig farm wastewater denitrification and nitrogen transformation - Rong Gao; Zhuangzhuang Liu; Weikun Li; Liu Lou; Tong Xu; Lin Shi; Jie Cao; Jun Fang; Gang Liu (Bioresource Technology, 2025)

Low-dosage hydrophobically modified copolymers as effective promoters in enzymatic hydrolysis of lignocellulosic biomass - Li Xu; Hongming Lou; Yuxia Pang; Xueqing Qiu (Bioresource Technology, 2025)

Study on the selective regulation of microbial community structure in microbial fuel cells by magnetic field–coupled magnetic carbon dots - Chao Zhao; Yangfan Song; Hongwei Chen; Yanmin Li; Ao Lei; Qianyun Wu; Lou Zhu; Qian He (Bioresource Technology, 2025)

Algae-induced anomalies in activated sludge sedimentation - Chenxuan Lou; Yuxiang Liang; Yanqing Zhang; Zhesong Zhou; Ying Chen; Dongqing Zhan; Pingli Li; Yangcheng Ding; Yafei Chen; Huajun Feng; Jionghui Li (Bioresource Technology Reports, 2025)

For cereal bran, rating of antioxidant capacity and screening of xanthine oxidase inhibitor - Ye Lou; Ming Cong Fan; Li Wang; Yan Li; Haifeng Qian (Bioactive Carbohydrates and Dietary Fibre, 2025)

The Development of a Prediction Model for In-Hospital Mortality of Pneumocystis Jirovecii Pneumonia among Kidney Transplant Recipients Based on the Trajectory of Absolute Lymphocyte Count - Yang Wang; Lixuan Lou; Yang Cong; Chunni Huang; Yuchao Zhou; Shutian Xu; Mingzhu Zheng; Shijun Li (Mycopathologia, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

TFAP2A-regulated CRNDE enhances colon cancer progression and chemoresistance via RIPK3 interaction - Xin Gao; Yanming Huang; Tonghui Wei; Jingmin Xue; Filippov Iurii; Laishou Yang; Liying Wang; Hao Li; Genshen Mo; Yuze Huang; Haonan Xie; Hang Wang; et al. (Functional & Integrative Genomics, 2025)

Summer PM2.5 concentrations in the northern subtropics modulated by the Hadley circulation edge location - Shuang Wang; Juan Feng; Sijia Lou; Jianping Li; Xuanliang Ji; Falei Xu (Climate Dynamics, 2025)

Cloning, Expression, and Odorant Binding Characteristics of the Chemosensory Protein 1 in Asecodes hispinarum, a Parasitoid of the Coconut Leaf Beetle - Keming Li; Fuping Lu; Huazhou Wu; Dezhao Lou; Peipan Gong; Tao Geng; Tao Jin; Jin Zhang; Shuchang Wang (Journal of Chemical Ecology, 2025)

The impact of lipid metabolism on ferroptosis in myocardial ischemia–reperfusion injury - Yuxin Li; Zekun Lou; Fang Liu; Yang Liu; Chaofan Wang; Yiwen Wang; Wei Qian; Dongye Li; Tongda Xu (Apoptosis, 2025)

ERO1A-positive tumor epithelial cells in colorectal cancer progression: a multi-omics perspective - Shangshang Hu; Jinwei Lou; Yuhan Chen; Muzi Ding; Jian Qin; Junjie Nie; Yue Li; Zixuan Liu; Mu Xu; Huiling Sun; Qianni Xiao; Yuqin Pan; et al. (Apoptosis, 2025)

Forecasting of water temperature and salinity in a coastal strait region using machine learning techniques - Lei Ren; Jianhao Gao; Liwei Wang; Zhenglin Li; Xiaofan Lou; Manman Wang; Qin Zhu; Zhenchang Zhu; Maximo Garcia-Jove; Lilia Flores Mateos (Acta Oceanologica Sinica, 2025)

Role of light irradiation in enhancing the aroma quality of green tea in spreading process: Regulatory strategies and practical application - Xianglin Kong; Jiayu Peng; Ruixin Lou; Liangji Wu; Luqing Li; Tao Hou; Kaikai Li (Trends in Food Science & Technology, 2025)

The response characteristics of fault-crossing tunnel subjected to different sequential combination actions of strike-slip fault dislocation and seismic wave propagation - Xiancheng Mei; Changdong Ding; Jianhe Li; Bo Lou; Zhen Cui; Mingnan Xu; Qian Sheng; Yajie Song; Jian Chen (Soil Dynamics and Earthquake Engineering, 2025)

Upgrading waste LiMn2O4 cathode for efficient photothermal polyester recycling - Xiangxi Lou; Penglei Yan; Qingqing Zhang; Binglei Jiao; Zhongyu Li; Panpan Xu; Muhan Cao; Jinxing Chen; Qiao Zhang (Science Bulletin, 2025)

Research on an electro-hydraulic individual pitch system of tidal current turbine - Pengpeng Zhang; Hongwei Liu; Yajing Gu; Liyan Lou; Yonggang Lin; Rongfu Li; Qingjun Li; Luoyang Huang; Jianzhong Tang (Ocean Engineering, 2025)

Mass spectrometry-based proteomics pipeline for screening hazardous proteins in alternative protein-based foods - Xiaowei Lou; Jared Lim; Bin Li; Dingyi Yu; Jayantha Gunaratne (Food Chemistry, 2025)

Rapid qPCR detection of Pseudomonas plecoglossicida and antimicrobial peptide dynamics in infected Larimichthys polyactis - Jiajie Zhu; Sifang Liu; Haowen Liu; Tianle Zhang; Qian Li; Honglin Chen; Ting Ye; Dandan Guo; Junquan Zhu; Bao Lou; Feng Liu (Fish & Shellfish Immunology, 2025)

Agricultural plastic Legacy in river Sediments: Abundance, oxidation, and occurrence characteristics of microplastics across rural China - Ge Ma; Kuangjia Li; Wei Zou; Rui Xin; Xiaohan Zhang; Jiaojiao Feng; Zheng Chen; Yinan Yang; Xiaomeng Lou; Kai Zhang; Fengxia Yang (Environmental Pollution, 2025)

Behaviour and fire resistance of mega concrete-filled steel box columns - Hong-Hui Qi; Yong-Chang Wang; Guo-Biao Lou; Guo-Qiang Li; Zhen Wang; Lingzhu Chen; Chenghao Wang (Engineering Structures, 2025)

Eccentric pull-out test and numerical investigation of bond behavior of corroded high-strength steel bars in ultra-high performance steel fiber-reinforced concrete (UHPSFRC) - Cexiang Lou; Junsheng Su; Xudong Zhao; Dianqi Wu; Jiaxing Ma; Zhong-Xian Li (Engineering Structures, 2025)

Modular synthesis of tetradentate Pt(II) complexes for structure-property studies and deep-blue OLED fabrications - Feng Zhan; Kewei Xu; Jianbing Zheng; Qidong Chen; Gang Shen; Jianxin Dai; Qi Feng; Hua Guo; Shun Liu; Jiale Ying; Jieying Tong; Weiwei Lou; et al. (Chemical Engineering Journal, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

Reconfiguration of the Fe N4 active site by S element and its effect on hydrogen evolution performance of Fe‑carbon dots SACs - Chenfang Lou; Qinfen Tian; Jiaqi Liang; Tingfeng Lin; Jiande Lin; Xinru Zheng; Xingyu Chen; Xin Li; Guofa Dong; Yuan Hu; Jiandong Zhuang (Chemical Engineering Journal, 2025)

Synergistic spin state and geometry engineering by constructing MoFe diatomic sites to catalyze non-radical and sustained oxidation of water pollutants - Chaofa Chen; Minjia Yan; Yu Li; Feng Chen; Zhangrong Lou; Xingshuai Lv; Xi-Lin Wu (Chemical Engineering Journal, 2025)

Creation of new rice germplasm with cross-resistance to auxin herbicides picloram and dicamba by genome editing of OsAFB4 - Haonan Wei; Dongling Li; Kexin Xie; Siying Lou; Guojun Dong; Fu Guo; Guiwei Lian; Xiangjian Pan; Zhanghui Zeng; Ning Han; Zhenyu Gao; Hongwu Bian (Theoretical and Applied Genetics, 2025)

Risk assessment of potentially toxic elements exposure through ganoderma lucidum consumption in the population of Longquan, China - Dingshuo Lou; Qi Li; Lv Ji; Junfei Hong; Hongyao Hu; Yang Yu (Environmental Geochemistry and Health, 2025)

L-GSH@AgNPs deprotonation hyperfine coupling with Ru(Ⅱ/Ⅲ) accelerated anode electrochemiluminescence of Ru/GO nanosheet for 8-OHdG immunoassay in cells - Ao Wang; Jia Zhong; Fei Zhang; Xinling Liu; Xulian Yang; Qinlan Yang; Na Chen; Li Yong; Yuxin Lou; Xu Liao; Li Mao (Analytica Chimica Acta, 2025)

Homologous nanocellulose modification: A “like cures like” strategy against coffee-ring and infiltration effects in paper-based colorimetric detection - Linan Sun; Yafei Lou; Siyu Chen; Hongyue Weng; Jiahao Li; Zhihui Lin; Junfei Tian; Rong Cao (Analytica Chimica Acta, 2025)

MsGal-2: a key regulator of gill microbiota and its contribution to mucosal immune function in juvenile largemouth bass (Micropterus salmoides) - Zhenzhen Yuan; Xiaocong Lou; Ying Ye; Haoyuan Li; Shun Yang; Mengmeng Huang; Hui Fei (Aquaculture International, 2025)

Quantifying tree-level peach flowering dynamics using UAV imagery and an optimized instance segmentation model - Qing Gu; Jiayu Cheng; Minghao Zhang; Xiongwei Li; Robert Jackson; Lei Ju; Weidong Lou; Miaojin Chen; Ji Zhou; Xiaobin Zhang (Computers and Electronics in Agriculture, 2025)

Multi-decadal dynamics of the Changjiang estuarine tidal flat resource: Causes and threats - Gang Liu; Yaying Lou; Jie Wang; Yulu Yang; Mingsi Li; Wen Wei (Ocean & Coastal Management, 2025)

Systematic assessment of landfill mining potential in Zhejiang Province, China: Resource recovery and economic potential - Zongao Zhen; Xianchao Xiang; Hao Zhang; Shi Feng; Jingyuan Sima; Fangfang Lou; Qunxing Huang; Mika Horttanainen; Xiaodong Li (Waste Management, 2025)

Experimental study on the crack propagation characteristics of drilled-slit and grouted rock samples based on CT three-dimensional scanning - Jianhua Fu; Xuelong Li; Hengjie Qin; Shuailin Wang; Shumin Liu; Zhiming Wang; Zeqi Wu; Zhen Lou (Process Safety and Environmental Protection, 2025)

Effect of geometry of active ignition with turbulent jet ignition on the flame propagation and combustion performance of methanol engine - Diming Lou; Xiaoxiao Zeng; Decheng Wang; Yunhua Zhang; Rui Dong; Yang Xu; Junzhe Li; Xuchong Li; Liang Fang; Yonghong Deng (Process Safety and Environmental Protection, 2025)

Discovery of the rare dimeric guaianes and their monomers from the Daphne penicillata Rehd - Tian-Ming Lv; Zhi‐Yuan Li; Li-Li Lou; Le Chen; Xiao‐Xiao Huang; Shao‐Jiang Song (Phytochemistry, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Early dry season changed the abundance and composition of soil antibiotic resistance genes in Dongting Lake wetland, China - Guxiang Xu; Yu Lou; Haipeng Wu; Juan Dai; Kenan Tian; Lean Zhou; Wenhao Li; Zeren Wang (Journal of Environmental Chemical Engineering, 2025)

Perfluorohexane sulfonate (PFHxS) induces liver cytotoxicity by activating autophagy and endoplasmic reticulum stress-regulated mitochondrial pathway apoptosis - Wenying Chen; Shuangchao Liu; Yao Zhou; Bin Liu; Wei Wang; Cheng Chen; Zaixiang Lou; Xiao Li Shen (Food and Chemical Toxicology, 2025)

Hepatopancreatic and intestinal inflammation is induced by lipopolysaccharide from Microcystis in common carp via the TLRs/NF-κB pathway - Yanzhe Yang; Zhaolu Gao; Mengya Lou; Junguo Ma; Xiaoyu Li (Fish & Shellfish Immunology, 2025)

Corncob-inspired synthesis of carbon fiber/PO43− intercalated NiFe-LDH hybrid for simultaneously improving flame retardancy and mechanical properties of epoxy resin composites - Yuanmeng Lou; Zhaotian Ba; Zhaodi Yuan; Jian Li; Cui Li; Lili Ma; Xiujuan Wang; Xin Wen; Pingan Song (Chemical Engineering Journal, 2025)

Imidazolium salt-functionalized Cu2O@SiO2 catalysts for integrated CO2 capture and electroreduction to multi-carbon products in acidic electrolytes - Hui Zhang; Shanshan Lou; Fan Yang; Keyi Fan; Zhengxin Gu; Wangbo Li; Yihe Chen; Yizhen Gan; Lushan Ma; Guoliang Wang; Hui Yang (Chemical Engineering Journal, 2025)

p-d orbital coupling and interfacial water regulation synergistically promote alkaline hydrogen electrocatalysis on Ru/VC heterostructures - Hao Hu; Nuo Sun; Jie Gao; Li Wang; Zhangrong Lou; Xuejing Cui; Jing Liu; Luhua Jiang (Chemical Engineering Journal, 2025)

Large electrocaloric temperature change in lead-free (Bi0.47Na0.47Ba0.06)TiO3-based ceramics via regulating non-ergodic - ergodic transition - Junwen Mei; Mei Bai; Yangfei Gao; Ruirui Kang; Xiangran Pei; Haichao Hu; Junjie Xiong; Jiantuo Zhao; Feng Li; Dezhen Xue; Zhongliang Lu; Xiaojie Lou (Chemical Engineering Journal, 2025)

Calycosin-7-O-β-D-glucoside modulates copper homeostasis through SLC31A1 to mitigate cuproptosis in cerebral ischemia/reperfusion injury - Qiaomei Lou; Li Yu; Siyu Liu; Chongyu Shao; Haitong Wan; Yu He (Chemico-Biological Interactions, 2025)

Thiosemicarbazone-Modified Polysilicate Flocculants for Copper Ion Removal - Jiatong Li; Lei Song; Hao Zhang; Runnan Wang; Bo Zhu; Dawei Lou (Water, Air, & Soil Pollution, 2025)

Inner Ear Organoid as a Preclinical Model of Hearing Regeneration: Progress and Applications - Yingjie Wang; Mengyu Chen; Yiyin Pan; Xianxia Li; Xiangxin Lou (Stem Cell Reviews and Reports, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

UAV state estimation based on mixture generalized minimum error entropy smooth variable structure filter - Yuzhao Jiao; Caoping Niu; Taishan Lou; Xuetao Li; Shuai Chang (Advances in Space Research, 2025)

Modifying polysaccharides to realized advanced function of novel food packaging materials - Hangyu Xie; Siting Li; Honghong Tian; Yi'er Lou; Yuanxin Ouyang; Min Wu; Xueping Song (Trends in Food Science & Technology, 2025)

A R2R3-MYB transcription factor LmMYB111 positively regulates chlorogenic acid and luteoloside biosynthesis in Lonicera macranthoides - Yanni Liu; Juan Lou; Guohua Liu; Qingqing Li; Zhengyan Cao; Peiyin Wu; Haoyang Mashu; Zhilin Liu; Jia Deng; Ziling Yang; Jiang Guo; Ning Tang; et al. (Plant Science, 2025)

Saleucanes A-J, structurally diverse neo-clerodane diterpenoids from Salvia leucantha with anti-neuroinflammatory activity via TLR4/MYD88/NF-κB pathway - Fen-Cong Pan; Han-Fei Liu; Xiao-Die Shu; Xiao-Qiao Yang; Hua-Yong Lou; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2025)

Treating PFOA emulsified oil in membrane distillation: Relationship between membrane fouling and surface properties - Weidong Gu; Jialong Wu; Mengmeng Lou; Jinjie Wang; Shuangshuang Jiang; Guanghui Li; Jun Li (Journal of Water Process Engineering, 2025)

Carbon footprint and environmental impact of reconstituted bamboo material based on life cycle assessment - Jingwen Chen; Yan Ma; Xiaomei Zhang; Nina Yan; Yanjun Li; Lei Xu; Zhichao Lou (Journal of Cleaner Production, 2025)

Synergistic inhibition of Maillard reaction hazards: Multifunctional hydrocolloids enable healthier air-fried beef patties with reduced heterocyclic amines and AGEs - Hongfei Du; Huang Zhang; Zixin Zhang; Zihan Yuan; Maiquan Li; Lei Zhou; Yan Liu; Aihua Lou; Mei Li; Ye Jiao; Qingwu Shen; Chaoyi Xue; et al. (Food Chemistry, 2025)

Control of Aspergillus flavus infection in grapes by antimicrobial protein from Bacillus tequilensis XZ4-1 - Yanjie Yi; Si Chen; Pengyuan Duan; Yu Lou; Guxiao Yang; Jiaoyang Liu; Rumeng Liu; Xuanhao Kuang; Wei Jiang; Ruifang Li (Food Bioscience, 2025)

Dual-photosensitizers photodynamic system for non-thermal inactivation of Shewanella putrefaciens and inhibition of microbial growth of refrigerated Litopenaeus vannamei - Dehua Wang; Yanzhe Lou; Xiaoming Jiang; Biqian Wei; Yong Xue; Zhaojie Li; Qingjuan Tang (Food Bioscience, 2025)

Oral administration of nanozyme-armed probiotic Escherichia coli Nissle 1917 with ROS scavenging for inflammatory bowel disease therapy - Tiantian Cui; Bing Li; Zhaoyang Lou; Kai Yang; Kaijin Yan; Danhong Ding; Hong Ge (Chemical Engineering Journal, 2025)

Solar-driven Janus fabric evaporator: Efficient desalination and selective lithium enrichment - Hong-Bei He; Yue Ma; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin; Hai-Tao Ren (Chemical Engineering Journal, 2025)

Highly hydrovoltaic fabrics based on water evaporation drive for self-powered wearable - Xiaoyang Zhang; Xuefei Zhang; Hai-Tao Ren; Ting-Ting Li; Ching-Wen Lou (Chemical Engineering Journal, 2025)

Engineering carbon-encapsulated iron selenide with tunable inner voids for highly reversible conversion-reaction anodes - Nadeem Hussain; Mehwish Kiran; Zongyan Gao; Zhu Zhu; Shijing Luo; Faxue Lu; Junjian Li; Xuechun Lou; Lina Zhou; Biqiong Chen; Zuofeng Chen; Tao Liu (Chemical Engineering Journal, 2025)

Dealuminated Beta zeolite-supported robust PtFe bimetallic catalysts for CO preferential oxidation in H2 - Jia Shen; Qian Xiang; Yake Lou; Jiajie Ye; Yanglong Guo; Wangcheng Zhan; Li Wang; Xiao-Ming Cao; Aiyong Wang; Xuan Tang; Yun Guo (Chemical Engineering Journal, 2025)

Improves the stability of containment leakage rate in constant pressure method by linear fitting analysis model - Li Jianfa; Chen Guangheng; Cong Jidong; Lou Taishan; Meng Zhaoming (Annals of Nuclear Energy, 2025)

Toad’s survivability and soil microbiome alterations impacted via individual abundance - Tian Zhang; Yang Liu; Junde Li; Mingjun Yuan; Chunhan Qiao; Xiao Huang; Xueyao Yang; Bo Gao; Chuan Lou; Yan Yang; Yu Cao (Biologia Futura, 2025)

Changes in the characteristics and risks of bioaerosols in school hospital before and after the COVID-19 epidemic - Yanjie Wang; Yifan Liu; Changfu Hao; Yan Li; Yang Liu; Haoran Zhu; Bisheng Lai; Hao Dong; Fengguang Chai; Hao Lou; Qing Hong (Air Quality, Atmosphere & Health, 2025)

Structurally diverse oxygen-containing aromatic compounds with anti-inflammatory activity from Aspergillus sp. LY-1-2 - Chu-Qiao Wang; Jinzhi Pan; Shuang-Zhi Yuan; Chao Yuan; Fei-Xiang Ji; Dan Feng; Xiao-Ping Peng; Qian Luo; Hong-Xiang Lou; Gang Li (Natural Product Research, 2025)

A new illudane sesquiterpene from the edible fungus Pholiota nameko - Lian Yang; Huan Zhang; Shu-Hang He; Ju Xu; Xiao-Long Li; Fei-Xing Li; Dong-Mei Lin; Deng-Ji Lou; Xiao-Yan Yang (Natural Product Research, 2025)

Nested MPI-CWRF dynamical downscaling and future projections of summer extreme precipitation changes in China - Huan Li; Fengxue Qiao; Nan Wei; Haoran Xu; Rui Wang; Fulin Jiang; Guimin Lou; Jia Zhao; Qingyu Yang (Frontiers of Earth Science, 2025)

Molecular hybridization of indoles and vanillins via α-hydroxyketone linking for discovering new inhibitor of PVY intercellular traffic - Feifei Chen; Jiao Li; Fenyan Wang; Ningning Zan; Mingshu Lou; Chunni Zhao; Baoan Song; Runjiang Song (Pesticide Biochemistry and Physiology, 2025)

Diterpenoids from Marmoritis complanata and their anti-inflammatory activity in zebrafish - Ruifeng Liu; Yongjie Wang; Xiaobin Li; Chengmin Zhang; Peilin Wu; Xiyue Wang; Hongxiang Lou; Jiaozhen Zhang (Phytochemistry, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Per- and polyfluoroalkyl substances mixture impairs intestinal barrier function through microbiota-derived 21-deoxycortisol and cortisol metabolism dysregulation - Tingting Lin; Luyang He; Sishuo Liu; Yahui Li; Zhi Huang; Delei Cai; Yiming Wang; Zhe Mo; Yi Zhu; Zhijian Chen; Peiwei Xu; Xiaoming Lou; et al. (Journal of Hazardous Materials, 2025)

Shift from physico-chemical properties to micro-organisms in driving phosphorus dynamics in paddy-maize transition system under long-term biochar addition - Zhijie Dong; Kaixiong Xing; Yilai Lou; Hongbo Li; Aiping Zhang (Journal of Environmental Management, 2025)

Comprehensive evaluation of sulfur content and curing duration effects on the rheological performance of sulfur-extended bitumen - Ke Shi; Feng Ma; Zhen Fu; Baowen Lou; Diego Maria Barbieri; Jiarong Li; Ruimeng Song; Dongdong Yuan (Fuel, 2025)

Corrigendum to “Synergistic effects of polymethoxyflavonoids from citrus peel extracts on harmful compound formation and flavor quality in grilled beef patties” [Food Chemistry 481 (2025) 1–11 144089] - Zhuoming Huang; Yang Xu; Ming Jin; Zixin Jiang; Lan Mo; Maiquan Li; Aihua Lou; Yan Liu; Chaoyi Xue; Jie Luo; Qingwu Shen; Shuai Wang; et al. (Food Chemistry, 2025)

Nano-selenium alleviates tetrabromobisphenol A induced PANoptosis in carp gill tissue by inhibiting TLR4/MyD88/NF-κB pathway - Shuang Lou; Huijie Chen; Mingyue Li; Shize Wang; Yuting Dong; Xinrui Deng; Shu Li (Fish & Shellfish Immunology, 2025)

Three-dimensional deformation inversion of mountain excavation and city construction areas using multi-track Sentinel-1 datasets and constraints of strain model and surface-parallel flow - Guangrong Li; Chaoying Zhao; Jiuyuan Li; Qin Zhang; Liquan Chen; Xiaojie Liu; Ming Yan; Jianqi Lou; Baohang Wang (Engineering Geology, 2025)

Three-dimensional deformation inversion of pre-sliding Baige landslide by multiple adaptive SAR offset tracking method - Ming Yan; Chaoying Zhao; Bin Li; Guangrong Li; Jianqi Lou; Xiaojie Liu (Landslides, 2025)
The Baige landslide, located on the west bank of the Jinsha River, in the Tibet Autonomous Region, China occurred on October 11 and November 3, 2018, which resulted in a blockage of the river, posing a significant threat to the safety of life and property of the people living downstream. Therefore, it is of importance to invert the high-precision, high spatiotemporal resolution three-dimensional pre-sliding deformation to analyze its developing process and reveal the precursory signal for the early warning the potential risks. Synthetic aperture radar (SAR) offset tracking was employed with adaptive window sizes to calculate the deformations prior to the landslide event from different tracks, including ascending and descending Sentinel- 1 A tracks, and ascending ALOS/PALSAR- 2 track. The three-dimensional deformation time series was inverted from two dimensional ones from three tracks. The results show that the Baige landslide moved continuously eastward, experiencing an initial acceleration, followed by deceleration; and it moved southward with continuously acceleration, even more pronounced when it approached the sliding time. Meanwhile, it moved vertically downward, with continuously increasing deformation rates. Then, the shear and dilation strains are inverted based on three-dimensional deformation time series. The results show that they were reversed on both edges of the landslide and increased over time, with dilation strains being larger than shear strains. Lastly, the thickness and volume of the landslide estimated through three-dimensional deformation are consistent at the order of magnitude with the digital elevation model (DEM) difference, which indicates that SAR deformation technique can provide key parameters for landslide analysis and assessment with high efficiency.

Deep Learning in Gravity Research: A Review - Qingkui Meng; Lianghui Guo; Shuai Zhang; Hanyu Lou; Rui Li (Journal of Earth Science, 2025)

Real-Time Prediction and Control of NOx Emissions in Heavy-Duty Diesel Vehicles Using OBD Data and Deep Learning Models - Tao Li; Xin Lou; Baoli Gong; Guoquan Xie; Kui Wang; Honghao Zhang; Yong Peng (Emission Control Science and Technology, 2025)

Contributions of urbanization and population growth to changes in urban flood exposure in recent decades - Ziyi Tang; Pin Wang; Yao Li; Chaohui Chen; Yihan Lou; Tangao Hu (Sustainable Cities and Society, 2025)

APPLE-MASNUM: Accelerating parallel processing for lightweight expansion of MASNUM on a single multi-GPU node - Qi Lou; Changmao Wu; Changming Dong; Xingru Feng; Yuanyuan Xia; Li Liu; Zhengwei Xu; Xu Gao; Meng Sun; Xunqiang Yin (Ocean Modelling, 2025)

Infection with infectious precocious virus (IPV) suppresses infection with decapod iridescent virus 1 (DIV1) in Macrobrachium rosenbergii - Haoyu Lou; Guohao Wang; Xuan Li; Chengyan Zhou; Xiaomeng Guo; Liying Wang; Qiongying Tang; Guoliang Yang; Xuan Dong; Jie Huang (Journal of Invertebrate Pathology, 2025)

Changes in the hydrological processes of glacial lake-fed rivers on the Tibetan Plateau due to climate change - Shengtian Yang; Jiyi Gong; Hezhen Lou; Tongliang Gong; Baichi Zhou; Zihao Pan; Huaixing Wang; Yulian Wang; Jiekang Li; Yunmeng Dai (Journal of Environmental Management, 2025)

Concurrent alien plant invasion and biodiversity loss enhance soil microbial carbon use efficiency by shifting the balance between microbial carbon and nitrogen acquisition - Abdulkareem Raheem; Babar Iqbal; Yanjiao Wang; Jiabao Lou; Yi Tang; Jian Li; Qiuyue Zhang; Sixuan Xu; Zhicong Dai; Xiaojun Zheng; Guangqian Ren; Guanlin Li; et al. (Journal of Environmental Management, 2025)

Potentially toxic elements in sediments of China's Shihe River: Urban-agricultural impact assessment and source apportionment - Kai Zhang; Ge Ma; Zheng Chen; Jilu Wang; Xiaomeng Lou; Yinan Yang; Jiaojiao Feng; Fengxia Yang; Kuangjia Li; Chenxuan Shang; Rui Xin; Xiangmin Zhang (Journal of Contaminant Hydrology, 2025)

Synergistic effects of polymethoxyflavonoids from citrus peel extracts on harmful compound formation and flavor quality in grilled beef patties - Zhuoming Huang; Yang Xu; Ming Jin; Zixin Jiang; Lan Mo; Maiquan Li; Aihua Lou; Yan Liu; Chaoyi Xue; Jie Luo; Qingwu Shen; Shuai Wang; et al. (Food Chemistry, 2025)

Spoilage mechanism and preservation technologies on the quality of salmon: An overview - Yongfa Cheng; Yongyong Li; Huicheng Yang; Liqing Wu; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Food Bioscience, 2025)

Lipoprotein-mimicking nanodiscs for precise glioblastoma therapy and immune microenvironment modulation - Taiyu Liu; Lisha Liu; Dandan Gao; Wenqing Li; Xianggui Wu; Shuo Li; Beiyuan Zhang; Yaohua Liu; Qiao Shan; Meiqing Lou; Lifang Yin; Yunke Bi (Chemical Engineering Journal, 2025)

Genomic analysis of the novel Stenotrophomonas phage vB_Srh_LBjhp91a, isolated from a Karst cave in China - Lou Ren; Zheng Fang; Shixia Li; Qingshan Wu; Lan Xiang; Chuangen Lin; Qiuping Liu; Leitao Tan; Qingbei Weng (Archives of Virology, 2025)

A TaqMan probe-based RT-qPCR for the detection of brine shrimp reovirus 1 - Xuan Li; Guohao Wang; Haoyu Lou; Chengyan Zhou; Xiangmin Meng; Xinping Wang; Xuan Dong (Aquaculture, 2025)

Remediation of microplastics-contaminated agricultural soils by unmodified and modified biochar derived from Solidago canadensis L. - Babar Iqbal; Muhammad Junaid Nazir; Jiabao Lou; Yanjiao Wang; Eun Hea Jho; Mao Ye; Mingming Sun; Abdulkareem Raheem; Inamullah; Muhammad Sohail Memon; Guanlin Li; Xin Zhao; et al. (Process Safety and Environmental Protection, 2025)

Understanding citrus aroma: Changes induced by postharvest treatments of fresh fruit - Shuxun Liu; Yuling Cai; Ying Lou; Yan Zhao; Mingfeng Cao; Ping Li; Qing Gu (Postharvest Biology and Technology, 2025)

Jasmonic acid signaling pathway is involved in agaro-oligosaccharides-induced disease resistance of peach fruit through PpMYC2-activated transcription of PpPGIP1 - Qian Li; Yingying Wei; Shu Jiang; Jianfen Ye; Yi Chen; Feng Xu; Yongjiang Lou; Phebe Ding; Xingfeng Shao (Postharvest Biology and Technology, 2025)

Mechanism of quartz flotation separation from gypsum using tetradecyl trimethyl ammonium chloride: Guiding the improvement of phosphogypsum quality - Haodong Shi; Liuyi Ren; Shenxu Bao; Yimin Zhang; Anh V. Nguyen; Bo Chen; Weifeng Li; Rui Huang; Yanqi Zeng; Sidi Lou (Minerals Engineering, 2025)

Formation of Sb2S3 photocatalyst during antimony removal from mine drainage by Shewanella sp. ANA-3 - Jinna Lu; Xiaohui Wu; Kaixiong Yang; Qiuyun Lou; Kun Xu; Li Ye (Journal of Water Process Engineering, 2025)

Rapid penetrating inactivation and disinfection through ice layers by light-condensed deep ultraviolet LED irradiation - Lucheng Yu; Peng Shen; Zefeng Lin; Shini Yang; Maowei Yang; Yaxiao Lou; Shiqiang Lu; Feiya Xu; Shengrong Huang; Xueqiong Sun; Jiamin He; Huachun Wang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Performance of ethanol transformable microemulsions and remediation of salinized oil – contaminated soils - Xiaoning Feng; Nan Shi; Shuhai Guo; Bo Wu; Gang Li; Bin Lou; Xiujie Yang; Yifan Wang; Ping Xiang; Xiahong He; Dong Liu (Journal of Hazardous Materials, 2025)

Characteristics and mechanism of paclobutrazol degradation by the novel bacterial strain Kurthia gibsonii CGMCC 32305 - Wenxin Zhang; Meiling Shi; Yue Lou; Xinyi Liu; Xiaoli Dai; Yang Liu; Zhaoyu Li; Xu Su; Jiajia Li; YongQiang Tian (Journal of Environmental Chemical Engineering, 2025)

Green and efficient conversion of polypropylene wastes into Ni@CNTs hybrids and their application for fire resistant polycarbonate composites - Junlin Zhu; Zhaotian Ba; Yuanmeng Lou; Cui Li; Lili Ma; Jie Liu; Xin Wen; Tao Tang (Journal of Environmental Chemical Engineering, 2025)

Biodegradable food packaging films: Material source, mechanical and water vapor barrier properties, and improvement strategies—A comprehensive review - Beibei He; Yongfang Gao; Wenjing Lou; Jingru Wang; Shitian Xin; Keshi Ma; Lili Li (Food Research International, 2025)

Effect of thermostatic freezing on physicochemical indexes and metabolism of shrimp (Solenocera melantho) - Yongfa Cheng; Xinling Liu; Juan Shi; Shiqian Fu; Huicheng Yang; Liqing Wu; Yongjiang Lou; Yongyong Li (Food Bioscience, 2025)

Hypoxia-induced mitochondrial dysfunction and mitophagy in the small yellow croaker (Larimichthys polyactis) - Lu Deng; Jingqian Wang; Yang Liu; Li Wang; Feng Liu; Bao Lou; Junquan Zhu (Fish & Shellfish Immunology, 2025)

Pathogenic bacteria and antibiotic resistance genes in hospital indoor bioaerosols: pollution characteristics, interrelation analysis, and inhalation risk assessment - Yang Liu; Yanjie Wang; Changfu Hao; Yan Li; Hao Lou; Qing Hong; Hao Dong; Haoran Zhu; Bisheng Lai; Yifan Liu; Jinlong Li (Environmental Pollution, 2025)

Efficient valorization of textile white mud to MIL-101(Fe) with abundant coordinatively unsaturated centers for enhanced fenton-like catalysis - Shuaibing Ren; Xiaofei Wen; Ting Lu; Huiyan Zhang; Zimo Lou; Xinhua Xu; Jiansheng Li; Jianming Yu (Chemical Engineering Journal, 2025)

Preparation of temperature-dependent flux controllable cellulose nanofiber-based films and their application in oil-water separation - Feiyun Li; Jinxian Shan; Helin Li; Hongming Lou; Yanjun Tang (Carbohydrate Polymers, 2025)

Mechanical performances of the pipe-liner structure under void conditions - Kangjian Yang; Jianwei Zhang; Hongyuan Fang; Shaochun Ma; Lei Shi; Bin Li; Yizhuang Lou; Kuoyu Yang; Kejie Zhai (Tunnelling and Underground Space Technology, 2025)

Integration of Bi in Fe, N co-doped carbon-encapsulated iron carbide nanoparticles for boosting oxygen reduction reaction - Jing Liu; Lang Xiao; Shankui Luan; Shengchang Li; Shuo Li; Zhangrong Lou; Xuejing Cui; Luhua Jiang (Fuel, 2025)

Vine tea (Ampelopsis grossedentata) ameliorates chronic alcohol-induced hepatic steatosis, oxidative stress, and inflammation via YTHDF2/PGC-1α/SIRT3 axis - Qihan Luo; Jiang Qiu; Minxia Chen; Na Yang; Xinyue Li; Shuo Huang; Qing Ma; Zongyuan Li; Dayong Lou; Yu Du; Li Chen; Qing Shen; et al. (Food Research International, 2025)

Oxidative stress induced by combined glyphosate and TBBPA exposure promotes gill autophagy and inflammation via the PI3K/AKT/mTOR pathway - Mingyue Li; Shuang Lou; Kai Chen; Yuting Dong; Shize Wang; Tingting Yu; Xinrui Deng; Shu Li (Fish & Shellfish Immunology, 2025)

Unveiling the functional heterogeneity of endogenous tissue extracellular vesicles in skeletal muscle through multi-omics - Yizhuo Wang; Peng Lou; Xiyue Zhou; Yijing Xie; Yimeng Zhang; Shuyun Liu; Lan Li; Yanrong Lu; Meihua Wan; Jingqiu Cheng; Jingping Liu (Chemical Engineering Journal, 2025)

Experimental study on the coupling motion mechanism of boulders in debris flow - Fei Wang; Jiading Wang; Xiaoqing Chen; Haijun Qiu; Canyun Lou; Yun Li (Landslides, 2025)

Anti-ferroptosis effects of undescribed abietane diterpenoids from Prunella vulgaris subsp . hispida (Benth.) Hultén - Heng-Li Yan; Xiao-Qiao Yang; Han-Fei Liu; Fen-Cong Pan; Jin-Yu Li; Wei-Dong Pan; Ni Zhang; Hua-Yong Lou; Chao Sun (Natural Product Research, 2025)

Exosomes secreted from M2-polarized macrophages inhibit osteoclast differentiation via CYLD - Zi-yan Guo; Nan-nan Yin; Xiao-fei Li; Meng-meng Wang; Xiao-na Sui; Cai-di Jiang; Ming-hua Xu; Xiao-e Jia; Chong-jian Fu; Tie-lou Chen; Xin Liu (Tissue and Cell, 2025)

Spatiotemporal estimates of anthropogenic NOx emissions across China during 2015–2022 using a deep learning model - Yuxin Lou; Yubao Chen; Xi Chen; Rui Li (Journal of Hazardous Materials, 2025)

Risk assessment of potentially toxic elements, microplastics, and microorganisms in groundwater around municipal solid waste landfill - Xueya Li; Tianmu Peng; Linyi Lin; Muhammad Amjad Khan; Shurui Zhang; Meijuan Kuang; Jinming Lou; Jiaxin He; Pangxiang Zhang; Xiaomao Song; Xu Wang; Qing Huang (Journal of Hazardous Materials, 2025)

Spatiotemporal analysis of wildfires in Alberta, Canada over the past sixty years: Increased wildfire frequency by human activities - Wenrui Li; Yuqi Bai; Ziyi Chen; Shuhan Lou; Yuanhong Liao (Journal of Environmental Management, 2025)

Stacking paper sheets into multi-purpose quick response sensing code with built-in nitrocellulose-membrane-free lateral flow assay for detecting tetracycline in food samples - Rong Cao; Yafei Lou; Zhiyuan Yang; Linan Sun; Azadeh Nilghaz; Miaosi Li; Junfei Tian (Food Chemistry, 2025)

Regulatory effects of Lacticaseibacillus rhamnosus ZFM216 and its bacteriocin on intestinal microbiota in vitro - Qingqing Zhou; Yeqing Lou; Chenjie Shan; Zhongdu Ye; Danli Wu; Ping Li; Eefjan Breukink; Qing Gu (Food Bioscience, 2025)

Review of designing anti-surfactant wetting Janus membranes for membrane distillation: Mechanisms, methods and challenges - Mengmeng Lou; Lijun Meng; Jun Li; Fang Li (Desalination, 2025)

Defect-rich FeCoNiMnRu high-entropy alloys with activated interfacial water for boosting alkaline water/seawater hydrogen evolution - Guangbo Liu; Chen Song; Xiaolei Li; Qisen Jia; Pengfei Wu; Zhihao Lou; Yuanshuo Ma; Xuejing Cui; Xin Zhou; Luhua Jiang (Chemical Engineering Journal, 2025)

Peppermint Essential Oil For Controlling Aspergillus flavus and Analysis of its Antifungal Action Mode - Yanjie Yi; Rumeng Liu; Zijun Shang; Kai Wang; Changfu Zhang; Zihao Wang; Yu Lou; Jiaoyang Liu; Peng Li (Current Microbiology, 2025)

BDS-3 PPP ambiguity resolved percentage analyses under geomagnetic storms in solar cycle 25 - Zhuang Chen; Xiaomin Luo; Yanxiong Liu; Yujie Li; Xiaolong Wan; Yidong Lou (Advances in Space Research, 2025)

Advancing predictive, preventive, and personalized medicine in eyelid diseases: a concerns-based and expandable screening system through structural dissection - Jing Cao; Kun You; Peifang Xu; Yiming Sun; Ji Shao; Yifan Zhou; Huimin Li; Lixia Lou; Qi Miao; Juan Ye (EPMA Journal, 2025)
Background/aims Early recognition of eyelid morphological abnormalities was crucial, as untreated conditions could lead to blinding complications. An eyelid screening system that could provide both anatomical and pathological information was essential for formulating personalized treatment strategies. This study aimed to develop a clinically concerns-based framework capable of identifying common eyelid diseases requiring further intervention by evaluating individual anatomical and pathological changes. This approach would enhance individualized and efficient prevention, while supporting targeted treatment strategies. Methods The eyelid disorder screening system, Eyetome, was developed based on a morphological atlas and comprised four modules designed to identify 14 common eyelid disorders and pathological changes. A total of 6180 eye patches were analyzed to extract anatomical and pathological features. The performance of Eyetome was evaluated using average accuracy (aACC) and F1 score, with comparisons made against traditional models and ophthalmologists. To assess the system’s expandability, an additional test was conducted in a multimorbidity scenario. Results Eyetome demonstrated high performance in recognizing single diseases, achieving an aACC of 98.83% and an F1 score of 0.93. The system outperformed classic models, with an aACC of 98.83% compared to 96.72% for Desnet101 and 97.59% for Vit. Additionally, Eyetome’s aACC exceeded that of a junior ophthalmologist (JO) (97.11%) and was comparable to a senior ophthalmologist (SO) (98.69%). In the extended multimorbidity dataset, Eyetome maintained robust performance with an accuracy of 97.97%, surpassing JO (95.47%) and closely matching SO (97.81%). Conclusions This study developed a clinical concerns-based system for screening and monitoring eyelid disorders, aimed at supporting predictive diagnosis, preventing diseases progression, and facilitating more effective, patient-centered treatment of common eyelid disorders, aligning with the principles of predictive, preventive, and personalized medicine (PPPM/3PM). The system’s interpretability, scalability, and user-friendly data acquisition design could further enhance its acceptance among both doctors and patients, facilitating the shift from reactive medicine to proactive precision medicine.

Design and parameter optimization of air-delivery auxiliary seed guide for pneumatic plate precision rapeseed metering device - Zhaodong Li; Heng Zhang; Jialuo Huang; Chao Lou; Yongxin Chen; Lichao Liu; Tian Zhang; Liqing Chen (Computers and Electronics in Agriculture, 2025)

Metabolic responses of small yellow croaker (Larimichthys polyactis) liver to hypoxic stress: Insights into glucose and lipid metabolism - Li Wang; Jingqian Wang; Yang Liu; Feng Liu; Bao Lou; Yiner Chen; Junquan Zhu (Aquaculture, 2025)

Stress-responsive plasma membrane H+-ATPases regulate deep rooting in rice - Di Wang; Kai Xu; Shoujun Chen; Lei Wang; Qiaojun Lou; Changsen Zhong; Yawen Wang; Tiemei Li; Huaxiang Cheng; Lijun Luo; Liang Chen (Plant Science, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Dynamic collision avoidance for maritime autonomous surface ships based on deep Q-network with velocity obstacle method - Yuqin Li; Defeng Wu; Hongdong Wang; Jiankun Lou (Ocean Engineering, 2025)

Quantification of inhaled cigarette smoke movement and deposition in human nasal airways - Yusheng Wang; Feilun Yang; Chaofan Li; Ruiping Ma; Zehui Li; Xiaole Chen; Shaokoon Cheng; Minjie Gong; Miao Lou; Zhenzhen Hu; Hongxian Ren; Yanxia Bai; et al. (Journal of Aerosol Science, 2025)

Impact of polyethylene terephthalate microfibers on histopathological and molecular responses induced by cadmium in the polychaete Perinereis aibuhitensis - Yi Cong; Yisong Jiang; Mingxing Zhang; Shuo Cao; Qi Li; Zhaochuan Li; Fei Jin; Yadi Lou; Ying Wang; Huahong Shi; Juying Wang (Environmental Pollution, 2025)

Novel 3D FRP systems used for casting and reinforcing low-carbon concrete elements - Wei Sun; Qinglin Guo; Wangzhou Xu; Tiejiong Lou; Haifeng Li (Engineering Structures, 2025)

Evaluating the effects of meteorology and emission changes on ozone in different regions over China based on machine learning - Boya Liu; Yuanyuan Li; Lili Wang; Lei Zhang; Fengxue Qiao; Peifan Nan; Dan Ji; Bo Hu; Zheng Xia; Zhengang Lou (Atmospheric Pollution Research, 2025)

Isolation and characterization of the novel Vibrio parahaemolyticus phage vB_VpaM_PVP-XSN - Tianpeng Qi; Sunjian Lyu; Meiwen Xia; Bao Lou; Li Liu; Haisheng Xu (Archives of Virology, 2025)

Assessment of atmospheric correction methods in MSI imagery for deriving bathymetry and substrates of shallow-water coral reefs - Wei Huang; Jun Zhao; Mingjie Li; Quansheng Lou; Nanyang Yan; Shaojie Sun (Frontiers in Marine Science, 2025)
Accurate atmospheric correction (AC) is a crucial procedure for monitoring coral reef habitat in shallow waters via remote sensing techniques. In this study, three commonly used AC processors—Dark Spectrum Fitting (DSF), Case 2 Regional Coast Color processor (C2RCC), and Polymer—were applied to evaluate their performance on Sentinel-2 MSI imagery of coral reef areas in the Xisha Islands, South China Sea. Since the latter two processors incorporate a sunglint removal approach, additional procedures were applied to DSF. These include short-wave infrared band Glint Correction (GC), DeGlint (DG), and near-infrared band intercept (DG865) algorithms to enhance glint correction after the DSF processor. The results demonstrate that Polymer outperforms the DSF method (either standalone or with glint corrections) and C2RCC. Polymer-derived remote sensing reflectance showed excellent agreement with in situ measurements, with R 2 > 0.95 in 3-hour matches and R 2 > 0.65 in 6-hour matches in visible bands (443nm-665nm). It effectively removed most of the glint contamination in the NIR bands (740nm,783nm), while revealing contributions from bottom reflections. Under various image conditions, Polymer consistently delivered the highest bathymetry accuracy (R 2 : 0.51 - 0.85) and the most stable substrate classifications. This study underscores the critical role of accurate AC in retrieving bathymetry and coral reef substrate information from optically shallow waters using medium- to high-resolution MSI imagery. Polymer proves to be a robust tool for precise remote sensing of coral reefs, offering superior performance even in challenging conditions.

Efficient weed segmentation in maize fields: A semi-supervised approach for precision weed management with reduced annotation overhead - Zhiming Guo; Yi Xue; Chuan Wang; Yuhang Geng; Ruoyu Lu; Hailong Li; Deng Sun; Zhaoxia Lou; Tianbao Chen; Jianzhe Shi; Longzhe Quan (Computers and Electronics in Agriculture, 2025)

Evaluation of protective efficacy of Pseudomonas plecoglossicida ΔdeoR as an attenuated vaccine against virulent challenge in large yellow croaker (Larimichthys crocea) - Pan Qin; Xingfu Chen; Jinmei Yang; Xin Li; Tong Wu; Jingsong Yang; Bilian Lou; Liangyin He; Youshen Li; Xinhua Chen (Aquaculture, 2025)

Potential of a novel marine microalgae Dunaliella sp. MASCC-0014 as feed supplements for sustainable aquaculture - Xueer Wen; Jiali Chen; Chenglong Liu; Xinran Zhuo; Ying Luo; Yongxuan Li; Danqiong Huang; Huachang Zhu; Zhangli Hu; Sulin Lou; Hui Li (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Distribution characteristics of Hg and As in the water-SPM system in the Xiaoqing river estuary and coastal - Feifei Zhang; Dong Zhang; Xiaoyue Li; Huawei Lou; Hongrui Fu; Xiaojun Sun; Peiyan Sun; Xinping Wang; Mutai Bao (Marine Environmental Research, 2025)

Water-rock interaction-induced degradation of Jinping marble in in-situ environments: A multi-scale analysis of mechanical behavior - Chendi Lou; Ru Zhang; Zetian Zhang; Li Ren; Jing Xie; Kun Xiao; Mingchuan Li; Jifang Zhou; Anlin Zhang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Enhanced catalytic activity and CO2 tolerance of La0.6Sr0.4Co0.2Fe0.8O3- cathode for solid oxide fuel cells via incorporation of Ce0.8Pr0.2O1.9 nanosheets - Hao Lou; Baixi Xia; Chuangang Yao; Haixia Zhang; Zhe Zhang; Yuxi Sun; Jingyi Ding; Li Zhang; Xiaoshi Lang; Kedi Cai (Fuel, 2025)

Antibacterial activity of zinc oxide nanoparticles against Shewanella putrefaciens and its application in preservation of large yellow croaker (Pseudosciaena crocea) - Mengqing Liu; Yuhan Mo; Zheyun Dong; Huicheng Yang; Bangchu Lin; Yongyong Li; Yongjiang Lou; Shiqian Fu (Food Research International, 2025)

Augmenting antioxidative capacity of myosin and cytoprotective potential of myosin digestion products through the integration of crocin and crocetin: A comprehensive analysis via quantum chemical computing and molecular dynamics - Chaoyi Xue; Jian Zhang; Chenxia Zhang; Zhonghao Hu; Huixue Liu; Lan Mo; Maiquan Li; Aihua Lou; Qingwu Shen; Jie Luo; Shuai Wang; Wei Quan (Food Chemistry, 2025)

Lipidomics reveals relationship between lipid changes and the development of volatile flavor compounds in Chinese bacon during cyclic temperature smoking - Ziyi Hu; Zhaoxia Qu; Enqi He; Huiyu Zou; Zixin Li; Lei Zhou; Aihua Lou; Yan Liu; Haohua Fu; Jie Luo; Wei Quan; Qingwu Shen (Food Bioscience, 2025)

The influence of carbon dioxide on fermentation products, microbial community, and functional gene in food waste fermentation with uncontrol pH - Xin-Rong Pan; Pei-Ken Shang-Guan; Shu-Hui Li; Chu-Hao Zhang; Jia-Min Lou; Liang Guo; Lu Liu; Yin Lu (Environmental Research, 2025)

Height development trends among 7–18-year-old school-age children in central plains of China between 2000 and 2019: A serial cross-sectional surveillance study in China - Fanke Zhou; Lifan Ding; Yuxi Li; Jiajia Hu; Junna Zhang; Yixiao Geng; Xiaolei Ban; Wencan Wu; Xiaomin Lou; Xian Wang (Economics & Human Biology, 2025)

Bismuth Boosts the Preferential oxidation of CO over Pt/Al2O3 by Regulating the Reactant adsorption and reaction route - Yake Lou; Qianqiu Wu; Jia Shen; Núria J. Divins; Jordi Llorca; Yanglong Guo; Wangcheng Zhan; Aiyong Wang; Li Wang; Yun Guo (Chemical Engineering Journal, 2025)

Triboelectric Nanogenerator based on superstructure MoS2 for energy harvesting and human sensing - Hao Zhao; Jia-Horng Lin; Hai-Tao Ren; Hao-kai Peng; Ching-Wen Lou; Ting-Ting Li (Chemical Engineering Journal, 2025)

Construction of novel blue-lighting emitters via stepwise locking-ring strategy in multi-aryl modified imidazole-based heterocyclic framework - Yu Huang; Jingli Lou; Baoxi Li; Han Zhang; Yichao Chen; Xin He; Xianfeng Qiao; Ben Zhong Tang; Zhiming Wang (Chemical Engineering Journal, 2025)

Aristolochic acid I abnormally activates the wnt7b/β-catenin signaling pathway and affects the repair of renal tubules - Xiaofen Li; Ying Zhang; Ailin Lan; Maojuan Li; Ming Xia; Chuanhua Huang; Didong Lou (Chemico-Biological Interactions, 2025)

A comparison of perceived social equity associated with different governance types of protected areas - Yin Zhang; Ying Lou; Yuqi Zhang; Meili Chen; Shengzhi Li; Dan Brockington (Biological Conservation, 2025)

Clinical evaluation of a highly multiplexed CRISPR-based diagnostic assay for diagnosing lower respiratory tract infection: a prospective cohort study - Hui Lou; Xiaojia Wang; Qiuting Jiang; Xi Li; Yake Yao; Qi Chen; Linxing Chen; Shanshan Zhang; Yunsong Yu; Chao Liu; Hua Zhou (Infectious Diseases, 2025)

Transpiration and water use strategies of three economic tree species in a semi-arid afforestation region - Wenjie Wu; Yue Li; Kiril Manevski; Mathias Neumann Andersen; Bingcheng Si; Yongcai Lou; Hao Feng; Kadambot H. M. Siddique (European Journal of Forest Research, 2025)

Lab on a single microbead: An enzyme-free strategy for the sensitive detection of microRNA via efficient localized catalytic hairpin assembly - Yan Qi; Jiangtao Yu; Ming Lou; Yameng Yu; Ruohan Li; Zhenhao Zhang; Yuxuan Dai; Kejing Lao; Meng Cao; Xingchun Gou (Analytica Chimica Acta, 2025)

A Novel High-Conjugated Probe of 4-(Acridone-10-yl)-Phenylethyl Chloroformate (APE-Cl) for Rapid Detection of Amino Compounds Using HPLC with Fluorescence Detection - Yingying Lou; Huiquan Xiao; Xiaocong Zou; Zenghui Xu; Zhiwei Sun; Zan Li; Zhongyin Ji; Jinmao You (Journal of Fluorescence, 2025)

Cadmium translocation combined with metabolomics analysis revealed potential mechanisms of MT@MSN-CS and GSH@MSN-CS in reducing cadmium accumulation in rice (Oryza sativa L.) grains - Wen-Ze Fang; Jun-Qiao Chen; Jing-Dong Mao; Bao-Feng Zhang; Li-Ping Lou; Qi Lin (Environmental Science and Pollution Research, 2025)

A new anthraquinone derivative from the marine fish-derived fungus Alternaria sp. X112 - Xiaoyuan Xu; Gang Li; Rao Fu; Hongxiang Lou; Xiaoping Peng (Natural Product Research, 2025)

Seismic demand-oriented design of hybrid base-isolated building with the tuned inerter eddy current damper - Dawei Li; He Bai; Yu Lou; Jianping Han (Soil Dynamics and Earthquake Engineering, 2025)

Facile fabrication of porous fluorinated polyurethane membranes for organic solvent adsorption based on thiol-ene click reaction within high internal phase emulsions - Aili Wang; Yuyang Liu; Yanping Yu; Minxin Song; Jinyue Li; Yutong Wang; Caiyang Zhang; Nan Lou; Fang Qi; Xueyi Han (Process Safety and Environmental Protection, 2025)

Corrigendum to “Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway” [Phytochemistry 225 (2024) 114192]> - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Co-governance of iron speciation and carbon phase on Fenton-like reaction triggered by Fe-enriched industrial sludge derived biochar - Wenjia Wei; Xiaofei Wen; Shengkun Zhang; Lvren Lin; Jinmei Zhu; Jianming Yu; Jiansheng Li; Zimo Lou; Xinhua Xu (Journal of Cleaner Production, 2025)

Exposure to titanium dioxide nanoparticles disrupts the BTB by interfering with the assembly of stress granules in germ cells - Lingjuan wang; Yantao Lou; Bin Li (Journal of Environmental Management, 2025)

Constructing of ultrahigh pH-responsive polycarboxylic copolymers for enhanced recycling cellulase from enzymatic hydrolyzate of corncob resides - Huinan Liang; Feiyun Li; Hongming Lou; Yanjun Tang (Fuel, 2025)

Quantitative estimation of three-dimensional fracture density: Insights from the stereological relationship between borehole and universal elliptical DFN - Kun Xiao; Ru Zhang; Li Ren; Anlin Zhang; Jing Xie; Ziwen Luo; Zetian Zhang; Chendi Lou; Zeqian Yang (Engineering Geology, 2025)

Harvesting sustainable and low-hysteresis anion redox chemistry in Na layered oxide cathodes through mild ligand-to-metal charge transfer - Chunjing Hu; Xiaobing Lou; Xiang Wu; Fushan Geng; Bingwen Hu; Chao Li (Chemical Engineering Journal, 2025)

High power density of flexible thermoelectric generator with low thermal resistance model based on body heat harvesting - Nianling Kuang; Yimeng Kang; Benyi Lou; Pan Sheng; Peng Li; Binbin Jiang; Dongfeng Xue (Chemical Engineering Journal, 2025)

Efficient tetradentate palladium(II) emitters for sky-blue OLEDs through tuning triplet excited states - Kewei Xu; Jianbing Zheng; Feng Zhan; Weiwei Lou; Xiaoli Fang; Qidong Chen; Hua Guo; Wei Chen; Yun-Fang Yang; Yuanbin She; Guijie Li (Chemical Engineering Journal, 2025)

Dy and K double-additive modified Co3O4 catalyst with high resistance to NO for catalyzing N2O decomposition - Haibiao Yu; Yanan Li; Yan Pan; Yuanting Du; Xiaogeng Feng; Junshuo Cui; Zhenning Lou; Weijun Shan; Ying Xiong (Chemical Engineering Journal, 2025)

Unveiling the synergistic effect of metal/nitrogen-doped carbon and Pt3Co nanoclusters for boosting the oxygen reduction reaction in PEMFC - Shankui Luan; Jing Liu; Shengchang Li; Shuo Li; Zhangrong Lou; Mingyue Lv; Xuejing Cui; Luhua Jiang (Chemical Engineering Journal, 2025)

Unlocking ABA’s role in rice cold tolerance: insights from Zhonghua 11 and Kasalath - Wenyu Li; Xin Lou; Zhijun Wang; Di Zhang; Lingling Li; Xiaoping Ding; Gongye Cheng; Weiying Nie; Zhilin Li; Jianghui Yu; Jiwai He; Nenghui Ye; et al. (Theoretical and Applied Genetics, 2025)

Underlying Mechanism of Lysosomal Membrane Permeabilization in CNS Injury: A Literature Review - Linyi Xiang; Junsheng Lou; Jiayi Zhao; Yibo Geng; Jiacheng Zhang; Yuzhe Wu; Yinuo Zhao; Zhichao Tao; Yao Li; Jianjun Qi; Jiaoxiang Chen; Liangliang Yang; et al. (Molecular Neurobiology, 2025)

Real-time retrieval of coseismic displacement with the variometric approach augmented by BDS3 B2b corrections - Jianfei Zang; Shijie Fan; Zhicai Li; Yangmao Wen; Rongxin Fang; Yidong Lou; Chaoqian Liang; Caijun Xu (GPS Solutions, 2025)

Integrating morphology, physiology, and computer simulation to reveal the toxicity mechanism of eco-friendly rosin-based pesticides - Renle Xu; Yuhang Lou; Yanqing Gao; Shibin Shang; Zhanqian Song; Kerang Huang; Luqi Li; Lei Chen; Jian Li (Chemosphere, 2024)

Impact of recharge water source quality on Chlorella vulgaris growth and biomass: Strategies for eutrophication control in urban landscape lakes - Li Luo; Jiahao Tan; Mawuli Dzakpasu; Chenghao Lou; Wenshan Guo; Huu Hao Ngo; Xiaochang C. Wang (Science of The Total Environment, 2024)

The Keap1-Nrf2/ARE signaling pathway regulates redox balance and apoptosis in the small yellow croaker (Larimichthys polyactis) under hypoxic stress - Jingqian Wang; Li Wang; Yang Liu; Congcong Hou; Qingping Xie; Daojun Tang; Feng Liu; Bao Lou; Junquan Zhu (Science of The Total Environment, 2024)

Clarifying the impact of engine operating parameters of heavy-duty diesel vehicles on NOx and CO2 emissions using multimodal fusion methods - Tao Li; Xin Lou; Zhuoqian Yang; Chaojie Fan; Baoli Gong; Guoquan Xie; Jing Zhang; Kui Wang; Honghao Zhang; Yong Peng (Science of The Total Environment, 2024)

Discovery of natural rosin-based preservative candidates to control Phytophthora capsici for postharvest disease management of solanaceae vegetables - Renle Xu; Jiaying Wu; Xu Han; Ziyu Wang; Yuhang Lou; Yanqing Gao; Shibing Shang; Zhanqian Song; Jie Song; Jian Li (Postharvest Biology and Technology, 2024)

Field evidence and modeling validation of biogeochemical controls on the deposition of persistent organic pollutants in the deep ocean - Mengyang Liu; Haowen Zheng; Hongliang Li; Fajin Chen; Linghao Lou; Weimin Wang; Haifeng Zhang; Chunqing Chen; Jiandong Ye; Meng Yan; Kenneth M.Y. Leung; Minggang Cai (Journal of Hazardous Materials, 2024)

Cascaded recurrent networks with masked representation learning for stereo matching of high-resolution satellite images - Zhibo Rao; Xing Li; Bangshu Xiong; Yuchao Dai; Zhelun Shen; Hangbiao Li; Yue Lou (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Multi-omics analyses of the mechanism for formation of key aroma-active compounds in blood orange wine fermented by Pichia kudriavzevii - Shuxun Liu; Ying Lou; Yan Zhao; Yuling Cai; Mingfeng Cao; Yixian Li; Ping Li; Qing Gu (Food Research International, 2024)

Inhibitory effects of cold plasma-activated water on the generation of advanced glycation end products and methylimidazoles in cookies and mechanistic evaluation using electron paramagnetic resonance - Chenxia Zhang; Jian Zhang; Tiantian Huang; Pin Jiang; Xuejiao Qie; Lan Mo; Maiquan Li; Aihua Lou; Qingwu Shen; Jie Luo; Shuai Wang; Yi XueC; et al. (Food Chemistry, 2024)

Surfactin conjugated ZIF-8-NH2 based MOF with the antibacterial ability against Pseudomonas fluorescens and its application in salmon preservation - Yongfa Cheng; Yongyong Li; Jinjie Zhang; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Food Bioscience, 2024)

Effect of low-salinity seawater transient on antioxidant capacity, muscle quality and intestinal microorganism of crucian carp (Carassius auratus gibelio) - Yawen Hong; Yunyun Pan; Qijian Zhu; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Food Bioscience, 2024)

Integrated DNA methylation analysis of peripheral blood from asbestos exposed populations and patients with malignant mesothelioma reveals novel methylation driver genes of diagnostic and prognostic relevance - Lingfang Feng; Tao Li; Biao Xu; Jing Huang; Hailing Xia; Zhaoqiang Jiang; Junfei Chen; Simiao Pan; Xing Zhang; Hua Jiang; Jianlin Lou (Environmental Pollution, 2024)

Asymmetric coordinative modulation boosting the activity and thermal stability of Pt1/CeO2 for CO oxidation under harsh condition - Lijun Ni; Yuwei Zhou; Wei Tan; Hong Li; Dong Wang; Qi Zhang; Bing Yang; Jing Xu; Ying Zhang; Chengsi Pan; Yongfa Zhu; Fudong Liu; et al. (Chemical Engineering Journal, 2024)

Microphysical characteristics of torrential predecessor rain events over the Yangtze River Delta Area and the related tropical cyclones - Huiyan Xu; Bin Xie; Xiaofan Li; Ben Wang; Lingyun Lou; Zhifeng Yu; Jiaxi Wu; Dengrong Zhang; Feng Zhang (Atmospheric Research, 2024)

TEDR: A spatiotemporal attention radar extrapolation network constrained by optical flow and distribution correction - Junkai Liu; Xinwei Qian; Lu Peng; Dan Lou; Yiwen Li (Atmospheric Research, 2024)

A novel m.5906G > a variant in MT-CO1 causes MELAS/Leigh overlap syndrome - Zhimei Liu; Yaojun Xie; Xiaoting Lou; Xiaofei Zeng; Luyi Zhang; Meng Yu; Junling Wang; Jiuwei Li; Danmin Shen; Hua Li; Suzhou Zhao; Yuwei Zhou; et al. (Molecular Genetics and Genomics, 2024)

Characterization of phosphorus storage and release fluxes at the sediment–water interface of lakes in typical agricultural and irrigation areas: a case study of Chagan Lake in western Jilin, China - Yining Li; Jianmin Bian; Fan Wang; Xiaoqing Sun; Yuqi Lou (Environmental Geochemistry and Health, 2024)

A transformer-based forecasting model for F 10.7 index and its application study on the Chinese Langfang dataset - Hongwei Ye; Yanfang Zheng; Xuebao Li; Liang Dong; Wengeng Huang; Jing Wang; Shuainan Yan; Hengrui Lou; Pengchao Yan; Shunhuang Zhang; Xuefeng Li; Yi Ling; et al. (Advances in Space Research, 2024)

Effects of Temporary Rearing with Edetate Disodium on Shrimp ( Litopenaeus vannamei ) Based on UPLC-MS Untargeted Metabolomics - Yutong Wu; Jing Yang; Zixuan Kang; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Journal of Aquatic Food Product Technology, 2024)

Physical activity and DNA methylation–based markers of ageing in 6208 middle-aged and older Australians: cross-sectional and longitudinal analyses - Haoxin Tina Zheng; Danmeng Lily Li; Makayla W. C. Lou; Allison M. Hodge; Melissa C. Southey; Graham G. Giles; Roger L. Milne; Brigid M. Lynch; Pierre-Antoine Dugué (GeroScience, 2024)
Epigenetic age quantifies biological age using DNA methylation information and is a potential pathway by which physical activity benefits general health. We aimed to assess the cross-sectional and longitudinal associations between physical activity and epigenetic age in middle-aged and older Australians. Blood DNA methylation data for 6208 participants (40% female) in the Melbourne Collaborative Cohort Study (MCCS) were available at baseline (1990–1994, mean age, 59 years) and, of those, for 1009 at follow-up (2003–2007, mean age, 69 years). Physical activity measurements (weighted scores at baseline and follow-up and total MET hours per week at follow-up) were calculated from self-reported questionnaire data. Five blood methylation–based markers of ageing ( PCGrimAge , PCPhenoAge , bAge , DNAmFitAge , and DunedinPACE ) and four fitness-related markers ( DNAmGaitspeed , DNAmGripmax , DNAmVO2max , and DNAmFEV1 ) were calculated and adjusted for age. Linear regression was used to examine the cross-sectional and longitudinal associations between physical activity and epigenetic age. Effect modification by age, sex, and BMI was assessed. At baseline, a standard deviation (SD) increment in physical activity was associated with 0.03-SD ( DNAmFitAge , 95%CI = 0.01, 0.06, P = 0.02) to 0.07-SD ( bAge , 95%CI = 0.04, 0.09, P = 2 × 10 −8 ) lower epigenetic age. These associations were attenuated after adjustment for other lifestyle variables. Only weak evidence was found for the longitudinal association ( N = 1009) of changes in physical activity and epigenetic age (e.g. DNAmFitAge : adjusted β = − 0.04, 95%CI = − 0.08, 0.01). The associations were not modified by age, sex, or BMI. In middle-aged and older Australians, higher levels of self-reported physical activity were associated with slightly lower epigenetic age.

Evaluating AGS efficiency in PHA synthesis and extraction integrated with nutrient removal: The impact of COD concentrations - Quan Yuan; Song Chen; Yun Chen; Xinyu Zhang; Yuqing Lou; Xueting Li; Qian Liang; Yanping Zhang; Yingxue Sun (Chemosphere, 2024)

Gckr depletion leads to growth retardation and diet-dependent visceral obesity in red crucian carp (Carassius auratus red var.) - Juan Li; Huilin Li; Yuan Ou; Qiyong Lou; Zehong Wei; Ming Wen; Shi Wang; Qingfeng Liu; Yuqin Shu; Shaojun Liu (Aquaculture, 2024)

Parkin deficiency exacerbates particulate matter-induced injury by enhancing airway epithelial necroptosis - Yuting Lin; Meiyu Quan; Xibin Wang; Wanqi Miao; Haibo Xu; Baiqi He; Bin Liu; Yanxia Zhang; Yijing Chen; Binqian Zhou; Mengying Xu; Li Dong; et al. (Science of The Total Environment, 2024)

Prospective study on the joint effect of persistent organic pollutants and glucose metabolism on chronic kidney disease: Modifying effects of lifestyle interventions - Dandan Wei; Jiayu Shi; Haoran Xu; Yao Guo; Xueyan Wu; Zhiwei Chen; Taimeng Chen; Huilin Lou; Erbao Han; Guozhen Han; Yumeng Yan; Xiaotian Liu; et al. (Science of The Total Environment, 2024)

Small reservoirs can enhance the terrestrial carbon sink of controlled basins in karst areas worldwide - Zihao Pan; Shengtian Yang; Hezhen Lou; Jiyi Gong; Baichi Zhou; Huaixing Wang; Hao Li; Jiekang Li; Yunmeng Dai; Yin Yi; Chengcheng Gao; Xueyong Huang (Science of The Total Environment, 2024)

Agaro-oligosaccharides enhanced the Monilinia fructicola resistance of peach fruit by regulating antioxidative and phenylpropanoid metabolism - Qian Li; Yingying Wei; Yi Chen; Shu Jiang; Jianfen Ye; Feng Xu; Yongjiang Lou; Phebe Ding; Meriem Ouaziz; Xingfeng Shao (Postharvest Biology and Technology, 2024)

Advancing ship trajectory prediction: Integrating deep learning with enhanced reference trajectory correction techniques - Xueyin Li; Chunshan Liu; Jianghui Li; Lou Zhao; Zhongping Du (Ocean Engineering, 2024)

Projecting urban flood risk through hydrodynamic modeling under shared socioeconomic pathways - Yihan Lou; Pin Wang; Yao Li; Yindong Zhang; Bin Xie; Tangao Hu (Journal of Environmental Management, 2024)

Meta-analysis of GHG emissions stimulated by crop residue return in paddy fields: Strategies for mitigation - Qianying Wu; Ruitao Lou; Yong He; Yawei Li; Zhiming Qi; Junzeng Xu; Ji Liu; Mostafa Rastgou; Qianjing Jiang (Journal of Environmental Management, 2024)

Feasibility analysis of continuous extraction of biomaterials from flocculant sludge and potential applications in the fire protection field - Chen Li; Jing Liu; Chuning Yu; Guanchen Lou (Journal of Environmental Management, 2024)

Enzyme-free method for preparation of sturgeon extracts with antioxidant, hepatoprotective and immune-enhancing functions - Lijun Xu; Yu Liu; Yi Jiao; Kangrong Zhong; Jinming Li; Yongjian Guan; Huaning Wei; Wenyong Lou; Jun Ge (Food Chemistry, 2024)

Effect of psyllium husk powder on the gelation behavior, microstructure, and intermolecular interactions in myofibrillar protein gels from Andrias davidianus - Xiang Huang; Hui Yang; Aihua Lou; Shuiyan Jiang; Kelang Kang; Yingjuan Wei; Xin Li; Yingmei Wu; Meijuan Yu; Qun Huang (Food Chemistry, 2024)

Optimizing tillage regimes in rice-rapeseed rotation system to enhance crop yield and environmental sustainability - Chunyun Wang; Zongkai Wang; Mengzhen Liu; Maria Batool; Ali Mahmoud El-Badri; Xianling Wang; Hongxiang Lou; Dongli Shao; Xiaoqiang Tan; Zhen Li; Jie Kuai; Bo Wang; et al. (Field Crops Research, 2024)

Understanding the drivers of PM2.5 concentrations in Chinese cities: A comprehensive study of anthropogenic and environmental factors - Mir Muhammad Nizamani; Hai-Li Zhang; Nanthi Bolan; Qian Zhang; Lingyuan Guo; YaHui Lou; Hai-Yang Zhang; Yong Wang; Hailong Wang (Environmental Pollution, 2024)

Atomically dispersed Ir Lewis acid sites on (111)-oriented CeO2 enable enhanced reaction kinetics for Li-O2 batteries - Yang Zhao; Zhen Wang; Shuyun Guan; Yinkun Gao; Shusheng Gong; Guokang Han; Peng Gao; Shuaifeng Lou; Yongming Zhu; Xudong Li (Chemical Engineering Journal, 2024)

Double network hydrogel confined MXene/Liquid metal by dynamic hydrogen bond for high-performance wearable sensors - Yuanwan Lou; Jingkun Wang; Yubo Peng; Xiaona Wang; Jianan Zhang; Lingfeng Chen; Wenchao Gao; Zhipeng Gao; Xiaona Li; Weiyi Chen; Min Zhao (Chemical Engineering Journal, 2024)

Novel personal cooling textiles revolutionizing human thermal management: principles, designs and applications - Xianjin Hu; Ting-Ting Li; Bingbing Shou; Letian Li; Hai-Tao Ren; Ching-Wen Lou (Chemical Engineering Journal, 2024)

A novel framework for multiple thermokarst hazards risk assessment and controlling environmental factors analysis on the Qinghai-Tibet Plateau - Peiqing Lou; Tonghua Wu; Guoan Yin; Jie Chen; Xiaofan Zhu; Xiaodong Wu; Ren Li; Sizhong Yang (CATENA, 2024)

Constructing an artificial in vitro multi-enzyme cascade pathway to convert glycerol and CO2 into L-aspartic acid - Longwei Lou; Feiyan Cheng; Zonglin Li; Zhimin Li (Bioresource Technology, 2024)

Microbial groups containing alkaline phosphatase accelerate soil phosphate mineralization in two soil patterns with contrasting pH levels - Hui Li; Jitong Lin; Qi Shao; Beibei Zhang; Yunting Wang; Linke Wang; Haojie Feng; Yanhong Lou; Hui Wang; Quangang Yang; Zhongchen Yang; Hongjie Di; et al. (Journal of Soils and Sediments, 2024)

Spartina alterniflora invasion altered soil greenhouse gas emissions via affecting labile organic carbon in a coastal wetland - Guanlin Li; Sixuan Xu; Yi Tang; Yanjiao Wang; Jiabao Lou; Qiuyue Zhang; Xiaojun Zheng; Jian Li; Babar Iqbal; Pengfei Cheng; Aibin Zhan; Daolin Du (Applied Soil Ecology, 2024)

Sensitive and rapid identification of pathogens by droplet digital PCR in a cohort of septic patients: a prospective diagnostic study - Zhenping Wu; Yake Yao; Xi Li; Hongliu Cai; Guobin Wang; Wenqiao Yu; Hui Lou; Qi Chen; Zhu Zeng; Hao Yu; Jiang Xia; Yunsong Yu; et al. (Infectious Diseases, 2024)

Effect driven prioritization of contaminants in wastewater treatment plants across China: A data mining-based toxicity screening approach - Jiehui Huang; Fei Cheng; Liwei He; Xiaohan Lou; Huizhen Li; Jing You (Water Research, 2024)

Divergent chemical compositions of soil organic matter size fractions under long-term amendments across a climate gradient - Fanbo Song; Ning Hu; Yilai Lou; Huimin Zhang; Ping Zhu; Dongchu Li; Hongjun Gao; Shuiqing Zhang; Yidong Wang (Soil and Tillage Research, 2024)

Predicting tremor improvement after MRgFUS thalamotomy in essential tremor from preoperative spontaneous brain activity: A machine learning approach - Dong Zhang; Yongqin Xiong; Haoxuan Lu; Caohui Duan; Jiayu Huang; Yan Li; Xiangbing Bian; Dekang Zhang; Jiayou Zhou; Longsheng Pan; Xin Lou (Science Bulletin, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Preparation and characterization of DOPO-MMT co-stabilized gel foam for inhibiting coal spontaneous combustion - Li Ma; Jiamin Zhang; Xixi Liu; Yanpeng He; Shikui Jin; Fang Lou; Yongyong Jia; Xinli Fan; Qi Wang; Ruizhi Guo (Fuel, 2024)

A Janus evaporator based on Donnan effect for efficient solar thermal desalination - Hai-Tao Ren; Hong-Bei He; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin (Desalination, 2024)

Biomaterials in heterotopic ossification: Prophylaxis and promotion - Xu Lou; Dan Huang; Guangfeng Li; Long Bai; Jiacan Su; Hua Yue (Chemical Engineering Journal, 2024)

Nicotinamide Riboside Promotes the Proliferation of Endogenous Neural Stem Cells to Repair Spinal Cord Injury - Jianping Zhang; Jun Shang; Han Ding; Wenxiang Li; Zonghao Li; Zhongze Yuan; Han Zheng; YongFu Lou; Zhijian Wei; Hengxing Zhou; Shiqing Feng; Xiaohong Kong; et al. (Stem Cell Reviews and Reports, 2024)

The CsPPR gene with RNA-editing function involved in leaf color asymmetry of the reciprocal hybrids derived from Cucumis sativus and C. hystrix - Lei Xia; Han Wang; Xiaokun Zhao; Qinzheng Zhao; Xiaqing Yu; Ji Li; Qunfeng Lou; Jinfeng Chen; Chunyan Cheng (Planta, 2024)

Characteristics, Distribution Patterns, and Classification of Volcanic Reservoirs in the Huanghua Depression, Bohai Bay Basin, China - Jian Huang; Changqian Ma; Shihui Zhang; Muyue Xu; Da Lou; Chongbiao Leng; Mutian Qin; Hongjun Li (Journal of Earth Science, 2024)

Lithium-ion battery remaining useful life prediction: a federated learning-based approach - Ruirui Zhong; Bingtao Hu; Yixiong Feng; Shanhe Lou; Zhaoxi Hong; Fei Wang; Guangshen Li; Jianrong Tan (Energy, Ecology and Environment, 2024)

Effect of long-term dosage of hydrazine on mainstream anammox process: Biofilm characteristics and microbial community - Quan Yuan; Yuqing Lou; Song Chen; Yun Chen; Xueting Li; Xinyu Zhang; Liang Qian; Yanping Zhang; Yingxue Sun (Chemosphere, 2024)

Electrical resistivity structure of the Southeastern part of Bayan Har Block: Insights into the seismogenic environment of 2022 Maerkang earthquake swarm - Yan Zhan; Xiangyu Sun; Xuehua Liu; Lingqiang Zhao; Dahu Li; Sha Li; Zeyi Dong; Xiaoyu Lou; Chongtao Hao; Yuxin Bao (Tectonophysics, 2024)

Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2024)

Hydrothermal petroleum related to intracontinental magmatism in the Bohai Bay Basin, eastern China - Li Wang; Yuanjia Han; Da Lou; Zhiliang He; Xiaowen Guo; Matthew Steele-MacInnis (Marine and Petroleum Geology, 2024)

Biochar with KMnO4-hematite modification promoted foxtail millet growth by alleviating soil Cd and Zn biotoxicity - Xirui Kang; Na Geng; Yaping Li; Wei He; Hui Wang; Hong Pan; Quangang Yang; Zhongchen Yang; Yajie Sun; Yanhong Lou; Yuping Zhuge (Journal of Hazardous Materials, 2024)

Environmental impacts and decarbonization pathways of oily sludge pyrolysis based on life cycle assessment - Longtao Ji; Dungang Gu; Bin Cai; Lei Che; Lishan Xiao; Dominic C.Y. Foo; Nan Zhang; Yuhang Lou; Tingting Hu; Guanghui Li; Jiaqi Lu (Journal of Cleaner Production, 2024)

Exosomal proteomics and cytokine analysis distinguish silicosis cases from controls - Jiahui Yao; Yongxin Li; Shujuan Wang; Xiaowen Dong; Lingfang Feng; Xiaoxue Gong; Tiancheng Chen; Luqiao Lai; Huadong Xu; Zhaoqiang Jiang; Junfei Chen; Hailing Xia; et al. (Environmental Pollution, 2024)

Exploring the trophic transfer and effects of microplastics in freshwater ecosystems: A focus on Bellamya aeruginosa to Mylopharyngodon piceus - Ming Zhang; Yijie Jin; Cenyi Fan; Yiwen Xu; Jiateng Li; Wenjing Pan; Ziyang Lou; Huili Chen; Binsong Jin (Environmental Pollution, 2024)

Metal-organic cages for efficient capture and convenient detection of iodine from vapor and aqueous solutions - Zhi-Yong Zeng; Zhen-Chen Lou; Lianrui Hu; Weitao Dou; Xiaoli Zhao; Xiaodong Li; Junfeng Fang; Xuhong Qian; Hai-Bo Yang; Lin Xu (Chemical Engineering Journal, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Ground-based cloud microphysical observations at Mount Lu in the East Asian monsoon region from 2015 to 2020 - Lijun Guo; Jing Duan; Xiaopeng Zhang; Jun Li; Kai Lyu; Yi Chang; Guangxian Lu; Dawei Lin; Tian Luan; Xiaofeng Lou; Baojun Chen (Atmospheric Research, 2024)

Novel polyketide from Fusarium verticillioide G102 as NPC1L1 inhibitors - Yuhan Zhang; Wenjing Liu; Gang Li; Changzheng Wu; Jing Yan; Dan Feng; Shuangzhi Yuan; Renshuai Zhang; Hongxiang Lou; Xiaoping Peng (Natural Product Research, 2024)

Inspection for the desorption effect and mechanism of petroleum from contaminated soil in surfactant solution - Meixia Gu; Xiaoshuang Yin; Xiaoning Feng; Nan Shi; Wei Zhu; Shuhai Guo; Min Li; Bo Wu; Gang Li; Xingshun Cong; Bin Lou; Fushan Wen; et al. (Journal of Soils and Sediments, 2024)

Amazon drought amplifies SST warming in the North Tropical Atlantic - Wei Lou; Cheng Sun; Fred Kucharski; Jianping Li; Yusen Liu (Climate Dynamics, 2024)

Thyroglobulin as a Sensitive Biomarker of Iodine Status in Mildly and Moderately Iodine-Deficient Pregnant Women - Yujie Jiang; Simeng Gu; Zhe Mo; Xueqing Li; Chenyang Liu; Yahui Li; Guangming Mao; Yuanyang Wang; Fanjia Guo; Xiaoming Lou; Xiaofeng Wang (Biological Trace Element Research, 2024)
Pregnant women are more susceptible to iodine deficiency. However, there are limitations in existing indicators for the evaluation of iodine nutrition in pregnant women. The study aimed to explore whether thyroglobulin (Tg) can be used as a more sensitive biomarker for pregnant women with mild and moderate iodine deficiency. A repeated-measure study was conducted among 1332 pregnant women in Zhejiang Province, China. Serum and urine specimens were collected at a mean of 10, 17, and 32 weeks of pregnancy, respectively; thyroid-stimulating hormone (TSH), Tg, and urinary iodine concentrations were measured. Linear mixed effects models were used to determine the associations between interaction of iodine concentrations and increasing gestation week and TSH and Tg, where participants were divided by urinary iodine concentration (UIC). The median Tg concentration was 11.56, 11.45, and 12.43 μg/L in the first, second, and third trimesters, respectively. After controlling the covariates, the interaction effects between the iodine status and gestation week were significant for both TSH and Tg ( p = 0.038 and p = 0.007, respectively). TSH increased with the week of gestation in both iodine concentration groups. Tg increased with advancing pregnancy in the iodine-deficient group whereas it did not in the iodine-sufficient group. There was no significant variation in TSH at each trimester, and Tg was higher in the iodine-deficient group than in the iodine-sufficient group. Tg may be a more sensitive iodine status biomarker than TSH for pregnant women with mild-to-moderate iodine insufficiency.

Research on fine modeling of dispersion fuel plate based on lattice method - Yuqing Chen; Pengfei Liu; Song Li; Lei Lou; Ang Li (Annals of Nuclear Energy, 2024)

Embryonic exposure to water accommodated fraction of crude oil inhibits reproductive capability in adult female marine medaka (Oryzias melastigma) - Chenshi Wang; Yingbin Lou; Ting Wang; Ruijun Li; Mo Peng; Dongxu Gao; Wei Lei (Chemosphere, 2024)

Co-exposure to cadmium and triazophos induces variations at enzymatic and transcriptional levels in Opsariichthys bidens - Yancen Lou; Xiaojun Xu; Lu Lv; Xinfang Li; Zhangjie Chu; Yanhua Wang (Chemosphere, 2024)

Microbial transformation mechanisms of particulate organic carbon to mineral-associated organic carbon at the chemical molecular level: Highlighting the effects of ambient temperature and soil moisture - Yali Niu; Yue Li; Mingxuan Lou; Zhen Cheng; Renjie Ma; He Guo; Jian Zhou; Hongtao Jia; Lichao Fan; Tiecheng Wang (Soil Biology and Biochemistry, 2024)

Roles of the SOM and clay minerals in alleviating the leaching of Pb, Zn, and Cd from the Pb/Zn smelter soil: Multi-surface model and DFT study - Yao Shi; Anxu Sheng; Fengjiao Zhang; Zezhou Zhao; Haiyi Bao; Zhida Li; Feixiang Zan; Wei Lou; Liu Cao; John C. Crittenden; Linling Wang; Jing Chen (Science of The Total Environment, 2024)

Estimating neighborhood-based mortality risk associated with air pollution: A prospective study - Chengzhe Tao; Zhaoyin Liu; Yun Fan; Yiting Yuan; Xinru Wang; Ziyan Qiao; Zhi Li; Qiaoqiao Xu; Zhe Lou; Haowei Wang; Xiang Li; Ruiyun Li; et al. (Journal of Hazardous Materials, 2024)

Understanding the correlation between formation of flavor compounds and dominant bacteria during Luoyang mung bean sour fermentation - Xunda Wang; Xiangyu Wang; Haiwei Lou; Yue Li; Reham khashaba; Renyong Zhao (Food Bioscience, 2024)

Improving multiple LEO combination for SLR-based geodetic parameters determination using variance component estimation - Xingxing Li; Yuanchen Fu; Keke Zhang; Yongqiang Yuan; Jiaqi Wu; Jiaqing Lou (Journal of Geodesy, 2024)

HDAC6 modulates the cognitive behavioral function and hippocampal tissue pathological changes of APP/PS1 transgenic mice through HSP90-HSF1 pathway - Bingyi Wang; Siyu Liu; Kaimin Hao; YaruWang Wang; Zongjing Li; Yuanyuan Lou; Yuan Chang; Wenxiu Qi (Experimental Brain Research, 2024)

Mechanisms of cuproptosis and its relevance to distinct diseases - Qiao-mei Lou; Fei-fan Lai; Jing-wei Li; Kun-jun Mao; Hai-tong Wan; Yu He (Apoptosis, 2024)

Preharvest spraying with L-Phenylalanine effectively delayed the degradation of chlorophyll in postharvest broccoli - Xiwang Wang; Deyun Lou; Li Li; Rong Li; Wenyi Xu; Xiaojing Wang; Yongcai Li; Yang Bi (Postharvest Biology and Technology, 2024)

Spatiotemporal carbon footprint analysis of bottled water production by ultrafiltration and reverse osmosis - Wenqi Hu; Mengqi Han; Dungang Gu; Robin Smith; Tingting Hu; Yuhang Lou; Yiran Sun; Guanghui Li; Nan Zhang; Jiaqi Lu (Journal of Water Process Engineering, 2024)

Comprehending hydrochemical fingerprint, spatial patterns, and driving forces of groundwater in a topical coastal plain of Northern China based on hydrochemical and isotopic evaluations - Jiutan Liu; Kexin Lou; Zongjun Gao; Yabo Wang; Qiang Li; Menghan Tan (Journal of Cleaner Production, 2024)

Distribution, sources and ecological risks of PAHs and n-alkanes in water and sediments of typically polluted estuaries: Insights from the Xiaoqing River - Feifei Zhang; Dong Zhang; Huawei Lou; Xiaoyue Li; Hongrui Fu; Xiaojun Sun; Peiyan Sun; Xinping Wang; Mutai Bao (Journal of Environmental Management, 2024)

Sensitive small extracellular vesicles associated circRNAs analysis combined with machine learning for precision identification of gastric cancer - Min Luo; Fei Lan; Chao Yang; Tingting Ji; Yuxin Lou; Yitong Zhu; Wenbin Li; Siting Chen; Zhuowei Gao; Shihua Luo; Ye Zhang (Chemical Engineering Journal, 2024)

The pivotal role of secondary nutrients and micronutrients in regulating fruit quality and root exudates metabolism profile of citrus - Yanni Tang; Wei Lou; Xiang Yan; Shiqian Li; Pengwei Wang; Yingjie Zhou; Ting Zhan; Siming Zhang; Chengxiao Hu; Xu Wang; Hanliang Liu; Qiling Tan; et al. (Plant and Soil, 2024)

Deoxynivalenol and T-2 toxin cause liver damage and egg quality degradation through endoplasmic reticulum stress in summer laying hens - Haoneng. Guo; Hongyan Wan; Wenfang Lou; Rifat Ullah Khan; Jinming You; Bo Huang; Shu Hao; Guanhong Li; Sifa Dai (International Journal of Biometeorology, 2024)

Compressibility characteristics of municipal solid waste considering multiple factors - Yangfan Lou; Zhenying Zhang; Tuo Li; Youwen Zhang; Wenjie Chen (Environmental Science and Pollution Research, 2024)

Possible enrichment process of Cd in the Se-rich soil area of Lanshan District, Shandong Province, China - Qiao Chen; Xuewenyu Wang; Haibo Li; Shuwen Lou; Maoguo An; Chenglong Zhi; Cai Wang (Environmental Geochemistry and Health, 2024)

An improved method for LEO orbit prediction using predicted accelerometer data - Junfeng Du; Xiaolei Dai; Yidong Lou; Yun Qing; Yaquan Peng; Xingang Li (GPS Solutions, 2024)

Soil microbial functional diversity is primarily affected by soil nitrogen, salinity and alkalinity in wetland ecosystem - Meng-Yuan Zhu; Zhen-Di Liu; Yan-Yu Song; Xian-Wei Wang; Jia-Bao Yuan; Meng-Ting Li; Yan-Jing Lou; Zhen-Ling Gao; Chang-Chun Song (Applied Soil Ecology, 2024)

Wave reflection and transmission in seawater-unconsolidated-consolidated sediment models based on VGS( λ ) and Biot theories - Jiashu Lou; Jiayong Tian; Chun-Feng Li (Ocean Engineering, 2024)

A waste extended input-output-based Transformer-LSTM method for analyzing hazardous waste reduction patterns: A case study of shanghai - Qian Zhou; Jicui Cui; Lan Wang; Shirui Sun; Hanyi Jiang; Jiyang Li; A.J.Y. Chen; Pingkuo Liu; Luochun Wang; Michael Palocz-Andresen; Yue Zhu; Ziyang Lou (Journal of Cleaner Production, 2024)

Synthesis of biochar-ZnAl-layered double hydroxide composite for effective heavy metal adsorption: Exploring mechanisms and structural transformations - Rashida Hameed; Adeel Abbas; Jiabao Lou; Wajid Ali Khattak; Beenish Roha; Babar Iqbal; Guanlin Li; Qianru Zhang; Xin Zhao (Journal of Environmental Chemical Engineering, 2024)

Optimization of flavonoids extracted from hawthorn （Crataegus pinnatifida） by ultrasonic-assisted deep eutectic solvent - Xiaojing Sun; Meiling Fu; Shihao Lou; Dandan Li; Xue Han; Shan Gao; Jianhua Xiu; Junfeng Wang; Yuanyuan Ren (Food Bioscience, 2024)

Synergic regulation of crystalline phase, composition and morphology of SAPO-34 via metal assistance and in situ etching strategy - Xiaosi Zhang; Miao Yang; Dong Fan; Ye Wang; Caiyi Lou; Haocheng Hu; Bing Li; Peng Tian; Zhongmin Liu (Chemical Engineering Journal, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

The role and intervention of mitochondrial metabolism in osteoarthritis - Zhanhai Qi; Jiaping Zhu; Wusheng Cai; Chunbiao Lou; Zongyu Li (Molecular and Cellular Biochemistry, 2024)
Osteoarthritis (OA), a prevalent degenerative joint disease, affects a substantial global population. Despite the elusive etiology of OA, recent investigations have implicated mitochondrial dysfunction as a significant factor in disease pathogenesis. Mitochondria, pivotal cellular organelles accountable for energy production, exert essential roles in cellular metabolism. Hence, mitochondrial dysfunction can exert broad-ranging effects on various cellular processes implicated in OA development. This comprehensive review aims to provide an overview of the metabolic alterations occurring in OA and elucidate the diverse mechanisms through which mitochondrial dysfunction can contribute to OA pathogenesis. These mechanisms encompass heightened oxidative stress and inflammation, perturbed chondrocyte metabolism, and compromised autophagy. Furthermore, this review will explore potential interventions targeting mitochondrial metabolism as means to impede or decelerate the progression of OA. In summary, this review offers a comprehensive understanding of the involvement of mitochondrial metabolism in OA and underscores prospective intervention strategies.

Behavioral responses of Nesidiocoris tenuis (Reuter) to different monochromatic lights and light intensities - Zhen Chen; Wen Fu; Chun-Fu Zhang; Hong-Mei Li; Jun-Jun Zhang; Deng-Ji Lou; Kai-Fei Guo (Journal of Plant Diseases and Protection, 2024)

Mechanisms for improving the quality of crucian carp (Carassius auratus) by short-term low-salinity treatment revealed by UPLC-MS and GC–MS - Yawen Hong; Yunyun Pan; Qijian Zhu; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Aquaculture International, 2024)

Effects of Natural and Artificial Seawater Temporary Rearing on Flavor and Immunomodulation of Acanthopagrus schlegelii : A Study Based on GC-MS and UPLC-MS Untargeted Metabolomics - Yunyun Pan; Yawen Hong; Shiqian Fu; Huicheng Yang; Bangchu Lin; Yongjiang Lou; Yongyong Li (Journal of Aquatic Food Product Technology, 2024)

Insights into growth stages and genotypes in airborne Pb accumulation in Oryza sativa L. grains: Utilizing isotope fingerprinting alongside a model study - Qi Lin; Ming-Jin Zhuang; Wei Dai; Jing Fang; Bao-Feng Zhang; Jing-Dong Mao; Li-Ping Lou (Chemosphere, 2024)

Coinfection with infectious precocity virus and Decapod iridescent virus 1 in farmed giant freshwater prawn (Macrobrachium rosenbergii) - Guohao Wang; Xiaomeng Guo; Chengyan Zhou; Haoyu Lou; Xuan Li; Jiayun Yao; Xuan Dong; Guoliang Yang; Jie Huang (Aquaculture, 2024)

Natural versus artificial seawater: Impacts on antioxidant capacity, muscle quality and gut microbiota of Acanthopagrus schlegelii during temporary rearing - Yunyun Pan; Chang Liu; Yawen Hong; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Aquaculture, 2024)

The promoting effects of soil microplastics on alien plant invasion depend on microplastic shape and concentration - Guanlin Li; Yi Tang; Jiabao Lou; Yanjiao Wang; Shiyu Yin; Lianghui Li; Babar Iqbal; Yudi M. Lozano; Tingting Zhao; Daolin Du (Science of The Total Environment, 2024)

Occurrence and distribution of antibiotics and antibiotic resistance genes from the land to ocean in Daliao River-Liaodong Bay, China - Yunfeng Xu; Hui Gao; Ruijing Li; Yingbin Lou; Bing Li; Guanjie Cheng; Guangshui Na (Marine Environmental Research, 2024)

Single-atom tailored transition metal oxide enhances d-p hybridization in catalytic conversion for lithium-oxygen batteries - Shuyun Guan; Xudong Li; Yang Zhao; Guokang Han; Shuaifeng Lou; Yongming Zhu (Chemical Engineering Journal, 2024)

Reshaped buried interface by comprehensive passivation for highly efficient perovskite photovoltaics - Lei Huang; Kai-Li Wang; Run-Jun Jin; Jing Chen; Chun-Hao Chen; Yu Xia; Yan-Hui Lou; Zhao-Kui Wang (Chemical Engineering Journal, 2024)

Large room-temperature electrocaloric response achieved by tailoring the first-order orthorhombic-tetragonal phase transition in BaTiO3-based ferroelectric ceramics - Ruirui Kang; Wenjing Qiao; Junjie Xiong; Haichao Hu; Ming Wu; Feng Li; Yangfei Gao; Lixue Zhang; Yingying Zhao; Xiaojie Lou (Chemical Engineering Journal, 2024)

Beneficial efficacy and mode of action of probiotic Bacillus subtilis SWL−19 on the silkworm (Bombyx mori L.) - Guannan Li; Yi Xiao; Jia Leng; Qinian Lou; Tianfu Zhao (Symbiosis, 2024)

Effects of degradable and non-degradable microplastics and oxytetracycline co-exposure on soil N2O and CO2 emissions - Kiran Yasmin Khan; Yi Tang; Pengfei Cheng; Yunliang Song; Xinyu Li; Jiabao Lou; Babar Iqbal; Xin Zhao; Rashida Hameed; Guanlin Li; Daolin Du (Applied Soil Ecology, 2024)

Tris buffer-accelerated ligand exchange rate for instant fluorescence detection of trivalent chromium ion - Nan Wang; Qianni Gao; Xiaoqi Li; Jinming Li; Xinhui Lou (Analytica Chimica Acta, 2024)

Water-saving irrigation and delayed sowing increased the emission intensity of CH4 and N2O in the rice-wheat rotated field under nighttime warming - Yunsheng Lou; Jun Li; Junhong Guo; Defeng Pan; Zhen Zhang; Li Ma; Rui Li; Lixuan Ren (Agriculture, Ecosystems & Environment, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

Typical antibiotic resistance genes and their association with driving factors in the coastal areas of Yangtze River Estuary - Qiuhong Xu; Shuguang Liu; Sha Lou; Junbiao Tu; Xin Li; Yuchen Jin; Wenjun Yin; Larisa Dorzhievna Radnaeva; Elena Nikitina; Aleksei Nikolavich Makhinov; José Tavares Araruna; Irina Viktorovna Fedorova (Environmental Science and Pollution Research, 2024)

Evaluation of the ecological status of shallow-water coral reefs in China using a novel method and identification of environmental factors for coral decline - Yihua Lyu; Weina Wang; Zihua Zhou; Zhiqiang Geng; Houlei Jia; Chuqian Lu; Zhiqiang Chen; Wei Deng; Xiaofei Xiong; Ronggui Shi; Haitao Li; Zhenxiong Yang; et al. (Marine Pollution Bulletin, 2024)

Environmental arsenic pollution induced liver oxidative stress injury by regulating miR-155 through inhibition of AUF1 - Ying Lv; Hongling Wang; Dan Zheng; Mingyang Shi; Dingnian Bi; Qian Hu; Haiyan Zhi; Didong Lou; Jun Li; Shaofeng Wei; Yong Hu (Science of The Total Environment, 2024)

Interactive effects of grassland utilization and climatic factors govern the plant diversity-soil C relationship in steppe of North China - Tengfei Li; Shenghua Chang; Zhaofeng Wang; Yunxiang Cheng; Zechen Peng; Lan Li; Shanning Lou; Yongjie Liu; Deli Wang; Huaping Zhong; Huazhong Zhu; Fujiang Hou; et al. (Science of The Total Environment, 2024)

Dynamic hysteresis compensation and iterative learning control for underwater flexible structures actuated by macro fiber composites - Pengfei Zhan; Junqiang Lou; Tehuan Chen; Guoping Li; Chao Xu; Yanding Wei (Ocean Engineering, 2024)

Different responses of marine microalgae Phaeodactylum tricornutum upon exposures to WAF and CEWAF of crude oil: A case study coupled with stable isotopic signatures - Yadi Lou; Ying Wang; Shiyue Li; Fuwei Yu; Xing Liu; Yi Cong; Zhaochuan Li; Fei Jin; Mingxing Zhang; Ziwei Yao; Juying Wang (Journal of Hazardous Materials, 2024)

The effect of electron beam irradiation combined with slurry ice on physicochemical parameters and bacterial communities of shrimp (Litopenaeus vannamei) during refrigerated storage - Chang Liu; Yunyun Pan; Yongyong Li; Huicheng Yang; Bangchu Lin; Zheyun Dong; Yongjiang Lou; Shiqian Fu (Food Control, 2024)

Biofilm formation and associated gene expression changes in Cronobacter from cereal related samples in China - Xiuqin Lou; Yue Wu; Zhenzhou Huang; Wei Zhang; Xiao Xiao; Jun Wu; Jun Li; Zhiguo Fang (Food Microbiology, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Correction to: Ketamine Improves the Glymphatic Pathway by Reducing the Pyroptosis of Hippocampal Astrocytes in the Chronic Unpredictable Mild Stress Model - Gehua Wen; Xiaoni Zhan; Xiaoming Xu; Xi Xia; Shukun Jiang; Xinghua Ren; Weishu Ren; Haoyang Lou; Lei Lu; Anca Hermenean; Jun Yao; Lina Gao; et al. (Molecular Neurobiology, 2024)

Ketamine Improves the Glymphatic Pathway by Reducing the Pyroptosis of Hippocampal Astrocytes in the Chronic Unpredictable Mild Stress Model - Gehua Wen; Xiaoni Zhan; Xiaoming Xu; Xi Xia; Shukun Jiang; Xinghua Ren; Weishu Ren; Haoyang Lou; Lei Lu; Anca Hermenean; Jun Yao; Lina Gao; et al. (Molecular Neurobiology, 2024)

Study on the poroelastic behaviors of the defected osteochondral unit - Hao Zhong; Xinqi Lou; Xuanze Fan; Songyuan Wang; Xiyu Wang; Lei Ma; Pengcui Li; Yanqin Wang; Xiaochun Wei; Jing Chen; Yanru Xue; Xiaogang Wu; et al. (Medical & Biological Engineering & Computing, 2024)

Portable photoelectrochemical immunoassay with micro-electro-mechanical-system for alpha-fetoprotein in hepatocellular carcinoma - Fangming Lou; Shaojie Wang; Bo Han; Qunfang Li; Dianping Tang (Analytica Chimica Acta, 2024)

Multi-object detection and behavior tracking of sea cucumbers with skin ulceration syndrome based on deep learning - Fengli Ge; Kui Xuan; Peng Lou; Juan Li; Lingxu Jiang; Jiasheng Wang; Qi Lin (Frontiers in Marine Science, 2024)
Skin ulceration syndrome of sea cucumbers is one of the most serious diseases in intensive aquaculture, and it is the most effective way of preventing the spread of this disease to detect the abnormal behavior of sea cucumbers in time and take corresponding measures. However, the detection and tracking of multi-object is a hard problem in sea cucumber behavior analysis. To solve this problem, this paper first proposes a novel one-stage algorithm SUS-YOLOv5 for multi-object detection and tracking of sea cucumbers. The proposed SUS-YOLOv5 optimizes the maximum suppression algorithm in the overlapping region of the object detection box. Next, the SE-BiFPN feature fusion structure is proposed to enhance the transmission efficiency of feature information between deep and shallow layers of the network. Then, a MO-Tracking algorithm is proposed integrated with DeepSORT to achieve real-time multi-object tracking. Experimental results show that the mAP @0.5 and mAP @0.5:0.95 of the proposed object detector reach 95.40% and 83.80%, respectively, which are 3.30% and 4.10% higher than the original YOLOv5s. Compared with the traditional SSD, YOLOv3, and YOLOv4, the mAP of SUS-YOLOv5 is improved by 5.49%, 1.57%, and 3.76%, respectively. This research can realize the multi-object detection and tracking, which lays the foundation for the prediction of skin ulceration syndrome in sea cucumbers and has a certain practical application value for improving the intelligence level of aquaculture.

DEHP and DINP accelerate aging effects in male and female of Drosophila melanogaster depend on AKT/FOXO pathway - Xudong Liu; Lulu Gao; Xian Li; Yang Liu; Xiaofan Lou; Mingsheng Yang; Weidong Wu; Xiaomeng Liu (Toxicology in Vitro, 2024)

Per- and polyfluoroalkyl substances (PFASs) in Chinese surface water: Temporal trends and geographical distribution - Jie Wang; Cheng Shen; Jin Zhang; Guangyu Lou; Shengdao Shan; Yaqian Zhao; Yu Bon Man; Yuliang Li (Science of The Total Environment, 2024)

Tsaokoflavanols A1–J1: Flavanol-fatty alcohol hybrids with HPL inhibitory activity from Amomum tsao-ko - Tian-Rong Yang; Shi-Chao Huang; Yun-Fen Wang; Zai-Xiang Lou; Shao-Xing Dai; Li-Hua Su; Min Xu (Phytochemistry, 2024)

Maternal exposure to E 551 during pregnancy leads to genome-wide DNA methylation changes and metabolic disorders in the livers of pregnant mice and their fetuses - Yingqi Zhan; He Lou; Rongshang Shou; Anyao Li; Jiaxin Shang; Yanyan Jin; Lu Li; Lidan Zhu; Xiaoyan Lu; Xiaohui Fan (Journal of Hazardous Materials, 2024)

Survey of the biogenic amines in typical foods commonly consumed from the Chinese market - Xuan Zhang; Changling Fang; Xiaoyi Lou; Feng Han; Siman Li; Yongfu Shi; Dongmei Huang (Food Control, 2024)

Experimental, numerical and analytical analysis of a single-span steel portal frame exposed to fire - Guo-Biao Lou; Jing Hou; Hong-Hui Qi; Yaqiang Jiang; Bo Zhong; Yansong Pang; Guo-Qiang Li (Engineering Structures, 2024)

Rosette-like (Ni,Co)Se2@Nb2CTx MXene heterostructure with abundant Se vacancies for high-performance flexible supercapacitor electrodes - Baolei Shen; Xianjin Hu; Hai-Tao Ren; Hao-Kai Peng; Bing-Chiuan Shiu; Jia-Horng Lin; Ching-Wen Lou; Ting-Ting Li (Chemical Engineering Journal, 2024)

Effects of flue gas desulfurization gypsum and clover planting on qualities of soil and winter jujube in coastal saline-alkali orchard of north China - Qi Shao; Xuejing Xia; Guihua Li; Hui Li; Jitong Lin; Yanhong Lou; Quangang Yang; Hui Wang; Zhongchen Yang; Hong Pan; Yuping Zhuge (Soil Ecology Letters, 2024)

Simultaneous Determination of Seven Pyrethroid Pesticide Residues in Aquatic Products by Gas Chromatography - Changling Fang; Xiaoyi Lou; Xuan Zhang; Siman Li; Yunyu Tang; Yongfu Shi; Dongmei Huang (Fishes, 2024)
Aquatic products are good sources of essential nutrients, but the presence of pyrethroids (PYRs) as contaminants may pose risks to consumer health as the intricate matrices of PYRs usually obstruct chemical hazard detection. In this study, a gas chromatographic method was established and validated for simultaneously detecting residues of seven PYRs (cyhalothrin, permethrin, cyfluthrin, cypermethrin, tau-fluvalinate, fenvalerate, deltamethrin) in aquatic products. The aim of this method was to assess better the potential risks of pesticide residues in aquatic products. The PYRs in aquatic products were extracted with acetonitrile, purified with n-hexane saturated with acetonitrile, and cleaned up on a Cleanert® Alumina N column. Statistical analysis and orthogonal array experimental design were used to optimize the key parameters. To validate the proposed method, commonly consumed aquatic products (such as carp, crucian carp, whiteleg shrimp, river crab, sea cucumber, and scallop) were obtained from local supermarkets in Shanghai. Satisfied linearity of the calibration curves was achieved in a matrix-matched standard solution, with a correlation coefficient (R2) larger than 0.995. The average recoveries at five fortification levels varied from 77.0% to 117.2%, with relative standard deviations (RSDs) below 11.1%. Concerning electron capture detection, the limits of detection (LOD) and limits of quantification (LOQ) were 2.0–5.0 µg/kg and 5.0–10.0 µg/kg, respectively. These results demonstrate the high stability and sensitivity of this method for simultaneously detecting PYRs in aquatic products, having great practicability and which can be popularized easily.

Characterization of the effects of Chinese peony (Radix paeoniae Alba) and its active ingredients on the hematopoietic function of the Chinese mitten crab (Eriocheir sinensis) - Sunjian Lyu; Weifeng Shen; Qi Guo; Mingming Han; Fulei Xiong; Li Liu; Weishao Bu; Julin Yuan; Bao Lou (Aquaculture, 2024)

Microbiome-functionality in anaerobic digesters: A critical review - Xingxing Zhang; Yiwei Wang; Pengbo Jiao; Ming Zhang; Ye Deng; Chengying Jiang; Xian-Wei Liu; Liping Lou; Yongmei Li; Xu-Xiang Zhang; Liping Ma (Water Research, 2024)

Micro/nanoplastics: Critical review of their impacts on plants, interactions with other contaminants (antibiotics, heavy metals, and polycyclic aromatic hydrocarbons), and management strategies - Ali Raza Khan; Zaid Ulhassan; Guanlin Li; Jiabao Lou; Babar Iqbal; Abdul Salam; Wardah Azhar; Sundas Batool; Tingting Zhao; Kexin Li; Qiuyue Zhang; Xin Zhao; et al. (Science of The Total Environment, 2024)

Material transport patterns in the Bohai Sea: A Lagrangian flow network perspective - Qi Lou; Xusheng Xiang; Xueqing Zhang; Zhendong Cao; Zhengyan Li (Journal of Hydrology, 2024)

Management of the designed risk level of urban drainage system in the future: Evidence from haining city, China - Yihan Lou; Pin Wang; Yao Li; Luoyang Wang; Chaohui Chen; Jiahui Li; Tangao Hu (Journal of Environmental Management, 2024)

Multi-electron collaborative photo-Fenton-like system for indoor air purification: A case study of Cu(II) grafted BaTiO3 with oxygen vacancies - Qinqin Xiao; Xiaohang Lou; Long Chen; Miao Li; Xiaoqing Qiu (Journal of Environmental Chemical Engineering, 2024)

Photothermal-driven pH-responsive fiber composite membrane for oil-wastewater purification - Shuxia Li; Jia-Horng Lin; Hai-Tao Ren; Bing-Chiuan Shiu; Fei Sun; Ching-Wen Lou; Ting-Ting Li (Journal of Environmental Chemical Engineering, 2024)

Characteristics of ash formed by different lubricant additives and its effect on DPF performance - Pi-qiang Tan; Tian-peng Liu; Li-shuang Duan; Yi-fan Yin; Di-ming Lou; Zhi-yuan Hu (Fuel, 2024)

Reactive force field molecular dynamics (ReaxFF-MD) simulation of lignite combustion under an external electric field - Minggao Yu; Rongyang Lou; Haitao Li; Fengchuan Wang; Jiachen Wang; Kai Wang (Fuel, 2024)

Phase transition behavior and mesophase aging phenomenon during liquid-state carbonization of FCC decant oil - Bin Lou; Jichang Zhang; Jun Li; Weichao Chou; Luning Chai; Lingyan Tian; Xiaofeng Wang; Xiaoqiao Huang; Dong Liu (Fuel, 2024)

Selecting autochthonous lactic acid bacteria for co-inoculation in Chinese bayberry wine production: Stress response, starter cultures application and volatilomic study - Qing Gu; Yixian Li; Ying Lou; Yan Zhao; Xujie Feng; Ping Li; Oskar Laaksonen; Baoru Yang; Vittorio Capozzi; Shuxun Liu (Food Research International, 2024)

Largemouth bass galectin, MsGal-9: Mediating various functions as a pattern recognition receptor and a potential damage-associated molecular pattern - Mengmeng Huang; Xiaocong Lou; Tao Tao; Haoyuan Li; Yang Guo; Zhenzhen Yuan; Shun Yang; Hui Fei (Fish & Shellfish Immunology, 2024)

Negative thermopower anisotropic ionic thermoelectric hydrogels based on synergistic coordination and hydration for low-grade heat harvesting - Luzheng Chen; Xuhui Rong; Zhuqing Liu; Qijun Ding; Xia Li; Yifei Jiang; Wenjia Han; Jiang Lou (Chemical Engineering Journal, 2024)

Modulating electronic confinement and structural distortion of multiple resonance emitters enables high-performance ultrapure blue OLED - Baoxi Li; Jingli Lou; Baijun Zhang; Lu Liu; Xin He; He Xu; Xing Feng; Han Zhang; Zhiming Wang; Ben Zhong Tang (Chemical Engineering Journal, 2024)

Simultaneous modification of interface and modulation of crystal growth by deep eutectic solvent for FACs-Based perovskite solar cells - Lingyun Lou; Li Wan; Zhong-Sheng Wang (Chemical Engineering Journal, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Regulation of Hepatocellular Cholesterol Metabolism By Lactobacillus Paracasei BY2 and Its Embedding Delivery - Hua-Ling Cui; Meng-Fan Li; Sheng-Ya Liu; Ming Yu; Wen-Yong Lou (Probiotics and Antimicrobial Proteins, 2024)

The N-terminal α2 helix element is critical for the activity of the rice transcription factor MYC2 - Hongyue Zu; Gaochen Jin; Yaze Kong; Zhaoyang Li; Yonggen Lou; Ran Li (Plant Molecular Biology, 2024)

Correction to: Evaluation of EpCAM-specific exosomal lncRNAs as potential diagnostic biomarkers for lung cancer using droplet digital PCR - Xintong Shen; Yifeng Yang; Yinfeng Chen; Chengwei Zhou; Xiaodong Zhao; Nan Li; Chengtao Lou; Ying Huang; Dongmei Tian; Yan Shen; Xiaodan Meng (Journal of Molecular Medicine, 2024)

A real-time fluorogenic recombinase polymerase amplification microfluidic chip (on-chip RPA) for multiple detection of pathogenic microorganisms of penaeid shrimp - Qiang Li; Lijun Duan; Dongsheng Jin; Yuxin Chen; Yirong Lou; Qianjin Zhou; Zhongjie Xu; Fangjie Chen; Hongxian Chen; Guizong Xu; Maocang Yan; Guanjun Yang; et al. (Aquaculture, 2024)

Ecological risk assessment of 50 emerging contaminants in surface water of the Greater Bay Area, China - Ziye Wang; Zhengyan Li; Qi Lou; Jinfen Pan; Jie Wang; Shuhui Men; Zhenguang Yan (Science of The Total Environment, 2024)

Studying the evolutions, differences, and water security impacts of water demands under shared socioeconomic pathways: A SEMs-bootstrap-ANN approach applied to Sichuan Province - Li Mo; Sijing Lou; Yongqiang Wang; Zixuan Liu; Pingan Ren (Journal of Environmental Management, 2024)

Effects of lubricant components on ash-bridge deposition characteristics in the diesel particulate filter - Pi-qiang Tan; Yuan Tian; Li-shuang Duan; Yun-peng Li; Di-ming Lou; Zhi-yuan Hu (Fuel, 2024)

Comparative analysis of whole-transcriptome RNA expression of lung tissue of Chinese soft-shell turtle infected by Trionyx sinensis Hemorrhagic Syndrome Virus - Sunjian Lyu; Qi Guo; Weifeng Shen; Mingming Han; Fulei Xiong; Xiaoling Dai; Li Liu; Weishao Bu; Bao Lou; Julin Yuan (Fish & Shellfish Immunology, 2024)

Ultrasmall Ce-based metal–organic frameworks nanozyme with hydrolytic activity for boosting antibiofilm therapy - Xin Yuan; Jun Xiong; Xiaoling Wu; Niya Ta; Shuli Liu; Zhixian Li; Wen-Yong Lou (Chemical Engineering Journal, 2024)

Performance assessment of the BDS-3 PPP-B2b service for real-time earthquake source description: a case study for the 2021 Mw 7.4 Maduo earthquake - Jianfei Zang; Shijie Fan; Caijun Xu; Zhicai Li; Rongxin Fang; Yidong Lou (GPS Solutions, 2024)

Geocenter motion derived from multi-LEO precise orbit determination based on GNSS observations and dynamic force models - Keke Zhang; Xingxing Li; Weiping Jiang; Yuanchen Fu; Yongqiang Yuan; Jiaqing Lou; Wei Zhang (GPS Solutions, 2024)

Is green manure a viable substitute for inorganic fertilizer to improve grain yields and advance carbon neutrality in paddy agriculture? - Ruitao Lou; Yong Li; Ying Liu; Qianjing Jiang; Qingguan Wu; Yong He; Ji Liu (Agriculture, Ecosystems & Environment, 2024)

Physicochemical characteristics of ash-bridges in diesel particulate filter - Li-shuang Duan; Pi-qiang Tan; Yun-peng Li; Yi-fan Yin; Di-ming Lou; Zhi-yuan Hu (Journal of Cleaner Production, 2023)

Inhibition evaluation of modified-fly ash inhibitors in methane/coal dust deflagrations - Minggao Yu; Jiachen Wang; Shanshan Li; Haitao Li; Fuer Zhai; Fengchuan Wang; Rongyang Lou; Yangjian Hu; Jingyu Cui (Fuel, 2023)

Effects of static magnetic field-assisted freezing on physicochemical indices and bacterial communities of shrimp (Penaeus vannamei) - Qijian Zhu; Shiqian Fu; Huicheng Yang; Bangchu Lin; Yongjiang Lou; Yongyong Li (Food Bioscience, 2023)

Comparison of anthocyanin and volatile organic compounds in juices and fruit wines made from blood oranges (Citrus sinensis L. Osbeck) at different maturity stages - Shuxun Liu; Ying Lou; Yixian Li; Yan Zhao; Xujie Feng; Vittorio Capozzi; Oskar Laaksonen; Baoru Yang; Ping Li; Qing Gu (Food Bioscience, 2023)

Antimicrobial photodynamic therapy encapsulation technology: Frontier exploration and application prospects of novel antimicrobial technology - Xianjin Hu; Bingbing Shou; Lu Yang; Letian Li; Hai-Tao Ren; Jia-Horng Lin; Ching-Wen Lou; Ting-Ting Li (Chemical Engineering Journal, 2023)

Nonradical activation of Oxone over Fe-doped nitrogen carbon (Fe@NC) armor catalysts for efficient degradation of anthropogenic phenolics (p-nitrophenol, 4-chlorophenol) in groundwater matrices - Lei Su; Yifan Li; Zhenkai Wang; Yao-Yin Lou; Qi-Zheng Zheng; Zhangxiong Wu; Sheng-Peng Sun (Chemical Engineering Journal, 2023)

Super-stretching and high-performance ionic thermoelectric hydrogels based on carboxylated bacterial cellulose coordination for self-powered sensors - Luzheng Chen; Jiang Lou; Xuhui Rong; Zhuqing Liu; Qijun Ding; Xia Li; Yifei Jiang; Xingxiang Ji; Wenjia Han (Carbohydrate Polymers, 2023)

Growth differentiation factor 7 pretreatment enhances the therapeutic capacity of bone marrow-derived mesenchymal stromal cells against cerebral ischemia-reperfusion injury - Hongmiao Tao; Lin Li; Lihua Dong; Haohao Chen; Xiaoyun Shan; Lujie Zhuge; Hongqiang Lou (Chemico-Biological Interactions, 2023)

Towards Millimeter-Level Accuracy in GNSS-Based Space Geodesy: A Review of Error Budget for GNSS Precise Point Positioning - Xianjie Li; Jean-Pierre Barriot; Yidong Lou; Weixing Zhang; Pengbo Li; Chuang Shi (Surveys in Geophysics, 2023)
The aim of the new generation of Global Geodetic Observing System is a millimeter-level accuracy in positioning, with a crucial role to be played by Global Navigation Satellites Systems (GNSS) in the Precise Point Positioning (PPP) mode. This is of course because GNSS constellations and receivers provide an efficient stand-alone technique with a homogeneous performance over large areas (positions, navigation and meteorology) when used in conjunction with the PPP mode, with also an ever-increasing data flow and different satellite line-of-sights. The requirement of accuracies reaching the millimeter or sub-millimeter implies a knowledge at this level of each line in the GNSS-PPP error budget, including, but not restricted to: clock biases, troposphere and ionosphere delays, multipath and ground deformations. In this review study, we consider this millimeter-/submillimeter level GNSS-PPP error budget, and possible mitigations and improvements in the frame of the existing global constellations: GPS, Galileo, GLONASS and BDS, in view of augmented constellations and/or Low Earth Orbit constellations, which will be available in the near future. We also pay a special attention to systematic biases that can/could exist between constellations.

Disentangling in-vivo microstructural changes of white and gray matter in mild cognitive impairment and Alzheimer’s disease: a systematic review and meta-analysis - Shuchang Zhong; Jingjing Lou; Ke Ma; Zhenyu Shu; Lin Chen; Chao Li; Qing Ye; Liang Zhou; Ye Shen; Xiangming Ye; Jie Zhang (Brain Imaging and Behavior, 2023)

Occurrence of sulfonamides and tetracyclines in the coastal areas of the Yangtze River (China) Estuary - Shuguang Liu; Xin Li; Sha Lou; Qiuhong Xu; Yuchen Jin; Radnaeva Larisa Dorzhievna; Nikitina Elena; Makhinov Aleksei Nikolavich; Araruna José Tavares; Fedorova Irina Viktorovna (Environmental Science and Pollution Research, 2023)

Relationship of individual and mixed urinary metals exposure with liver function in the China National Human Biomonitoring (CNHBM) of Zhejiang Province - Ping Cheng; Yi Tao; Jinfeng Hu; Hongxin Wang; Ruifang Zhao; Shenghua Mei; Yin Yang; Fugen Ye; Zhijian Chen; Hao Ding; Mingluan Xing; Peiwei Xu; et al. (Chemosphere, 2023)

Change to the transcriptomic profile, oxidative stress, apoptotic and immunity in the liver of small yellow croaker (Larimichthys polyactis) under hypoxic stress - Jingqian Wang; Li Wang; Yang Liu; Chen Du; Congcong Hou; Qingping Xie; Daojun Tang; Feng Liu; Bao Lou; Junquan Zhu (Aquaculture, 2023)

How weather impacts the citizens' activity patterns in southern China? Enlightenment from large-scale mobile phone signaling data of Guangzhou - Yukai Zou; Weien Xie; Siwei Lou; Lei Zhang; Yu Huang; Dawei Xia; Xiaolin Yang; Chao Feng; Yilin Li (Urban Climate, 2023)

Phosphorus deficiency is the main limiting factor for re-vegetation and soil microorganisms in Mu Us Sandy Land, Northwest China - Jiakun Yan; Li Lou; Wenhui Bai; Suiqi Zhang; Ningning Zhang (Science of The Total Environment, 2023)

Whole-genome sequencing-based analysis of antimicrobial resistance, virulence factors, and genetic diversity in Yersinia isolated in Wenzhou, China 2020 - Shaojie Huang; Yi Li; Chengji Hong; Yafang Jin; Shengkai Li; Xuelian Xu; Yanmei Xia; Leyi Zhang; Yongliang Lou; Wanchun Guan (Molecular Phylogenetics and Evolution, 2023)

Chitosan bimetallic particles with in-situ ROS driven self-cleaning performance for tetracycline elimination - Yaopeng Zhang; Miaojia Du; Hui Chen; Chensi Shen; Mengmeng Lou; Chenye Xu; Chunyan Ma; Fang Li (Journal of Cleaner Production, 2023)

Effect of ash on temperature and particulate emission characteristics of diesel particulate filter during active regeneration - Li-shuang Duan; Pi-qiang Tan; Yi-fan Yin; Yun-peng Li; Di-ming Lou; Zhi-yuan Hu (Journal of Cleaner Production, 2023)

Direct identification of total and missing OH reactivities from light-duty gasoline vehicle exhaust in China based on LP-LIF measurement - Xuehui Liu; Zibing Yuan; Qing'e Sha; Shengrong Lou; Hongli Wang; Xin Li; Junyu Zheng; Bin Yuan; Min Shao (Journal of Environmental Sciences, 2023)

Experimental study on the influence of distributor types on the property effect of finned evaporator - Zhili Sun; Jintao Li; Wanfei Cheng; Youcai Liang; Lin Lou; Hui Jin; Chao Zhang; Yian Wang (International Journal of Refrigeration, 2023)

Influence of a self-formed three-stage dual-wing-shaped carbon on reduction of soot emission from acetylene diffusion flame - Yuhang Lu; Hui Guo; Hanqing Lou; Yange Suo; Yanghui Ye; Guoneng Li; Zhiguo Zhang; Dan Zhao (Fuel, 2023)

Agricultural waste valorization towards (nano)catalysts for the production of chemicals and materials - Junwei Lou; Masoumeh Rezaee Babadi; Maryam Otadi; Mehrasa Tarahomi; Quyet Van Le; Hossein Ali Khonakdar; Cheng Li (Fuel, 2023)

Determination of vitamin K in infant formulas by liquid chromatography–online electrochemical reduction based on porous Pt/Ti electrode-fluorescence detection - Zhenzhen Wang; Chaoyang Sun; Shuchao Wu; Siyuan Ding; Lingxia Chen; Liying Wu; Jian Lou; Bin Xia; Li Wang (Food Chemistry, 2023)

A-site defects boosted exsolution on (La0.5Ca0.5)(1-α)Ni0.06Ti0.94O3-δ for ethanol steam reforming - Shifeng Lou; Xuan Meng; Naiwang Liu; Li Shi (Chemical Engineering Journal, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Ent-eudesmane sesquiterpenoids from the Chinese liverwort Chiloscyphus polyanthus - Ming-Zhu Zhu; Yi Li; Jin-Chuan Zhou; Dong-Xue Lv; Xiao-Jie Fu; Zhen Liang; Shuang-Zhi Yuan; Jing-Jing Han; Jiao-Zhen Zhang; Ze-Jun Xu; Wen-Qiang Chang; Hong-Xiang Lou (Phytochemistry, 2023)

Coupling effect of vortex-induced vibration and local scour of double tandem pipelines in steady current - Weixing Liang; Min Lou; Changhong Fan; Deguang Zhao; Xiang Li (Ocean Engineering, 2023)

Application of a deep learning-based discrete weather data continuousization model in ship route optimization - Zhizheng Wu; Shengzheng Wang; Qiumeng Yuan; Naiyuan Lou; Siyuan Qiu; Li Bo; Xiuzhi Chen (Ocean Engineering, 2023)

Melatonin alleviates aluminum toxicity by regulating aluminum-responsive and nonresponsive pathways in hickory - Hao Zeng; Yaru Li; Weijie Chen; Jingwei Yan; Jiasheng Wu; Heqiang Lou (Journal of Hazardous Materials, 2023)

Multimodal remote sensing application for weed competition time series analysis in maize farmland ecosystems - Longzhe Quan; Zhaoxia Lou; Xiaolan Lv; Deng Sun; Fulin Xia; Hailong Li; Wenfeng Sun (Journal of Environmental Management, 2023)

UPU structured lipids and their preparation methods: A mini review - Ke Yue; Hang Yang; Jian Li; Yanlan Bi; Linshang Zhang; Wen-Yong Lou (Food Bioscience, 2023)

Comparison of phenolic profiles of albino bilberry (Vaccinium myrtillus L.) wines fermented by non-Saccharomyces yeasts - Shuxun Liu; Yan Zhao; Yixian Li; Ying Lou; Xujie Feng; Baoru Yang (Food Bioscience, 2023)

Auxin plays a key role in nitrogen and plant density-modulated root growth and yield in different plant types of rapeseed - Hongxiang Lou; Bowen Zhao; Yan Peng; Ali Mahmoud El-Badri; Maria Batool; Chunyun Wang; Zongkai Wang; Wei Huang; Tianyao Wang; Zhen Li; Zhenghua Xu; Jing Wang; et al. (Field Crops Research, 2023)

The synergistic strategy of hexaazatrinaphthylene-cyanoindone-based electron transporting material enabling efficient and stable inverted perovskite solar cells - Li Wan; Lingyun Lou; Zhong-Sheng Wang (Chemical Engineering Journal, 2023)

Synthesis of bifunctional thermal response promoters for improved high-solids enzymatic hydrolysis of corncob residues - Feiyun Li; Haohao Li; Hongming Lou; Fubao Sun; Yanjun Tang (Bioresource Technology, 2023)

Correction to: Long-term changes in observed soil temperature over Poyang Lake Basin, China, during 1960–2016 - Dan Lou; Xiao Shi; Waheed Ullah; Dawei Shi; Chao Li; Yuanfang Chai; Xu Jinping; Hao Zhou (Theoretical and Applied Climatology, 2023)

Long-term changes in observed soil temperature over Poyang Lake Basin, China, during 1960–2016 - Dan Lou; Xiao Shi; Waheed Ullah; Dawei Shi; Chao Li; Yuanfang Chai; Xu Jinping; Hao Zhou (Theoretical and Applied Climatology, 2023)

Association of urinary bisphenols with thyroid function in the general population: a cross-sectional study of an industrial park in China - Yang Hu; Shiming Lai; Ying Li; Xiaodong Wu; Mingluan Xing; Xueqing Li; Dandan Xu; Yuan Chen; Jie Xiang; Ping Cheng; Xiaofeng Wang; Zhijian Chen; et al. (Environmental Science and Pollution Research, 2023)

Bisphenol A decreases the developmental toxicity and histopathological alterations caused by polystyrene nanoplastics in developing marine medaka Oryzias melastigma - Fuwei Yu; Fei Jin; Yi Cong; Yadi Lou; Zhaochuan Li; Ruijing Li; Baojun Ding; Ying Wang; Jingwen Chen; Juying Wang (Chemosphere, 2023)

Soil minerals and organic matters affect ARGs transformation by changing the morphology of plasmid and bacterial responses - Hongyu Shi; Xinyi Hu; Jin Zhang; Wenxuan Li; Jiang Xu; Baolan Hu; Liping Ma; Liping Lou (Journal of Hazardous Materials, 2023)

An improved hourly-resolved atmospheric NOx emission inventory of industrial sources based on Continuous Emission Monitoring System data: Case of Jiangsu Province, China - Chu Sun; Baojie Li; Lei Chen; Yucheng Gao; Jianbing Jin; Xuan Gu; Yang Yang; Yuxiang Lou; Yongqi Zhao; Hong Liao (Journal of Cleaner Production, 2023)

Cost-efficient bathymetric mapping method based on massive active–passive remote sensing data - Tong Han; Huaguo Zhang; Wenting Cao; Chengfeng Le; Chen Wang; Xinke Yang; Yunhan Ma; Dongling Li; Juan Wang; Xiulin Lou (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Aroma characteristics of volatile compounds brought by variations in microbes in winemaking - Shuxun Liu; Ying Lou; Yixian Li; Yan Zhao; Oskar Laaksonen; Ping Li; Jiaojiao Zhang; Maurizio Battino; Baoru Yang; Qing Gu (Food Chemistry, 2023)

Microplastics cause reproductive toxicity in male mice through inducing apoptosis of spermatogenic cells via p53 signaling - Chunsheng Lu; Yuehui Liang; Ya Cheng; Chan Peng; Yuanyuan Sun; Kangle Liu; Yingqing Li; Yixia Lou; Xiao Jiang; Aihua Zhang; Jinyi Liu; Jia Cao; et al. (Food and Chemical Toxicology, 2023)

Prestress loss of twisted wire strands and parallel wire strands at elevated temperatures - Guo-biao Lou; Jing Hou; Hong-hui Qi; Fang-xin Li; Zhan-hui Song; Guo-qiang Li (Engineering Structures, 2023)

Chitosan-based antibacterial microspheres loaded multifunctional Janus composite membranes with unidirectional biofluid transport, antioxidant and pH-responsive monitoring - Ting-Ting Li; Li Sun; Ying Zhang; Bing-Chiuan Shiu; Hai-Tao Ren; Hao-Kai Peng; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2023)

Phosphorus recovery and resource utilization from phosphogypsum leachate via membrane-triggered adsorption and struvite crystallization approach - Xinping Hu; Jingfu Wang; Fengxue Wu; Danhao Li; Jiaojiao Yang; Jingan Chen; Jiaxin Liang; Xiangyang Lou; Hong Chen (Chemical Engineering Journal, 2023)

Millettia speciosa Champ cellulose-based hydrogel as a novel delivery system for Lactobacillus paracasei: Its relationship to structure, encapsulation and controlled release - Meng-Fan Li; Hua-Ling Cui; Wen-Yong Lou (Carbohydrate Polymers, 2023)

Thermal-mechanical coupled XFEM simulation of low temperature cracking behavior in asphalt concrete waterproofing layer - Liangwei Lou; Xin Xiao; Jin Li; Feipeng Xiao (Cold Regions Science and Technology, 2023)

Co-immobilization of β-xylosidase and endoxylanase on zirconium based metal–organic frameworks for improving xylosidase activity at high temperature and in acetone - Na Li; Huan Xia; Yanbin Jiang; Jun Xiong; Wenyong Lou (Bioresource Technology, 2023)

Urban agglomeration waterlogging hazard exposure assessment based on an integrated Naive Bayes classifier and complex network analysis - Mo Wang; Xiaoping Fu; Dongqing Zhang; Siwei Lou; Jianjun Li; Furong Chen; Shan Li; Soon Keat Tan (Natural Hazards, 2023)

Assessment of eutrophication from Xiaoqing River estuary to Laizhou Bay: Further warning of ecosystem degradation in typically polluted estuary - Feifei Zhang; Hongrui Fu; Huawei Lou; Xiaojun Sun; Dong Zhang; Peiyan Sun; Xinping Wang; Yiming Li; Jinren Lu; Mutai Bao (Marine Pollution Bulletin, 2023)

Pallamins A–C, ent-labdane and pallavicinin based dimers from the Chinese liverwort Pallavicinia ambigua (mitt.) stephani - Yi Li; Xiao-Bin Li; Jin-Chuan Zhou; Ze-Jun Xu; Ming-Zhu Zhu; Yan Zong; Jiao-Zhen Zhang; Jing-Jing Han; Ya-Jie Tang; Hong-Xiang Lou (Phytochemistry, 2023)

Experimental study of emission characteristics and performance of SCR coated on DPF with different catalyst washcoat loadings - Pi-qiang Tan; Ying-jie Chen; Zi-tong Wang; Li-shuang Duan; Yang Liu; Di-ming Lou; Zhi-yuan Hu; Yun-hua Zhang (Fuel, 2023)

Blue/red dual emission based ratiometric fluorescent intelligent labels for real-time food freshness monitoring - Shuo Yang; Jiang Lou; Limin Jing; Qijun Ding; Xia Li; Yifei Jiang; Zhuqing Liu; Wenjia Han (Food Control, 2023)

Hexavalent chromium [Cr(VI)]-induced ribosomal DNA copy number variation and DNA damage responses and their associations with nucleolar protein HRAS in humans and cells - Huadong Xu; Li Shi; Lingfang Feng; Fan Wu; Junfei Chen; Yao Qin; Xiaowen Dong; Zhaoqiang Jiang; Yongxin Li; Hailing Xia; Jianlin Lou (Environmental Pollution, 2023)

Deduction of carbon footprint for membrane desalination processes towards carbon neutrality: A case study on electrodeionization for ultrapure water preparation - Yuan Yuan; Jiaqi Lu; Dungang Gu; Yuhang Lou; Na Xue; Guanghui Li; Wenjie Liao; Nan Zhang (Desalination, 2023)

Highly robust and sensitive dual-network freeze-resistant organic hydrogel thermocells - Yudong Zong; Luzheng Chen; Xia Li; Qijun Ding; Wenjia Han; Jiang Lou (Carbohydrate Polymers, 2023)

Preparation of bio-jet fuels by a controllable integration process: Coupling of biomass fermentation and olefin polymerization - Yuehui Luo; Rui Zhang; Yuting He; DanFeng Lou; Rui Zhu; Can Zhu; Minghui Fan; Quanxin Li (Bioresource Technology, 2023)

Observation of nitrogen oxide-influenced chlorine chemistry and source analysis of Cl2 in the Yangtze River Delta, China - Fangbing Li; Dan Dan Huang; Wei Nie; Yee Jun Tham; Shengrong Lou; Yuanyuan Li; Linhui Tian; Yuliang Liu; Min Zhou; Haichao Wang; Liping Qiao; Hongli Wang; et al. (Atmospheric Environment, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Identifying interactions of linked irrigated lake-groundwater system by combining hydrodynamic and hydrochemical method - MuRong Li; Jianmin Bian; Yu Wang; Xinying Cui; Yuanfang Ding; Xiaoqing Sun; Fan Wang; Yuqi Lou (Environmental Science and Pollution Research, 2023)

Big-sized trees and higher species diversity improve water holding capacities of forests in northeast China - Yanbo Yang; Lixin Jing; Qi Li; Chentao Liang; Quanxing Dong; Shuting Zhao; Yuwen Chen; Danqi She; Xu Zhang; Lei Wang; Guanchao Cheng; Xiting Zhang; et al. (Science of The Total Environment, 2023)

Configuration optimization of driving devices in a steam and power system for carbon emission reduction - Jie Zhang; Dungang Gu; Yuhang Lou; Jiaqi Lu; Guanghui Li; Pinhua Rao; Nan Zhang (Journal of Cleaner Production, 2023)

Effects of a long-term operation wetland for wastewater treatment on the spatial pattern and function of microbial communities in groundwater - Rongwei Xiong; Yong Li; Xiufang Gao; Na Li; Ruitao Lou; Laraib Saeed; Jinquan Huang (Environmental Research, 2023)

Vegetation carbon input moderates the effects of climate change on topsoil organic carbon in China - Yunfeng Cen; Yongcai Lou; Zhaoliang Gao; Wenbo Liu; Xun Zhang; Guanfang Sun; Yonghong Li (CATENA, 2023)

Long-Term Trajectory Prediction for Oil Tankers via Grid-Based Clustering - Xuhang Xu; Chunshan Liu; Jianghui Li; Yongchun Miao; Lou Zhao (Journal of Marine Science and Engineering, 2023)
Vessel trajectory prediction is an important step in route planning, which could help improve the efficiency of maritime transportation. In this article, a high-accuracy long-term trajectory prediction algorithm is proposed for oil tankers. The proposed algorithm extracts a set of waymark points that are representative of the key traveling patterns in an area of interest by applying DBSCAN clustering to historical AIS data. A novel path-finding algorithm is then developed to sequentially identify a subset of waymark points, from which the predicted trajectory to a fixed destination is produced. The proposed algorithm is tested using real data offered by the Danish Maritime Authority. Numerical results demonstrate that the proposed algorithm outperforms state-of-the-art vessel trajectory prediction algorithms and is able to make high-accuracy long-term trajectory predictions.

The metabolism and dissipation behavior of tolfenpyrad in tea: A comprehensive risk assessment from field to cup - Zihan Wang; Fengjian Luo; Mingming Guo; Jiawei Yu; Li Zhou; Xinzhong Zhang; Hezhi Sun; Mei Yang; Zhengyun Lou; Zongmao Chen; Xinru Wang (Science of The Total Environment, 2023)

New evidence of the Hoyle-like structure in 16O - Jiahao Chen; Yanlin Ye; Kai Ma; Jiaxing Han; Dongxi Wang; Chengjian Lin; Huiming Jia; Lei Yang; Gen Li; Lisheng Yang; Ziyao Hu; Zhiwei Tan; et al. (Science Bulletin, 2023)

Wheat PHT1;9 acts as one candidate arsenate absorption transporter for phytoremediation - Pengfei Wang; Zedong Chen; Yanjun Meng; Huanting Shi; Chuang Lou; Xu Zheng; Gezi Li; Xiangnan Li; Wanxi Peng; Guozhang Kang (Journal of Hazardous Materials, 2023)

New insight into desorption behavior and mechanism of oil from aged oil-contaminated soil in microemulsion - Xiaoning Feng; Shuhai Guo; Fushan Wen; Wei Zhu; Xiujie Yang; Meixia Gu; Nan Shi; Zhiheng Li; Bin Lou; Dong Liu (Journal of Hazardous Materials, 2023)

Edible fungi efficiently degrade aflatoxin B1 in cereals and improve their nutritional composition by solid-state fermentation - Haiwei Lou; Chuangming Yang; Ying Gong; Yang Li; Yonghui Li; Shuangqi Tian; Yu Zhao; Renyong Zhao (Journal of Hazardous Materials, 2023)

Effects of Fe(II) and organic carbon on nitrate reduction in surficial sediments of a large shallow freshwater lake - Na Li; Yong Li; Ruitao Lou; Hong Xu; Laraib Saeed (Journal of Environmental Management, 2023)

Effects of high-voltage electrostatic field (HVEF) on frozen shrimp (Solenocera melantho) based on UPLC-MS untargeted metabolism - Jiao Liu; Feixia Zhu; Jing Yang; Yue Wang; Xiaohan Ma; Yongjiang Lou; Yongyong Li (Food Chemistry, 2023)

Preparation and study of bark-like MXene based high output power hydroelectric generator - Xiaoyang Zhang; Yanting Wang; Xuefei Zhang; Ching-Wen Lou; Jia-Horng Lin; Ting-Ting Li (Chemical Engineering Journal, 2023)

Analytical Solutions for the Characteristic Size Distribution of the Elliptical Model in Fractured Rock Mass - Kun Xiao; Ru Zhang; Jing Xie; Li Ren; Mingzhong Gao; Zetian Zhang; Chendi Lou; Ting Ai; Ersheng Zha (Rock Mechanics and Rock Engineering, 2023)

3D Pore-Throat Microstructure Complexity of Igneous Reservoir Rock and its Effects on the Porosity–Permeability Relation - Mutian Qin; Shuyun Xie; Hongjun Li; Da Lou; Tianfu Zhang; Emmanuel John M. Carranza; Zhiwei Kuang (Natural Resources Research, 2023)

The diagnostic potential of a circRNA–miRNA network in non-small cell lung cancer - Xinyi Ma; Chengtao Lou; Junjie Pan; Chengwei Zhou; Xiaodong Zhao; Nan Li; Haihua Tian; Xiaodan Meng (Journal of Molecular Medicine, 2023)

Research on Feature Extraction of Ship-Radiated Noise Based on Multiscale Fuzzy Dispersion Entropy - Yuxing Li; Yilan Lou; Lili Liang; Shuai Zhang (Journal of Marine Science and Engineering, 2023)
In recent years, fuzzy dispersion entropy (FDE) has been proposed and used in the feature extraction of various types of signals. However, FDE can only analyze a signal from a single time scale during practical application and ignores some important information. In order to overcome this drawback, on the basis of FDE, this paper introduces the concept of multiscale process and proposes multiscale FDE (MFDE), based on which an MFDE-based feature extraction method for ship-radiated noise is proposed. The experimental results of the simulated signals show that MFDE can reflect the changes in signal complexity, frequency, and amplitude, which can be applied in signal feature extraction; in addition, the measured experimental results demonstrate that the MFDE-based feature extraction method has a better feature extraction effect on ship-radiated noise, and the highest recognition rate is 99.5%, which is an improvement of 31.9% compared to the recognition rate of a single time scale. All the results show that MFDE can be better applied to the feature extraction and identification classification of ship-radiated noise.

Bifunctional collagen fiber/carbon quantum dot fluorescent adsorbent for efficient adsorption and detection of Pb2+ - Limin Jing; Qijun Ding; Xia Li; Jiang Lou; Zhuqing Liu; Yifei Jiang; Wenjia Han; Zheng Cheng (Science of The Total Environment, 2023)

Whether the enhanced terrestrial vegetation carbon sink affect the water resources in the middle-low latitude karst areas of China? - Hezhen Lou; Shengtian Yang; Xuewei Shi; Jun Zhang; Zihao Pan; Chaojun Li; Yujia Zhang; Baichi Zhou; Hao Li; Yuanli Shi; Yin Yi; Ya Luo (Journal of Hydrology, 2023)

River discharge recovery lag in the small and medium-sized rivers occurred in response to climate change and human activities - Hezhen Lou; Hao Li; Shengtian Yang; Xuelei Wang; Zihao Pan; Yujia Zhang; Baichi Zhou; Jun Zhang (Journal of Hydrology, 2023)

Epistatic interaction between CsCEN and CsSHBY in regulating indeterminate/determinate growth of lateral branch in cucumber - Fan Yang; Martin Kagiki Njogu; Obel Hesbon; Yuhui Wang; Qunfeng Lou; Chunyan Cheng; Junguo Zhou; Ji Li; Jinfeng Chen (Theoretical and Applied Genetics, 2023)

Accumulation of Intracellular Ferrous Iron in Inflammatory-Activated Macrophages - Huijuan Ma; Qi Shu; Dan Li; Tingqian Wang; Linyi Li; Xiaodong Song; Kaiyan Lou; Huan Xu (Biological Trace Element Research, 2023)

Improving agricultural robot patch-spraying accuracy and precision through combined error adjustment - Hailong Li; Longzhe Quan; Yinghao Guo; Pengfei Pi; Yihui Shi; Zhaoxia Lou; Wei Jiang; Fulin Xia; Deng Sun; Yunhuan Yang; Wenchao Xu; Qian Chen (Computers and Electronics in Agriculture, 2023)

Carbon footprint analysis and carbon neutrality potential of desalination by electrodialysis for different applications - Na Xue; Jiaqi Lu; Dungang Gu; Yuhang Lou; Yuan Yuan; Guanghui Li; Shogo Kumagai; Yuko Saito; Toshiaki Yoshioka; Nan Zhang (Water Research, 2023)

GEE can prominently reduce uncertainties from input data and parameters of the remote sensing-driven distributed hydrological model - Zihao Pan; Shengtian Yang; Xiaoyu Ren; Hezhen Lou; Baichi Zhou; Huaixing Wang; Yujia Zhang; Hao Li; Jiekang Li; Yunmeng Dai (Science of The Total Environment, 2023)

Insight into tetrahydrofuran lignans from Isatis indigotica fortune with neuroprotective and acetylcholinesterase inhibitor activity - Yu-Fei Xi; Ming Bai; Xin Zhang; Zi-Lin Hou; Bin Lin; Guo-Dong Yao; Li-Li Lou; Xiao-Bo Wang; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Conductive carrier promotes synchronous biofilm formation and granulation of anammox bacteria - Kun Feng; Yu Lou; Yitian Li; Baiyun Lu; Anran Fang; Guojun Xie; Chuan Chen; Defeng Xing (Journal of Hazardous Materials, 2023)

Insight into the desorption behavior of oily soil with different particle sizes based on accumulation effect and binding interaction - Xiaoning Feng; Zhiheng Li; Xiujie Yang; Bin Lou; Fushan Wen; Nan Shi; Wei Zhu; Shuhai Guo; Meixia Gu; Dong Liu (Journal of Environmental Chemical Engineering, 2023)

New approach to monitoring and characterizing the directionality of electromagnetic radiation generated from rock fractures - Menghan Wei; Dazhao Song; Xueqiu He; Quan Lou; Zhenlei Li; Liming Qiu; Shengquan He (Journal of Applied Geophysics, 2023)

Quantitative characterization of filamentous fungal promoters on a single-cell resolution to discover cryptic natural products - Peng-Lin Wei; Jie Fan; Jingwen Yu; Zihui Ma; Xian Guo; Nancy P. Keller; Erwei Li; Chunbo Lou; Wen-Bing Yin (Science China Life Sciences, 2023)

Hydrological and erosion responses of steep spoil heaps to taproot and fibrous root grasses under simulated rainfalls - Jianming Li; Li Li; Wenlong Wang; Hongliang Kang; Mingming Guo; Jinquan Huang; Yifeng Wang; Yibao Lou; Xiaoxia Tong; Huiying Nie (Journal of Hydrology, 2023)

Effect of a novel catalyst zonal coating strategy on the performance of SCR coated particulate filters - Pi-qiang Tan; Li-shuang Duan; Yang Liu; Ying-jie Chen; Di-ming Lou; Zhi-yuan Hu (Fuel, 2023)

Transcriptomic analysis reveals the inhibition mechanism of pulsed light on fungal growth and ochratoxin A biosynthesis in Aspergillus carbonarius - Yan Wang; Yong Zheng; Aiyun Zhou; Jing Neng; Di Wu; Xiao Li Shen; Xiuyu Lou; Kai Yang (Food Research International, 2023)

Ovalbumin-coated gold nanoparticles with interesting colloidal stability for colorimetric detection of carbaryl in complex media - Huimin Hao; Jian Zhu; Bin Yang; Li Peng; Shuyan Lou (Food Chemistry, 2023)

Efficient electromagnetic wave absorption and Joule heating via ultra-light carbon composite aerogels derived from bimetal-organic frameworks - Weiwei He; Jiajia Zheng; Weiping Dong; Shaohua Jiang; Gang Lou; Lin Zhang; Wenya Du; Zhaochun Li; Xiping Li; Yiming Chen (Chemical Engineering Journal, 2023)

Purinergic receptors mediate endothelial dysfunction and participate in atherosclerosis - Xian-Ming Wu; Ning Zhang; Jiang-Shan Li; Zhi-Hong Yang; Xiao-Lou Huang; Xiao-Fang Yang (Purinergic Signalling, 2023)
Atherosclerosis is the main pathological basis of cardiovascular disease and involves damage to vascular endothelial cells (ECs) that results in endothelial dysfunction (ED). The vascular endothelium is the key to maintaining blood vessel health and homeostasis. ED is a complex pathological process involving inflammation, shear stress, vascular tone, adhesion of leukocytes to ECs, and platelet aggregation. The activation of P2X4, P2X7, and P2Y2 receptors regulates vascular tone in response to shear stress, while activation of the A2A, P2X4, P2X7, P2Y1, P2Y2, P2Y6, and P2Y12 receptors promotes the secretion of inflammatory cytokines. Finally, P2X1, P2Y1, and P2Y12 receptor activation regulates platelet activity. These purinergic receptors mediate ED and participate in atherosclerosis. In short, P2X4, P2X7, P2Y1, and P2Y12 receptors are potential therapeutic targets for atherosclerosis.

Elevation of hsa-miR-7-5p level mediated by CtBP1-p300-AP1 complex targets ATXN1 to trigger NF-κB-dependent inflammation response - Li-Qiong Lou; Wen-Qiang Zhou; Xin Song; Zhi Chen (Journal of Molecular Medicine, 2023)

Enhanced degradation of emerging contaminants by percarbonate/Fe(II)-ZVI process: case study with nizatidine - Mingxin Huo; Deqiang Zou; Yingzi Lin; Yi Lou; Gen Liu; Siwen Li; Lei Chen; BaoLing Yuan; Qingyu Zhang; Ao Hou (Environmental Science and Pollution Research, 2023)

Introduction of non‐native fish for aquaculture in China: A systematic review - Bin Kang; Jean R. S. Vitule; Shan Li; Fangmin Shuai; Liangliang Huang; Xiaoxia Huang; Jinghui Fang; Xiaotao Shi; Yugui Zhu; Dongpo Xu; Yunrong Yan; Fangrui Lou (Reviews in Aquaculture, 2023)
Aquaculture, especially of non‐native species and translocated domestic species, is a greatly encouraged way of relieving the conflicts between food and economic demand and resource depletion. We herein summarized the introduction history of non‐native fish for aquacultural use in China, including 105 species introduced from abroad and 61 species translocated domestically across river basins, which has brought great economic benefits but high ecological risks. Of these, one‐fourth have successfully established wild populations in natural waters and 15% have successfully invaded. We presented specific examples of seven aquaculture species/taxa and three aquarium species/taxa to explain their outcomes. The notable economic benefits, complex species composition and strain selection of tilapias, carps and sturgeons may together facilitate their invasion, and result in fish diversity decline, genetic pollution, and loss of ecosystem service. We specifically reviewed invasion cases in lakes and reservoirs and found that lakes in western China and reservoirs made by major hydroprojects are hotspots for non‐native species, and this has led to the disappearance of endemic species and changes to the original faunal composition. The escaped non‐native fish introduced via aquaculture has changed the original fish biogeography, resulting in the loss of assemblage uniqueness and causing faunal homogeneity. China has achieved significant progress in completing the Aichi Targets by improving the legal system and strengthening conservational actions on controlling non‐native species. Further actions, especially on risk assessment and management of non‐native species are expected for a healthy outlook for the aquaculture industry of China.

Analysis on the dynamic mechanism of Acetes aggregation near a nuclear power cooling water system based on the Lagrangian flow network - Qi Lou; Xueqing Zhang; Xusheng Xiang; Fan Yu; Ying Xiong; Zhengyan Li (Frontiers in Marine Science, 2023)
The outbreak of nuclear power cooling water system (NPCS) disaster-causing organisms has become more frequent, causing huge economic losses. Therefore, it is necessary to understand the aggregation mechanism of disaster-causing organisms for the risk prevention and control of NPCS. Hence, this study applied the Lagrangian flow network (LFN) to analyze the aggregation mechanism of Acetes near NPCS, as such a complex network can describe the interconnections between massive nodes and has already been used for modeling complex nonlinear systems, revealing how the mechanisms of such novel processes emerge. In this study, the degree and probability paths in the network were used to reveal the transport pathway and aggregation area of Acetes . The experimental results highlighted that the sea area of the nuclear power plant is the key node with a large in-degree of the LFN, where the material easily accumulated. The Acetes near the NPCS mainly originated from the east along two critical paths. Overall, this study demonstrates that the LFN is a feasible approach to predicting the transport and the accumulation of the NPCS disaster-causing plankton.

Enhancing mechanical and photocatalytic properties by surface microstructure regulation of TiO2 nanofiber membranes - Xilin Liao; Hai-Tao Ren; Baolei Shen; Jia-Horng Lin; Ching-Wen Lou; Ting-Ting Li (Chemosphere, 2023)

Host's P85α genotype restructures the gut microbiota and regulates fat metabolism in gibel carp - Tengba Fan; Ivan Jakovlić; Qiyong Lou; Dong Han; Wenxiang Li; Ming Li; Hong Zou; Guitang Wang; Shangong Wu (Aquaculture, 2023)

Target-triggered double fluorescent biosensors for rapid and sensitive detection of long-chain perfluorinated compounds using DNA probe and lysozyme fiber - Jian Zhu; Bin Yang; Li Peng; Jinwei Wu; Huimin Hao; Shuyan Lou (Science of The Total Environment, 2023)

Two new terpenoids and other constituents from Salvia cavaleriei and their antibacterial activities - Yu-Min Zhao; Ke Li; Han-Fei Liu; Jin-Yu Li; Jian Fu; Hua-Yong Lou; Wei-Dong Pan (Phytochemistry Letters, 2023)

Two haplotype-resolved, gap-free genome assemblies for Actinidia latifolia and Actinidia chinensis shed light on the regulatory mechanisms of vitamin C and sucrose metabolism in kiwifruit - Xue Han; Yilin Zhang; Qiong Zhang; Ni Ma; Xiaoying Liu; Wenjing Tao; Zhiying Lou; Caihong Zhong; Xing Wang Deng; Dawei Li; Hang He (Molecular Plant, 2023)

Reconstruction of the water cycle process reveals the 600-year evolution of the human-water relationship in Tunpu, China - Shengtian Yang; Zihao Pan; Hezhen Lou; Chaojun Li; Jun Zhang; Yujia Zhang; Yin Yi; Jiyi Gong; Ya Luo; Min Zhi; Xi Li (Journal of Hydrology, 2023)

Mechanism of β-blocker biodegradation by wastewater microorganisms - Ming Yi; Jinxiu Lou; Wanlu Zhu; Dan Li; Pingfeng Yu; Huijie Lu (Journal of Hazardous Materials, 2023)

Observation-based sources evolution of non-methane hydrocarbons (NMHCs) in a megacity of China - Yarong Peng; Hongli Wang; Qian Wang; Shengao Jing; Jingyu An; Yaqin Gao; Cheng Huang; Rusha Yan; Haixia Dai; Tiantao Cheng; Qiang Zhang; Meng Li; et al. (Journal of Environmental Sciences, 2023)

Experimental investigation of transition process from LTC to ITC and HTC during diesel spray combustion at low ambient temperatures - Dongfang Wang; Jiahao Zhang; Yikai Li; Ziming Yang; Zhongjie Shi; Yue Lou (Fuel, 2023)

Experimental exploration and mechanism analysis of the deflagration pressure of methane/pulverized coal blenders inhibited by modified kaoline-containing compound inhibitors - Minggao Yu; Fengchuan Wang; Tao He; Haitao Li; Shixin Han; Rongyang Lou; Kai Zheng; Yingying Yu (Fuel, 2023)

Repaired surface structural imperfection of tin Wide-Bandgap perovskite films for photovoltaic application - Tian-Yu Teng; Fan Hu; Yan-Hui Lou; Jun-Jie Cao; Chun-Hao Chen; Yi-Ran Shi; Kai-Li Wang; Jing Chen; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2023)

Low-temperature cracking resistance of asphalt concretes for railway substructure exposed to repeated freeze-thaw cycles - Xin Xiao; Jin Li; Degou Cai; Liangwei Lou; Yuefeng Shi; Feipeng Xiao (Cold Regions Science and Technology, 2023)

Synthesis of temperature and pH responsive lignin-grafted sulfobetaine for efficiently recycling cellulase - Feiyun Li; Yuxia Pang; Hongming Lou; Xueqing Qiu (Bioresource Technology, 2023)

Characteristics of the intestinal bacterial microbiota profiles in Bifidobacterium pseudocatenulatum LI09 pre-treated rats with D-galactosamine-induced liver injury - Hua Zha; Jiafeng Xia; Guinian Si; Ruiqi Tang; Shengjie Li; Qian Li; Yiqing Lou; Wanlong Wo; Kevin Chang; Lanjuan Li (World Journal of Microbiology and Biotechnology, 2023)

Temperature and flooding depth thresholds for early recruitment stages in a bulbous plant Bolboschoenus planiculmis - Dongjia Yu; Haoran Tang; Pangwei Li; Mengdie Zhou; Guangying Zhao; Yanjing Lou (Wetlands Ecology and Management, 2023)

Collateral-Core Ratio as a Novel Predictor of Clinical Outcomes in Acute Ischemic Stroke - Jinhao Lyu; Sa Xiao; Zhihua Meng; Xiaoyan Wu; Wen Chen; Guohua Wang; Qingliang Niu; Xin Li; Yitong Bian; Dan Han; Weiting Guo; Shuai Yang; et al. (Translational Stroke Research, 2023)

Central pattern generator network model for the alternating hind limb gait of rats based on the modified Van der Pol equation - Xiaoyan Shen; Yan Wu; Xiongjie Lou; Zhiling Li; Lei Ma; Xiongheng Bian (Medical & Biological Engineering & Computing, 2023)

CircCAMTA1 facilitates atrial fibrosis by regulating the miR-214-3p/TGFBR1 axis in atrial fibrillation - Li Zhang; Qi Lou; Wei Zhang; Wen Yang; Luyifei Li; Hongyan Zhao; Yihui Kong; Weimin Li (Journal of Molecular Histology, 2023)

Association Between Serum Neurofilament Light Chain and Neurochemistry Deficits in Patients with Spinocerebellar Ataxia Type 3 - Yuchao Chen; Yi Jin; Zhouyao Hu; Mengqiu Qiu; Dan Li; Qiusi Cai; Chenjuan Tao; Danning Lou; Le Qi; Sidan Chen; Hao Yu; Zhongming Gao (The Cerebellum, 2023)

Establishment of the first cell line from the small yellow croaker (Larimichthys polyactis) and its application in unraveling the mechanism of ROS-induced apoptosis under hypoxia - Jingqian Wang; Xinming Gao; Li Wang; Chen Du; Congcong Hou; Feng Liu; Qingping Xie; Bao Lou; Shan Jin; Junquan Zhu (Aquaculture, 2023)

Alterations of gut and oral microbiota in the individuals consuming take-away food in disposable plastic containers - Hua Zha; Jiawen Lv; Yiqing Lou; Wanlong Wo; Jiafeng Xia; Shengjie Li; Aoxiang Zhuge; Ruiqi Tang; Nian Si; Zhihao Hu; Haifeng Lu; Kevin Chang; et al. (Journal of Hazardous Materials, 2023)

Numerical evaluation of the influence of initial pressure/temperature on the explosion properties and soot formation of methane/coal volatiles mixtures - Minggao Yu; Shanshan Li; Haitao Li; Shixin Han; Fengchuan Wang; Rongyang Lou; Kai Zheng; Yingying Yu (Fuel, 2023)

Seismic behaviour of a self-centring steel connection with replaceable energy-dissipation components - Ting Lou; Wei Wang; Junlin Li (Engineering Structures, 2023)

A biomass-based bilayer aerogel for efficient solar-driven steam production and electricity generation - Lingxuan Bai; Hanxiao Zhang; Rui Lou; Jianzong Li; Mingchao Chi; Jiulong Sha; Xuelian Zhou (Chemical Engineering Journal, 2023)

Isomeric effect of meta and para Indolocarbazole-based hole transporting materials on the performance of inverted perovskite solar cells - Li Wan; Yang Zhao; Yulin Tan; Lingyun Lou; Zhong-Sheng Wang (Chemical Engineering Journal, 2023)

Sputter-deposited nickel nanoparticles on Kevlar fabrics with laser-induced graphene for efficient solar evaporation - Shuaihang Zhu; Zhiwei Lei; Yuejie Dou; Ching-Wen Lou; Jia-Horng Lin; Jiwei Li (Chemical Engineering Journal, 2023)

Novel ionic complex with flame retardancy and ultrastrong toughening effect on epoxy resin - Gaobo Lou; Qingqing Rao; Qing Li; Zhicheng Bai; Xingwei He; Youhua Xiao; Jinfeng Dai; Shenyuan Fu; Shengxiang Yang (Chemical Engineering Journal, 2023)

Screening Hoffman-type metal organic frameworks for efficient C2H2/CO2 separation - Wushuang Lou; Jiahao Li; Wanqi Sun; Yongqi Hu; Lingyao Wang; Rodrigo F. Neumann; Mathias Steiner; Zonglin Gu; Binquan Luan; Yuanbin Zhang (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Photo-induced conversion of type-II CoPc/BiOBr-NSs to S-scheme heterostructure for boosting CO2 photoreduction - Wenxuan Li; Xiaochi Li; Xionghui Fu; Zaizhu Lou; Yi Zhu; Yuanming Zhang (Chemical Engineering Journal, 2023)

Efficient ultraviolet–visible-near infrared self-powered photodetector based on hexagonal YMnO3-based ferroelectric thin film by multiscale polarity structure optimization - Mengwei Tian; Xiangjun Liu; Ao Gong; Shan Zhang; Guangcheng Wang; Pei Han; Yong Li; Xiaojie Lou; Xihong Hao (Chemical Engineering Journal, 2023)

Spatiotemporal accuracy evaluation and errors analysis of global VTEC maps using a simulation technique - Jian Lin; Xinxing Li; Shenfeng Gu; Yidong Lou; Qing Yun (GPS Solutions, 2023)

N2O emissions from soils under short-term straw return in a wheat-corn rotation system are associated with changes in the abundance of functional microbes - Jitong Lin; Zhiyu Xu; Yinghao Xue; Renhua Sun; Rongguang Yang; Xiaoxu Cao; Hui Li; Qi Shao; Yanhong Lou; Hui Wang; Quangang Yang; Hong Pan; et al. (Agriculture, Ecosystems & Environment, 2023)

The prenatal weekly temperature exposure and neonatal congenital heart disease: a large population-based observational study in China - Weize Xu; Die Li; Zehua Shao; Yanqin You; Feixia Pan; Hongliang Lou; Jing Li; Yueqin Jin; Ting Wu; Lulu Pan; Jing An; Junqiu Xu; et al. (Environmental Science and Pollution Research, 2022)

The CRISPR-Cas system as a tool for diagnosing and treating infectious diseases - Juan Lou; Bin Wang; Junwei Li; Peng Ni; Yuefei Jin; Shuaiyin Chen; Yuanlin Xi; Rongguang Zhang; Guangcai Duan (Molecular Biology Reports, 2022)

Lagrangian analysis of material transport around the headland in the Yellow River Estuary - Qi Lou; Zhengyan Li; Xueqing Zhang; Xusheng Xiang; Zhendong Cao (Frontiers in Marine Science, 2022)
Material transport around the headland has received more attention. To reveal the material transport pattern and its response to the topography in the Yellow River Estuary (YRE), in this paper, three Lagrangian analysis methods, including Lagrangian residual current, particle tracking model, and Lagrangian coherent structures (LCSs), are used to analyze the material horizontal transport near the headland in the YRE. The results of the study show that the headland plays an important role in the hydrodynamic processes and material transport in the YRE. Due to the current shear induced by the topography, materials easily diffuse, forming a front around the headland. Due to the blocking and shading effects of the headland, the materials tend to accumulate on the right side of the headland (facing the sea). The above three Lagrangian methods can describe the characteristics of the material distribution, but the LCS method is superior in comparison. Due to their more stable spatial structure, LCSs can be used to analyze the transport of pollutants, larvae, microplastics, etc. in the YRE.

Effects of Electron Beam Irradiation on Portunus trituberculatus Based on Tandem-Mass Tag-Based Quantitative Proteomic Analysis - Huijuan Pan; Qi Yu; Chenru Qian; Haitao Shao; Yongyong Li; Yongjiang Lou (Journal of Aquatic Food Product Technology, 2022)

U-net Models Based on Computed Tomography Perfusion Predict Tissue Outcome in Patients with Different Reperfusion Patterns - Yaode He; Zhongyu Luo; Ying Zhou; Rui Xue; Jiaping Li; Haitao Hu; Shenqiang Yan; Zhicai Chen; Jianan Wang; Min Lou (Translational Stroke Research, 2022)

Real-time precise orbit and clock estimation of multi-GNSS satellites with undifferenced ambiguity resolution - Xiaolei Dai; Xiaopeng Gong; Chenglong Li; Yun Qing; Shengfeng Gu; Yidong Lou (Journal of Geodesy, 2022)

The Derivation of Nutrient Criteria for the Adjacent Waters of Yellow River Estuary in China - Qi Lou; Xueqing Zhang; Bei Zhao; Jing Cao; Zhengyan Li (Journal of Ocean University of China, 2022)

Real-time precise point positioning based on BDS-3 global short message communication - Shengfeng Gu; Rongxin Guo; Xiaopeng Gong; Shuangcheng Zhang; Yidong Lou; Zhenhong Li (GPS Solutions, 2022)

Meshless Surface Wind Speed Field Reconstruction Based on Machine Learning - Nian Liu; Zhongwei Yan; Xuan Tong; Jiang Jiang; Haochen Li; Jiangjiang Xia; Xiao Lou; Rui Ren; Yi Fang (Advances in Atmospheric Sciences, 2022)

Rapid detection of neutralising acid adulterants in raw milk using a milk component analyser and chemometrics - Huaixiang Tian; Bin Chen; Hongbin Yu; Xinman Lou; Yong Li; Haiyan Yu; Liqiong Chen; Chen Chen (Food Additives & Contaminants: Part A, 2022)

Experimental investigation on the effects of DPF Cs-V-based non-precious metal catalysts and their coating forms on non-road diesel engine emission characteristics - Boyang Qi; Zhenguo Li; Diming Lou; Yunhua Zhang (Environmental Science and Pollution Research, 2022)

Reconstruction of large complex sand-wave bathymetry with adaptive partitioning combining satellite imagery and sparse multi-beam data - Huaguo Zhang; Juan Wang; Dongling Li; Bin Fu; Xiulin Lou; Ziyin Wu (Journal of Oceanology and Limnology, 2022)

Administration of mesenchymal stem cells in diabetic kidney disease: mechanisms, signaling pathways, and preclinical evidence - Yuexin Zhu; Manyu Luo; Xue Bai; Yan Lou; Ping Nie; Shan Jiang; Jicui Li; Bing Li; Ping Luo (Molecular and Cellular Biochemistry, 2022)

Preventive effects of arctigenin from Arctium lappa L against LPS-induced neuroinflammation and cognitive impairments in mice - Quan Yuan; Yiran Wu; Gang Wang; Xiang Zhou; Xiaohui Dong; Zihan Lou; Sanqiang Li; Dongmei Wang (Metabolic Brain Disease, 2022)

Polystyrene microplastics alter bioaccumulation, and physiological and histopathological toxicities of cadmium in the polychaete Perinereis aibuhitensis - Yi Cong; Yadi Lou; Huan Zhao; Zhaochuan Li; Mingxing Zhang; Fei Jin; Ying Wang; Juying Wang (Frontiers in Marine Science, 2022)
Heavy metal (HM) pollution in the marine environment has been of concern for decades. The potential impact of HMs carried by emerging marine pollutants such as microplastics (MPs) has attracted attention only in recent years. In this study, we investigated the single and combined chronic toxic effects (growth, burrowing behavior, and histopathology) of cadmium (Cd, three concentrations of low, medium, and high) and polystyrene (PS) microspheres (1 μm, 10 μg/L) on the coastal polychaete Perinereis aibuhitensis . Cd bioaccumulation under two exposure scenarios was also explored. Our results showed that Cd and PS did not affect worm growth for single or combined exposure, while 13.08 μg/L of Cd (Cd L ) alone significantly decreased the burrowing time of P. aibuhitensis in sediment. The presence of PS mitigated the hormetic effect of Cd on worm burrowing behavior, and this influence was Cd concentration-related. Cd body burdens in worms exposed to the medium and high Cd concentrations (Cd M and Cd H ) were significantly greater than those of control worms with or without the presence of PS. In addition, Cd bioaccumulation was significantly higher with the coexistence of PS than those of Cd alone at the Cd L and Cd M groups. Histopathological analyses demonstrated a trend of epidermal and intestinal damages for single Cd/PS and their combined groups, and the contribution of PS-MPs should not be ignored. Our results indicate that the toxic effects and bioaccumulation pattern of Cd could be altered with the presence of PS-MPs for P. aibuhitensis , especially at environmentally relevant concentrations.

Differentiation and Temperature Adaptation of Pampus Echinogaster Based on Genome-Wide SNPs - Yuan Li; Fangrui Lou; Shigang Liu; Hai Li; Jiali Xiang; Binbin Shan; Longshan Lin; Xuan Zhuang (Frontiers in Marine Science, 2022)
Climate change and overfishing have led to the degradation of the quality and stock of Pampus echinogaster. Exploring the genetic structure and local adaptive evolutionary mechanisms of P. echinogaster is crucial for the management of this species. This population genomic study of nine geographical populations of P. echinogaster in China was conducted by specific-locus amplified fragment sequencing (SLAF-seq). A total of 935,215 SLAF tags were obtained, and the average sequencing depth of the SLAF tags was 20.80×. After filtering, a total of 46,187 high-consistency genome-wide single nucleotide polymorphisms (SNPs) were detected. Based on all SNPs, the population size of the nine P. echinogaster geographical populations was large. The Shantou population had the lowest genetic diversity, and the Tianjin population had the highest. Moreover, the population genetic structure based on all SNPs revealed significant gene exchange and no significant genetic differentiation among the nine P. echinogaster geographical populations, probably because of the population expansion after the last glacial period, the lack of balance between migration and genetic drift, and the long-distance diffusion of eggs and larvae. We suspect that variation of material metabolism, ion transfer, breeding, stress response, and inflammatory reactions-related genes were critical for adaptation to spatially heterogeneous temperature selection in natural P. echinogaster populations.

Role of jasmonate signaling in rice resistance to the leaf folder Cnaphalocrocis medinalis - Yunqi Zhuang; Xinjue Wang; Lucas Cortés Llorca; Jing Lu; Yonggen Lou; Ran Li (Plant Molecular Biology, 2022)

Neuropeptide FF-related gene in fish (Larimichthys polyactis): identification, characterization, and potential anti-inflammatory function - Ran Xiao; Zuting Guo; Li-bing Zheng; Wei Huang; Chang-feng Chi; Bao Lou (Molecular Biology Reports, 2022)

Effects of pre-oxidation by ozone, permanganate and ferrate on generation and toxicities of disinfection byproducts - Y. Lin; Y. Lou; A. Li; Y. Wei; H. Li; M. Zhou; Y. Li (International Journal of Environmental Science and Technology, 2022)

Corrigendum: The Identification of Fish Eggs From Four Economically Important Species in Guanghai Bay (China) - Yan-Jing Zheng; Xiao-Juan Peng; Wei-Xu Cai; Quan-Sheng Lou; Xiang-Li Lyu; Ying-Hua Huang (Frontiers in Marine Science, 2022)

The Impact of Urban Expansion on Plant Diversity Change in Karst Regions of Southwest China - Shengtian Yang; Chaojun Li; Hezhen Lou; Ya Luo; Pengfei Wang; Jun Zhang; Xi Li; Xijin Wu (Chinese Geographical Science, 2022)

The Identification of Fish Eggs From Four Economically Important Species in Guanghai Bay (China) - Yan-Jing Zheng; Xiao-Juan Peng; Wei-Xu Cai; Quan-Sheng Lou; Xiang-Li Lyu; Ying-Hua Huang (Frontiers in Marine Science, 2022)
By far, very few studies have dealt with the ichthyoplankton diversity in Guanghai Bay (China), which is a potential spawning ground for many important fish species. In this study, fish eggs collected in Guanghai Bay were identified through molecular method combined with visual taxonomic method. We employed two mitochondrial gene regions of cytochrome c oxidase subunit I (COI) and 16S ribosomal RNA (16S rRNA) as genetic markers for species identification. Through sequence identification at NCBI, 121 eggs with overlapping size range and easy to be confused were discriminated as four economically important species: seven as silver sillago Sillago sihama , 48 as black-banded sillago Sillago nigrofasciata , 38 as yellow drum Nibea albiflora , and 28 as Pacific seabream Acanthopagrus pacificus . Phylogenetic analyses showed that these 121 eggs clustered in four groups with strong support. To testify the validity of these identification results, species identification through five BarcodingR package methods was also carried out using sequences of 33 fish specimens as a reference library covering four target species. Finally, a highly consensus of species assignment results was achieved across different methods. Morphological characteristics and detailed photographs for eggs from these four species were supplied here. Eggs of each species are pelagic, round, have a smooth chorion and one single oil globule. Embryonic pigment patterns vary as eggs develop and can be used for species distinguishing. Eggs from S. nigrofasciata and A. pacificus were described for the first time in this study. One simple and accurate method for identifying N. albiflora eggs was additionally provided. Moreover, the morphological differences between two Sillago eggs offered supportive evidence for the recent separation of S. nigrofasciata as a new species from S. sihama . All these results would be critical for the discrimination of eggs from these four species and the estimation for their spawning areas. Meanwhile, our study would contribute to the stock assessment and fishery management in Guanghai Bay.

Erratum to: Impact of typhoon Lekima (2019) on material transport in Laizhou Bay using Lagrangian coherent structures - Qi Lou; Zhengyan Li; Yanwei Zhang; Yilei Feng; Xueqing Zhang (Journal of Oceanology and Limnology, 2022)

Impact of typhoon Lekima (2019) on material transport in Laizhou Bay using Lagrangian coherent structures - Qi Lou; Zhengyan Li; Yanwei Zhang; Yilei Feng; Xueqing Zhang (Journal of Oceanology and Limnology, 2022)

Surge Response Analysis of the Serbuoys-TLP Tension Leg Platform under the Action of Wave–Current Coupling - Zhe Ma; Zhehan Lou; Gangjun Zhai; Jiakang Li (Journal of Marine Science and Engineering, 2022)
A new type of tension leg platform (TLP) connected to a series of buoys (Serbuoys-TLP) has been proven to effectively suppress the surge response of the platform during wave conditions. However, in the complex marine environment, it is more relevant to study its motion response to the action of waves and currents. Considering the tension tendon as a lumped mass model, a DUTMST 2.0 time-domain simulation program was written, based on MATLAB, which can accurately calculate the surge response of the Serbuoys-TLP under wave–current coupling conditions. The suppression efficiency of the Serbuoys-TLP on the surge response was analyzed under different current velocities and wave parameters, and the results showed that the suppression efficiency by the Serbuoys-TLP of surges was higher under the action of waves and currents compared with the action of waves. In addition, the surge response of the platform under the two conditions of wave–current combination and wave–current coupling was also investigated, where wave–current coupling considers the effect of the current’s velocity on the wave period, while the wave–current combination does not consider it, which means that the wave and current are linearly superimposed. The results show that the surge response of the platform will be overestimated without considering the coupling effect of waves and currents. The effect of wave–current coupling has a greater impact on the surge response of the Serbuoys-TLP than that of conventional TLP. Therefore, in the design of new floating structures, the motion performance in response to the effect of wave–current coupling should be paid full attention.

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Variation in precipitation over Songhua River Basin and its relationship with north Tropical Atlantic sea surface temperature anomalies during boreal spring - Chen Chen; Yongsheng Li; Dejun Lou; Xianwei Zhou; Lihong Bao (Theoretical and Applied Climatology, 2022)

Soil phosphorus availability and stoichiometry determine microbial activity and functional diversity of fluvo-aquic soils under long-term fertilization regimes - Wei He; Wenhua Ye; Mingjie Sun; Yaping Li; Manman Chen; Meng Wei; Guoqing Hu; Quangang Yang; Hong Pan; Yanhong Lou; Hui Wang; Yuping Zhuge (Journal of Soils and Sediments, 2022)

A genetic-based population PK/PD modeling of methadone in Chinese opiate dependence patients - Dong Guo; Zhirong Tan; Xiaoya Lou; Shan Shi; Yan Shu; Honghao Zhou; Li Yu; Hong Yang (European Journal of Clinical Pharmacology, 2022)

New sesquiterpeniod esters form Blumea balsamifera (L.) DC. and their anti-influenza virus activity - Yan Xiong; Ping Yi; Yuhuan Li; Rongmei Gao; Junlei Chen; Zhanxing Hu; Huayong Lou; Caixia Du; Jiayu Zhang; Yu Zhang; Chunmao Yuan; Liejun Huang; et al. (Natural Product Research, 2022)

Temporal Stability Analysis for the Evaluation of Spatial and Temporal Patterns of Surface Water Quality - Xiaobin Zhang; Ligang Ma; Yihang Zhu; Weidong Lou; Baoliang Xie; Li Sheng; Hao Hu; Kefeng Zheng; Qing Gu (Water Resources Management, 2022)

Impacts of River Discharge on the Sea Temperature in Changjiang Estuary and Its Adjacent Sea - Hui Shen; Ye Zhu; Zhiguo He; Li Li; Yingzhong Lou (Journal of Marine Science and Engineering, 2022)
Freshwater plume at the Changjiang River (CR) mouth are essential to the coastal water quality and ecosystem because they can cause estuary stratification and hypoxia, potentially deteriorating the water environment. Furthermore, the advection heat transport is modulated by increasing anthropogenic effects. A comprehensive understanding of the influence of river discharge on the three-dimensional sea temperature, fronts and thermal stratification in the CR estuary remains lacking. A well-calibrated numerical model using Regional Ocean Modeling Systems (ROMS) is used to investigate the impacts of CR discharge on the sea temperature in coastal zones. Model results show that the amplitude and spatial distribution of the heating or cooling rate can be influenced by CR freshwater, especially in frontal areas. Specifically, the large runoff flow will reduce the heating or cooling rate in shallow waters ( 20 m). Generally, the effect of the freshwater discharge on the upper layer is greater than on the bottom layer, and the runoff has a positive correlation to the intensity of the frontal zones in the CR estuary, though this relationship is weakened in autumn because of the weak intensity of the frontal zone. Note that seawater thermal stratification and its seasonal variation can be regulated by runoff; thermal stratification will be strengthened in abundant runoff conditions and weakened in scarce runoff conditions.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Neural Network Non-Singular Terminal Sliding Mode Control for Target Tracking of Underactuated Underwater Robots with Prescribed Performance - Liwei Guo; Weidong Liu; Le Li; Yichao Lou; Xinliang Wang; Zhi Liu (Journal of Marine Science and Engineering, 2022)
This paper proposes a neural network-based nonsingular terminal sliding mode controller with prescribed performances for the target tracking problem of underactuated underwater robots. Firstly, the mathematical formulation of the target tracking problem is presented with an underactuated underwater robot model and the corresponding control objectives. Then, the target tracking errors from the line-of-sight guidance law are transformed using the prescribed performance technique to achieve good dynamic performance and steady-state performance that meet the pre-set conditions. Meanwhile, considering the model’s uncertainties and the external disturbances to the underwater robots, a target tracking controller is proposed based on the radial basis function (RBF) neural network and the non-singular terminal sliding mode control. Lyapunov stability analysis and homogeneity theory prove the tracking errors can converge on a small region that contains the origin with prescribed performance in finite time. In the simulation comparison, the controller proposed in this paper had better dynamic performance, steady-state performance and chattering supression. In particular, the steady-state error of the tracking error was lower, and the convergence time of the tracking error in the vertical distance was reduced by 19.1%.

Full-Length Transcriptome of the Whale Shark (Rhincodon typus) Facilitates the Genome Information - Fangrui Lou; Li Wang; Zhiyang Wang; Lei Wang; Linlin Zhao; Qingjie Zhou; Zhichuang Lu; Yongzheng Tang (Frontiers in Marine Science, 2022)
Rhincodon typus is a keystone and indicator species in marine ecosystems. Meanwhile, R. typus has been listed on the IUCN red list of vulnerable species. Here we used ONT platform to determine the full-length (FL) transcriptome of R. typus and obtained 14,930 FL transcripts. Among all FL transcripts, 14,915 transcripts were covered 11,892 genetic loci and 1,642 novel genetic loci were further found. Meanwhile, we identified 714 novel transcripts by compared FL transcripts with the R. typus genome. Based on FL transcripts, we also predicted the distribution patterns of ASs, LncRNAs, polyAs, CDSs and methylation sites on FL transcriptome of R. typus . Furthermore, a total of 31,021 (97.86%) CDSs can obtained annotation information. Overall, our work firstly provided the FL transcriptome and these sequences complete the annotated R. typus genome information. Furthermore, these information are a potential resource to study biological processes of R. typus .

Tandem Mass Tag-Based Proteomics Reveals the effect of Electron Beam Irradiation on Metabolism-Related Differentially Expressed Proteins in Solenocera melantho Postmortem - Qi Yu; Huijuan Pan; Haitao Shao; Chenru Qian; Yongyong Li; Yongjiang Lou (Journal of Aquatic Food Product Technology, 2022)

Evaluation of EpCAM-specific exosomal lncRNAs as potential diagnostic biomarkers for lung cancer using droplet digital PCR - Xintong Shen; Yifeng Yang; Yinfeng Chen; Chengwei Zhou; Xiaodong Zhao; Nan Li; Chengtao Lou; Ying Huang; Dongmei Tian; Yan Shen; Xiaodan Meng (Journal of Molecular Medicine, 2022)

Discriminating hydrocarbon generation potential of coaly source rocks and their contribution: a case study from the Upper Paleozoic of Bohai Bay Basin, China - Jinjun Xu; Da Lou; Qiang Jin; Lixin Fu; Fuqi Cheng; Shuhui Zhou; Xiuhong Wang; Chao Liang; Fulai Li (Frontiers of Earth Science, 2021)

Evaluation and GWAS of radicle gravitropic response in a core rice germplasm population - Qiaojun Lou; Qingsong Li; Fangjun Feng; Ryan Joynson; Yunan Yang; Lijun Luo; Liang Chen (Plant and Soil, 2021)
Aims Since gravitropism is one of the primary determinants of root development, facilitating root penetration into soil and subsequent absorption of water and nutrients, we studied this response in rice. Methods The gravitropism of 226 Chinese rice micro-core accessions and drought-resistant core accessions were assessed through the modified gravity-bending experiment and genome-wide association analysis (GWAS) was used to map the associated QTLs. Results The average value of gravitropic response speed of seminal roots was 41.05°/h, ranging from 16.77°/h to 62.83°/h. The gravity response speed of Indica (42.49°/h) was significantly (P < 0.002) higher than Japonica (39.71°/h) subspecies. The gravitational response speed of seminal roots was significantly positively correlated with the number of deep roots (r = 0.16), the growth speed of seminal roots (r = 0.21) and the drought resistance coefficient (r = 0.14). Conclusions In total, 3 QTLs (quantitative traits) associated with gravitropic response speed were identified on chromosome 4, 11 and 12. There are some known QTLs relating to roots traits and drought resistance located nearby the QTLs identified here, which confirms the close relationship between radicle gravitropism and the drought resistance. From within these intervals, 5 candidate genes were screened and verified by qPCR in a few rice varieties with extreme phenotypic values, demonstrating that gene LOC_Os12g29350 may regulate gravitropism negatively. This may be a promising candidate to be confirmed in further studies.

The identification of fish eggs of two species, the ovate sole Solea ovata and black porgy Acanthopagrus schlegelii - Yan‐jing Zheng; Xiu‐qin Li; Zhen‐xiong Yang; Wei‐xu Cai; Quan‐sheng Lou; Wei Tao (Journal of Fish Biology, 2021)
Fish eggs of the ovate sole Solea ovata and black porgy Acanthopagrus schlegelii were identified through DNA barcoding of cytochrome c oxidase subunit I (COX1). Visual taxonomic features were achieved, and photographs of the eggs of both species at different developmental stages were reported for the first time. In addition, the dissolution of oil globules caused by ethanol as egg fixatives was observed. This result showed the importance of using formalin as egg fixatives in the case of morphometric analysis and the necessity of combining molecular and visual taxonomic method for morphological study.

Pleosporalins H and I, two new heptaketides from the endophytic fungus Pleosporales sp. F46 by using OSMAC strategy - Hong-Xia Yang; Xiao-Ping Peng; Han Gao; Hui-Min Zhang; Zi-Ru Wang; Gang Li; Hong-Xiang Lou (Natural Product Research, 2021)

The Relationship Between the Gut Microbiome and Neurodegenerative Diseases - Xueling Zhu; Bo Li; Pengcheng Lou; Tingting Dai; Yang Chen; Aoxiang Zhuge; Yin Yuan; Lanjuan Li (Neuroscience Bulletin, 2021)
Many recent studies have shown that the gut microbiome plays important roles in human physiology and pathology. Also, microbiome-based therapies have been used to improve health status and treat diseases. In addition, aging and neurodegenerative diseases, including Alzheimer's disease and Parkinson's disease, have become topics of intense interest in biomedical research. Several researchers have explored the links between these topics to study the potential pathogenic or therapeutic effects of intestinal microbiota in disease. But the exact relationship between neurodegenerative diseases and gut microbiota remains unclear. As technology advances, new techniques for studying the microbiome will be developed and refined, and the relationship between diseases and gut microbiota will be revealed. This article summarizes the known interactions between the gut microbiome and neurodegenerative diseases, highlighting assay techniques for the gut microbiome, and we also discuss the potential therapeutic role of microbiome-based therapies in diseases.

Conversion of organics and minerals into electricity and microalgae using a dual-membrane cylinder photo-microbial fuel cell - Gang Li; Haixing Chang; Yajun Zou; Jianzhi Yue; Yaping Zheng; Haowen Feng; Haihua Wu; Wenbo Wu; Jie Lou; Xueqiang Qi; Xingran Zhang (Environmental Chemistry Letters, 2021)

Effect of fasting on protein metabolism in muscle tissue of Larimichthys crocea revealed by transcriptome and proteome - Yu Zhang; Weiliang Shen; Juan Li; Baoxiao Zheng; Zhengjia Lou; Mohammad Aslam Hosain; Baoying Qian; Liangyi Xue (Journal of Oceanology and Limnology, 2021)

Pathogenic Factors Identification of Brain Imaging and Gene in Late Mild Cognitive Impairment - Xia-an Bi; Lou Li; Ruihui Xu; Zhaoxu Xing (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Characterization, Sources and Excessive Cancer Risk of PM2.5-Bound Polycyclic Aromatic Hydrocarbons in Different Green Spaces in Lin’an, Hangzhou, China - Fang Huang; Yinke Zhang; Yilei Lou; Xiaolu Li; Tianran Zhang; Hui Yu; Chuyang Yuan; Qun Tong; Feng Qi; Feng Shao (Bulletin of Environmental Contamination and Toxicology, 2021)

Iodinated Contrast Agents Reduce the Efficacy of Intravenous Recombinant Tissue-Type Plasminogen Activator in Acute Ischemic Stroke Patients: a Multicenter Cohort Study - Zhicai Chen; Chao Xu; Wansi Zhong; Xiaoxian Gong; Haitao Hu; Xuting Zhang; Yi Chen; Qingqing Li; Zhongyu Luo; Zhuojian Chen; Min Lou (Translational Stroke Research, 2021)

Photosynthetic rate and chlorophyll fluorescence of barley exposed to simulated acid rain - Hao Hu; Wei Hua; Alin Shen; Hongkui Zhou; Li Sheng; Weidong Lou; Guangzhi Zhang (Environmental Science and Pollution Research, 2021)

Mid-Level Riverine Outflow Matters: A Case of Microplastic Transport in the Jiulong River, China - Yifan Li; Siguang Liu; Mengyang Liu; Wei Huang; Kai Chen; Yongcheng Ding; Fangzhu Wu; Hongwei Ke; Linghao Lou; Yan Lin; Mingyu Zhang; Fengjiao Liu; et al. (Frontiers in Marine Science, 2021)
Riverine outflow is one of the major pathways for microplastic transportation to coastal environments. Research on the output of microplastics in small- or medium-sized rivers will help accurately understand the status of their marine loads. In this study, we used both trawling and pumping methods to collect microplastics of different sizes in the Jiulong River Estuary and Xiamen Bay. We found that the abundance of small microplastics (44 μm–5.0 mm) was at least 20 times higher than the large particles (0.33–5.0 mm). The abundance of the large particles ranges from 4.96 to 16.3 particles/m 3 , and that of the small particles ranged from 82.8 to 918 particles/m 3 . Granule was the dominant shape (>60%), and polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET) were the most common components. The riverine flux of small microplastics (44 μm–5 mm, 472 ± 230 t/y) was at a medium level and was eight times greater than that of large particles (0.33–5.0 mm, 61.2 ± 2.6 t/y). The behavior of the large microplastics was relatively conservative, whose abundance had a significant correlation with salinity ( R 2 = 0.927) and was mainly influenced by physical factors. In contrast, results of statistical analysis revealed that more complicated factors influenced the small microplastics.

Comparative analysis of sRNAs, degradome and transcriptomics in sweet sorghum reveals the regulatory roles of miRNAs in Cd accumulation and tolerance - Weitao Jia; Kangqi Lin; Tengxue Lou; Juanjuan Feng; Sulian Lv; Ping Jiang; Ze Yi; Xuan Zhang; Duoliya Wang; Zijing Guo; Yetao Tang; Rongliang Qiu; et al. (Planta, 2021)

A bamboo leaf-specific aquaporin gene PePIP2;7 is involved in abiotic stress response - Huayu Sun; Sining Wang; Yongfeng Lou; Chenglei Zhu; Hansheng Zhao; Ying Li; Xueping Li; Zhimin Gao (Plant Cell Reports, 2021)

Production and characteristics of elemental sulfur during simultaneous nitrate and sulfide removal - Yue Sun; Mahmood Qaisar; Kaiquan Wang; Juqing Lou; Qiangbiao Li; Jing Cai (Environmental Science and Pollution Research, 2021)

Local ionospheric plasma bubble revealed by BDS Geostationary Earth Orbit satellite observations - Xiaomin Luo; Yidong Lou; Shengfeng Gu; Guozhu Li; Chao Xiong; Weiwei Song; Zhengyu Zhao (GPS Solutions, 2021)

Development and Application of Digital Human Models in the Field of Vehicle Collisions: A Review - Qian Wang; Yunfeng Lou; Tong Li; Xianlong Jin (Annals of Biomedical Engineering, 2021)

Vertical Profiles of Volatile Organic Compounds in Suburban Shanghai - Yuhan Liu; Hongli Wang; Shengao Jing; Ming Zhou; Shenrong Lou; Kun Qu; Wanyi Qiu; Qian Wang; Shule Li; Yaqin Gao; Yusi Liu; Xiaobing Li; et al. (Advances in Atmospheric Sciences, 2021)

A new dineolignan with anti- β -amyloid aggregation activity from the fruits of crataegus pinnatifida bge - Peng Zhao; Li-Li Lou; Hao Zhang; Rui Guo; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

Sulfur dioxide (SO2) emission reduction and its spatial spillover effect in high-tech industries: based on panel data from 30 provinces in China - Lingyan Lou; Jian Li; Shen Zhong (Environmental Science and Pollution Research, 2021)

Dilemma and solution of land scarcity, agro-production, and environmental risk for typical grain-producing areas in rapid urbanizing process in China - Guanyi Yin; Xilong Jiang; Yue Xin; Yi Lou; Shuai Xie; Guanghao Li; Shuang Liu; Xiaoming Wang; Xia Shi (Environmental Science and Pollution Research, 2021)

Performance analysis of landslide susceptibility assessment under different factor-filtering models - Yangchun Li; Feikai Lin; Lianhui Lou; Jiang Li; Zhanya Xu; Shuang Zhu; Xiangang Luo; Guangjie Huo; Qianjun Zhao (Arabian Journal of Geosciences, 2021)

Nitrification characteristics of long-term idle aerobic activated sludge during domestication - Zhaoxu Peng; Tianyu Lou; Kun Jiang; Ningqi Niu; Ju Wang; Lei Li (Environmental Science and Pollution Research, 2021)

Prediction of oral hepatotoxic dose of natural products derived from traditional Chinese medicines based on SVM classifier and PBPK modeling - Size Li; Yiqun Yu; Xiaolan Bian; Li Yao; Min Li; Yan-Ru Lou; Jing Yuan; Hai-shu Lin; Lucy Liu; Bing Han; Xiaoqiang Xiang (Archives of Toxicology, 2021)

An active-passive fusion strategy and accuracy evaluation for shallow water bathymetry based on ICESat-2 ATLAS laser point cloud and satellite remote sensing imagery - Bincai Cao; Yong Fang; Li Gao; Haiyan Hu; Zhengzhi Jiang; Bijiao Sun; Lele Lou (International Journal of Remote Sensing, 2021)

Biotechnology and bioengineering of pullulanase: state of the art and perspectives - Pei Xu; Shi-Yu Zhang; Zhi-Gang Luo; Min-Hua Zong; Xiao-Xi Li; Wen-Yong Lou (World Journal of Microbiology and Biotechnology, 2021)

The interaction between lipocalin 2 and dipyridine ketone hydrazone dithiocarbamte may influence respective function in proliferation and metastasis-related gene expressions in HepG2 cell - Cuiping Li; Yongli Li; Liying Lou; Xinyi Han; Huihui Wang; Tengfei Huang; Changzheng Li (JBIC Journal of Biological Inorganic Chemistry, 2021)

Potential mechanisms of cerebrovascular diseases in COVID-19 patients - Manxue Lou; Dezhi Yuan; Shengtao Liao; Linyan Tong; Jinfang Li (Journal of NeuroVirology, 2021)

Genome-wide association study of six quality-related traits in common wheat (Triticum aestivum L.) under two sowing conditions - Hongyao Lou; Runqi Zhang; Yitong Liu; Dandan Guo; Shanshan Zhai; Aiyan Chen; Yufeng Zhang; Chaojie Xie; Mingshan You; Huiru Peng; Rongqi Liang; Zhongfu Ni; et al. (Theoretical and Applied Genetics, 2021)

Morphological, anatomical and photosynthetic consequences of artificial allopolyploidization in Cucumis - Xiaqing Yu; Yufei Zhai; Panqiao Wang; Chunyan Cheng; Ji Li; Qunfeng Lou; Jinfeng Chen (Euphytica, 2021)

The bioaerosols emitted from toilet and wastewater treatment plant: a literature review - Mengmeng Lou; Shuai Liu; Chunjie Gu; Huimin Hu; Zhengkun Tang; Yaopeng Zhang; Chenye Xu; Fang Li (Environmental Science and Pollution Research, 2021)

Atlantic Meridional Overturning Circulation reconstructions and instrumentally observed multidecadal climate variability: A comparison of indicators - Cheng Sun; Jing Zhang; Xiang Li; Chunming Shi; Zhanqiu Gong; Ruiqiang Ding; Fei Xie; Panxing Lou (International Journal of Climatology, 2021)
The Atlantic Meridional Overturning Circulation (AMOC) has an important role in the Earth's climate system, but it remains unclear how the instrumentally observed multidecadal variability of the Earth's climate is related to the AMOC. We carried out a comprehensive evaluation of five representative indicators of the AMOC, including one atmospheric index based on the effect of accumulated atmospheric forcing on the AMOC and four oceanographic indices using surface and subsurface oceanographic variables in the North Atlantic Ocean. We compared reconstructions of the AMOC against measurement records and analysed the relationships with the multidecadal variability of the annual mean surface air temperature anomalies over the North Atlantic, Northern Hemisphere and South Atlantic. All the AMOC indicators show a weakening trend during the most recent decade, which is in good agreement with the RAPID measurement record of the AMOC. Besides, the atmospheric reconstruction shows the best agreement with the observed low‐frequency variation in the AMOC since 2004. The multidecadal variability in hemispheric/regional surface temperatures is closely related to all the AMOC reconstructions and opposite relationships are observed between the North Atlantic and South Atlantic oceans. The multidecadal surface air temperature anomalies associated with the variations in the AMOC are most pronounced for the atmospheric reconstruction index, which leads the variations in the surface air temperature by 4–5 years. Among the oceanographic indicators, the reconstructions using subsurface oceanographic variables performed best in terms of the relationship with the variations in the multidecadal surface air temperature.

ScAOC1, an allene oxide cyclase gene, confers defense response to biotic and abiotic stresses in sugarcane - Tingting Sun; Guangli Cen; Chuihuai You; Wenyue Lou; Zhoutao Wang; Weihua Su; Wenju Wang; Damei Li; Youxiong Que; Yachun Su (Plant Cell Reports, 2020)

Effect of Rock Properties on Electromagnetic Radiation Characteristics Generated by Rock Fracture During Uniaxial Compression - Menghan Wei; Dazhao Song; Xueqiu He; Zhenlei Li; Liming Qiu; Quan Lou (Rock Mechanics and Rock Engineering, 2020)

Carbon sequestration in aggregates from native and cultivated soils as affected by soil stoichiometry - Ruqin Fan; Jianjun Du; Aizhen Liang; Jun Lou; Jiangye Li (Biology and Fertility of Soils, 2020)

Variation in dustfall on the western Chinese Loess Plateau - Xunming Wang; Diwen Cai; Junpeng Lou; Zhenghua Tao; Hui Li; Caixia Zhang (Arabian Journal of Geosciences, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Identification of suitable reference genes for normalization of real-time quantitative PCR data in pecan (Carya illinoinensis) - Zhenghai Mo; Yaqi Chen; Wenrui Lou; Xiaodong Jia; Min Zhai; Jiping Xuan; Zhongren Guo; Yongrong Li (Trees, 2020)

Anxiolytic Effect of Increased NREM Sleep after Acute Social Defeat Stress in Mice - Xiang Feng; Hui-Ying Zhao; Yu-Jin Shao; Hui-Fang Lou; Li-Ya Zhu; Shumin Duan; Yan-Qin Yu (Neuroscience Bulletin, 2020)
Social defeat stress (SDS) plays a major role in the pathogenesis of psychiatric disorders like anxiety and depression. Sleep is generally considered to involve recovery of the brain from prior experience during wakefulness and is altered after acute SDS. However, the effect of acute SDS on sleep/wake behavior in mice varies between studies. In addition, whether sleep changes in response to stress contribute to anxiety is not well established. Here, we first investigated the effects of acute SDS on sleep/wake states in the active period in mice. Our results showed that total sleep time (time in rapid eye-movement [REM] and non-REM [NREM] sleep) increased in the active period after acute SDS. NREM sleep increased mainly during the first 3 h after SDS, while REM sleep increased at a later time. Then, we demonstrated that the increased NREM sleep had an anxiolytic benefit in acute SDS. Mice deprived of sleep for 1 h or 3 h after acute SDS remained in a highly anxious state, while in mice with ad libitum sleep the anxiety rapidly faded away. Altogether, our findings suggest an anxiolytic effect of NREM sleep, and indicate a potential therapeutic strategy for anxiety.

Dynamic Mechanical Properties and Fragment Fractal Characteristics of Fractured Coal–Rock-Like Combined Bodies in Split Hopkinson Pressure Bar Tests - Chengjie Li; Ying Xu; Peiyuan Chen; Hailong Li; Peijie Lou (Natural Resources Research, 2020)

Characteristics of chemotherapy-induced diabetes mellitus in acute lymphoblastic leukemia patients - Shan-shan Suo; Chen-ying Li; Yi Zhang; Jing-han Wang; Yin-jun Lou; Wen-juan Yu; Jie Jin (Journal of Zhejiang University-SCIENCE B, 2020)

A Comparative Study between Evergreen and Deciduous Daylily Species Reveals the Potential Contributions of Winter Shoot Growth and Leaf Freezing Tolerance to Foliar Habits - Danqing Li; Yiping Xia; Jianhua Lou; Dong Zhang; Xiaobin Wang; Jiaping Zhang (Journal of Plant Growth Regulation, 2020)

The influence of flow rates and water depth gradients on the growth process of submerged macrophytes and the biomass composition of the phytoplankton assemblage in eutrophic water: an analysis based on submerged macrophytes photosynthesis parameters - Duo Xu; Yan Xia; Zhaoxin Li; Yonggang Gu; Chunhua Lou; Hao Wang; Jinlong Han (Environmental Science and Pollution Research, 2020)

Cu(OH)2 nanorods undergo sulfidation in water: in situ formation of CuO nanorods as intermediates and enhanced toxicity to Escherichia coli - Heming Su; Xiaoting Qian; Zhouhang Gu; Zhenlan Xu; Haijin Lou; Xinyun Bian; Tao Zeng; Daohui Lin; Juliane Filser; Lingxiangyu Li (Environmental Chemistry Letters, 2020)

Machine Learning-based Weather Support for the 2022 Winter Olympics - Jiangjiang Xia; Haochen Li; Yanyan Kang; Chen Yu; Lei Ji; Lve Wu; Xiao Lou; Guangxiang Zhu; Zaiwen Wang; Zhongwei Yan; Lizhi Wang; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2020)

The metabolic changes in the hippocampus of an atherosclerotic rat model and the regulation of aerobic training - Beibei Liu; Jingjing Li; Xiaojing Lin; Jingyun Hu; Shujie Lou (Metabolic Brain Disease, 2020)

Glutathione S-transferase genes in scallops and their diverse expression patterns after exposure to PST-producing dinoflagellates - Jiarun Lou; Jie Cheng; Xiaogang Xun; Xu Li; Moli Li; Xiangchao Zhang; Tingting Li; Zhenmin Bao; Xiaoli Hu (Marine Life Science & Technology, 2020)

Gill transcriptomes reveal expression changes of genes related with immune and ion transport under salinity stress in silvery pomfret (Pampus argenteus) - Juan Li; Liangyi Xue; Mingyue Cao; Yu Zhang; Yajun Wang; Shanliang Xu; Baoxiao Zheng; Zhengjia Lou (Fish Physiology and Biochemistry, 2020)

Preparation and Flocculation Performance of Polysilicate Aluminum-Cationic Starch Composite Flocculant - Yuying Li; Hao Zhang; Xiyue Wang; Jie Ma; Lili Lian; Dawei Lou (Water, Air, & Soil Pollution, 2020)

Liquid-liquid phase separation in biology: mechanisms, physiological functions and human diseases - Hong Zhang; Xiong Ji; Pilong Li; Cong Liu; Jizhong Lou; Zheng Wang; Wenyu Wen; Yue Xiao; Mingjie Zhang; Xueliang Zhu (Science China Life Sciences, 2020)

Genome-wide analysis of laccase genes in moso bamboo highlights PeLAC10 involved in lignin biosynthesis and in response to abiotic stresses - Lichao Li; Kebin Yang; Sining Wang; Yongfeng Lou; Chenglei Zhu; Zhimin Gao (Plant Cell Reports, 2020)

Phthalate esters (PAEs) in soil and vegetables in solar greenhouses irrigated with reclaimed water - Yan Li; Guanhua Huang; Lei Zhang; Hua Gu; Chunhua Lou; Hang Zhang; Honglu Liu (Environmental Science and Pollution Research, 2020)

Karstification of Ordovician carbonate reservoirs in Huanghua depression and its control factors - Jinning Zhang; Jiansheng Zhou; Lixin Fu; Hongjun Li; Da Lou (Carbonates and Evaporites, 2020)
With extensive ancient karsts and abundant oil and gas resources, the Ordovician carbonate reservoirs in the Huanghua depression have broad prospects of exploration and development. The types, characteristics, distribution and controlling factors of karsts were investigated by means of the analysis of cores, thin slices, logging, seismic, and geochemical data in this study. The study reveals that the Ordovician carbonate reservoirs in the Huanghua depression falls into three main categories, pore type, pore-vug-fracture type and fracture type, of which, pore-vug-fracture reservoirs account for 62%. The epigenetic uniform karst mainly developed in the Late Ordovician to Early Carboniferous, while the differential karst developed in the Mesozoic. The uniform karstification mainly include chemical dissolution of the original carbonate rock, while the differential karstification not only include chemical dissolution but also hydraulic erosion and biochemical dissolution by organic acid. The burial karstification mainly involved the dissolution of the Ordovician reservoir by large amount of acidic fluids generated by the overlying Upper Paleozoic coal measure source rock while generating hydrocarbon. The dissolution caused by upwelling magmatic-tectonic hydrothermal fluids along faults also contributed to the formation of burial karst reservoirs. The sedimentation-diagenesis and paleogeomorphology-tectonic movement have certain control effects on the karstification of the Ordovician reservoirs in the Huanghua depression, determining the reservoir quality.

Acrepyrone A, a new γ -pyrone derivative from an endophytic fungus, Acremonium citrinum SS-g13 - Xiao-Ping Peng; Gang Li; Li-Xia Ji; Ying-Xia Li; Hong-Xiang Lou (Natural Product Research, 2020)

Perfusion Changes of Unexplained Early Neurological Deterioration After Reperfusion Therapy - Jingjing Fu; Ying Zhou; Qingqing Li; Genlong Zhong; Sheng Zhang; Ruiting Zhang; Chang Liu; Minming Zhang; Min Lou (Translational Stroke Research, 2020)

Correction to: Transcriptomic Profiling Provides Insights into Inbreeding Depression in Yesso Scallop Patinopecten yessoensis - Liang Zhao; Yangping Li; Jiarun Lou; Zhihui Yang; Huan Liao; Qiang Fu; Zhenyi Guo; Shanshan Lian; Xiaoli Hu; Zhenmin Bao (Marine Biotechnology, 2020)

Regulatory mechanisms and therapeutic potential of microglial inhibitors in neuropathic pain and morphine tolerance - Er-rong Du; Rong-ping Fan; Li-lou Rong; Zhen Xie; Chang-shui Xu (Journal of Zhejiang University-SCIENCE B, 2020)

Establishment and characterization of a new cell line derived from half-smooth tongue sole Cynoglossus semilaevis kidney - Yanan Lou; Bin Sun; Lina Zhang; Yong Li; Peng Xiao (Journal of Oceanology and Limnology, 2020)

Fupyrones A and B, two new α -pyrones from an endophytic fungus, Fusarium sp. F20 - Han Gao; Gang Li; Xiao-Ping Peng; Hong-Xiang Lou (Natural Product Research, 2020)

Betulinic acid attenuates lipopolysaccharide-induced vascular hyporeactivity in the rat aorta by modulating Nrf2 antioxidative function - Yao-Yao Bai; Dong Yan; Hui-Ying Zhou; Wei-Xin Li; Yang-Yun Lou; Xin-Ru Zhou; Ling-Bo Qian; Chi Xiao (Inflammopharmacology, 2020)

Chemical constituents from Ginkgo biloba leaves and their cytotoxicity activity - Penghua Shu; Mengyuan Sun; Junping Li; Lingxiang Zhang; Haichang Xu; Yueyue Lou; Zhiyu Ju; Xialan Wei; Wenming Wu; Na Sun (Journal of Natural Medicines, 2020)

Self-healing effect of water-conducting fractures due to water-rock interactions in undermined rock strata and its mechanisms - Jinfeng Ju; Quansheng Li; Jialin Xu; Xiaozhen Wang; Jinfu Lou (Bulletin of Engineering Geology and the Environment, 2020)

Systematic analysis of long non-coding RNA and mRNA expression changes in ApoE-deficient mice during atherosclerosis - Xiaoqian Lou; Xiaoyan Ma; Dawei Wang; Xiangjun Li; Bo Sun; Tong Zhang; Meng Qin; Liqun Ren (Molecular and Cellular Biochemistry, 2019)
Atherosclerosis plays an important role in the pathology of coronary heart disease, cerebrovascular disease, and systemic vascular disease. Long non-coding RNAs (lncRNAs) are involved in most biological processes and are deregulated in many human diseases. However, the expression alteration and precise role of lncRNAs during atherosclerosis are unknown. We report here the systematic profiling of lncRNAs and mRNAs in an ApoE-deficient (ApoE − / − ) mouse model of atherosclerosis. Clariom D solutions for the mouse Affymetrix Gene Chip were employed to analyze the RNAs from control and ApoE − / − mice. The functions of the differentially expressed mRNAs and lncRNAs and the relationships of their expression with atherosclerosis were analyzed by gene ontology, co-expression network, pathway enrichment, and lncRNA target pathway network analyses. Quantitative real-time PCR (QRT-PCR) was used to determine the expression of mRNAs and lncRNAs. A total of 2212 differentially expressed lncRNAs were identified in ApoE − / − mice, including 1186 up-regulated and 1026 down-regulated lncRNAs (|FC| ≥ 1.1, p < 0.05). A total of 1190 differentially expressed mRNAs were found in the ApoE − / − mice with 384 up-regulated and 806 down-regulated (|FC| ≥ 1.1, p < 0.05). Bioinformatics analyses demonstrated extensive co-expression of lncRNAs and mRNAs and concomitant deregulation of multiple signaling pathways associated with the initiation and progression of atherosclerosis. The identified differentially expressed mRNAs and lncRNAs as well as the related signaling pathways may provide systematic information for understanding the pathogenesis and identifying biomarkers for the diagnosis, treatment, and prognosis of atherosclerosis.

Effect of Straw Retention on Crop Yield, Soil Properties, Water Use Efficiency and Greenhouse Gas Emission in China: A Meta-Analysis - Peng Liu; Jin He; Hongwen Li; Qingjie Wang; Caiyun Lu; Kan Zheng; Wenzheng Liu; Hongbo Zhao; Shangyi Lou (International Journal of Plant Production, 2019)

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Candidate genes underlying the quantitative trait loci for root-knot nematode resistance in a Cucumis hystrix introgression line of cucumber based on population sequencing - Chunyan Cheng; Xing Wang; Xuejiao Liu; Shuqiong Yang; Xiaqing Yu; Chuntao Qian; Ji Li; Qunfeng Lou; Jinfeng Chen (Journal of Plant Research, 2019)
The southern root-knot nematode (RKN), Meloidogyne incognita (Kofoid & White) Chitwood, is one of most destructive species of plant parasitic nematodes, causing significant economic losses to numerous crops including cucumber ( Cucumis sativus L. 2n = 14). No commercial cultivar is currently available with resistance to RKN, severely hindering the genetic improvement of RKN resistance in cucumber. An introgression line, IL10-1, derived from the interspecific hybridization between the wild species Cucumis hystrix Chakr. (2n = 24, HH) and cucumber, was identified with resistance to RKN. In this study, an ultrahigh-density genetic linkage bin-map, composed of high-quality single-nucleotide polymorphisms (SNPs), was constructed based on low-coverage sequences of the F 2:6 recombinant inbred lines derived from the cross between inbred line IL10-1 and cultivar ‘Beijingjietou’ CC3 (hereinafter referred to as CC3). Three QTLs were identified accounting for 13.36% (qRKN1-1), 9.07% and 9.58% (qRKN5-1 and qRKN5-2) of the resistance variation, respectively. Finally, four genes with nonsynonymous SNPs from chromosome 5 were speculated to be the candidate RKN-resistant related genes, with annotation involved in disease resistance. Though several gaps still exist on the bin-map, our results could potentially be used in breeding programs and establish an understanding of the associated mechanisms underlying RKN resistance in cucumber.

Evolution of Local Mine Stiffness with Mining Process: Insight from Physical and Numerical Modeling - Fuqiang Gao; Hongpu Kang; Jinfu Lou; Jianzhong Li; Xiaoqing Wang (Rock Mechanics and Rock Engineering, 2019)

Brain-wide Mapping of Mono-synaptic Afferents to Different Cell Types in the Laterodorsal Tegmentum - Xiaomeng Wang; Hongbin Yang; Libiao Pan; Sijia Hao; Xiaotong Wu; Li Zhan; Yijun Liu; Fan Meng; Huifang Lou; Ying Shen; Shumin Duan; Hao Wang (Neuroscience Bulletin, 2019)

Transcriptomic Profiling Provides Insights into Inbreeding Depression in Yesso Scallop Patinopecten yessoensis - Liang Zhao; Yangping Li; Jiarun Lou; Zhihui Yang; Huan Liao; Qiang Fu; Zhenyi Guo; Shanshan Lian; Xiaoli Hu; Zhemin Bao (Marine Biotechnology, 2019)

Genetic mapping of angular leaf spot resistance to Pseudomonas syringae pv. lachrymans in a Cucumis hystrix introgression line of cucumber - Kaijing Zhang; Yifan Wei; Martin Kagiki Njogu; Xing Wang; Qunfeng Lou; Ji Li; Jinfeng Chen (Euphytica, 2019)

Aerobic Exercise Improves Synaptic-Related Proteins of Diabetic Rats by Inhibiting FOXO1/NF-κB/NLRP3 Inflammatory Signaling Pathway and Ameliorating PI3K/Akt Insulin Signaling Pathway - Qian Wang; Jingyun Hu; Yuran Liu; Jingjing Li; Beibei Liu; Mingming Li; Shujie Lou (Journal of Molecular Neuroscience, 2019)

Acyl-CoA synthetases from Physcomitrella, rice and Arabidopsis: different substrate preferences but common regulation by MS188 in sporopollenin synthesis - Yue-Ling Li; Yan-Fei Zhang; Dan-Dan Li; Qiang-Sheng Shi; Yue Lou; Zhong-Nan Yang; Jun Zhu (Planta, 2019)

Effects of Spartina alterniflora invasion on quality of the red-crowned crane (Grus japonensis) wintering habitat - Juan Wang; Hongyu Liu; Yufeng Li; Ling Liu; Fufu Xie; Cairong Lou; Huabing Zhang (Environmental Science and Pollution Research, 2019)

A new coumarin from Juglans mandshurica Maxim induce apoptosis in hepatocarcinoma cells - Li-Li Lou; Peng Zhao; Zhuo-Yang Cheng; Rui Guo; Guo-Dong Yao; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

A Simple and Rapid Method to Determine Sulfonation Degree of Lignosulfonates - Qi Li; Meijun Zeng; Duming Zhu; Hongming Lou; Yuxia Pang; Kexian Qiu; Jinhao Huang; Xueqing Qiu (BioEnergy Research, 2019)

Conditioned Medium Enhances Osteogenic Differentiation of Induced Pluripotent Stem Cell-Derived Mesenchymal Stem Cells - Siying Zhong; Xufeng He; Yuexia Li; Xiangxin Lou (Tissue Engineering and Regenerative Medicine, 2019)

Real-time precise orbit determination for BDS satellites using the square root information filter - Xiaolei Dai; Yidong Lou; Zhiqiang Dai; Yun Qing; Min Li; Chuang Shi (GPS Solutions, 2019)

Alkaloids from Juglans Mandshurica maxim induce distinctive cell death in hepatocellular carcinoma cells - Li-Li Lou; Zhuo-Yang Cheng; Rui Guo; Guo-Dong Yao; Shao-Jiang Song (Natural Product Research, 2019)

The short- and long-term effects of nitrite on denitrifying anaerobic methane oxidation (DAMO) organisms - Juqing Lou; Xilei Wang; Jiaping Li; Jingyi Han (Environmental Science and Pollution Research, 2019)

The synthesized transporter K16APoE enabled the therapeutic HAYED peptide to cross the blood-brain barrier and remove excess iron and radicals in the brain, thus easing Alzheimer’s disease - Zhenyou Zou; Qiqiong Shen; Yanxia Pang; Xin Li; Yongfeng Chen; Xinjuan Wang; Xinhua Luo; Zhongmin Wu; Zhaosheng Bao; Juanli Zhang; Jiawei Liang; Lingjia Kong; et al. (Drug Delivery and Translational Research, 2019)

A half-type ABC transporter FeSTAR1 regulates Al resistance possibly via UDP-glucose-based hemicellulose metabolism and Al binding - Jia Meng Xu; He Qiang Lou; Jian Feng Jin; Wei Wei Chen; Jiang Xue Wan; Wei Fan; Jian Li Yang (Plant and Soil, 2018)

Knockdown of miR-372 Inhibits Nerve Cell Apoptosis Induced by Spinal Cord Ischemia/Reperfusion Injury via Enhancing Autophagy by Up-regulating Beclin-1 - Xigong Li; Xianfeng Lou; Sanzhong Xu; Quan Wang; Miaoda Shen; Jing Miao (Journal of Molecular Neuroscience, 2018)

Complete resistance to powdery mildew and partial resistance to downy mildew in a Cucumis hystrix introgression line of cucumber were controlled by a co-localized locus - Kaijing Zhang; Xing Wang; Wenwei Zhu; Xiaodong Qin; Jian Xu; Chunyan Cheng; Qunfeng Lou; Ji Li; Jinfeng Chen (Theoretical and Applied Genetics, 2018)

LeSPL-CNR negatively regulates Cd acquisition through repressing nitrate reductase-mediated nitric oxide production in tomato - Wei Wei Chen; Jian Feng Jin; He Qiang Lou; Li Liu; Leon V. Kochian; Jian Li Yang (Planta, 2018)

Polyphenolic compounds from Malus hupehensis and their free radical scavenging effects - Qingwen Hu; Ying-Ying Chen; Qi-Yang Jiao; Afsar Khan; Jimiao Shan; Gui-Dong Cao; Feng Li; Chao Zhang; Hong-Xiang Lou (Natural Product Research, 2018)

Glucocorticoid receptor activation induces decrease of hippocampal astrocyte number in rats - Yu-Xia Lou; Jing Li; Zhen-Zhen Wang; Cong-Yuan Xia; Nai-Hong Chen (Psychopharmacology, 2018)

Rapid estimation of microbial biomass in acid red soils with and without substrate incorporation - Peng Su; Yong Liu; Sifan Wang; Zhongqi Yan; Shan Wang; Lian Zhu; Jun Lou; Fangbai Li (Journal of Soils and Sediments, 2018)

Srk1 kinase, a SR protein‐specific kinase, is important for sexual reproduction, plant infection and pre‐mRNA processing in Fusarium graminearum - Guanghui Wang; Peng Sun; Ziwen Gong; Lianfeng Gu; Yi Lou; Wenqin Fang; Lianhu Zhang; Li Su; Tao Yang; Baohua Wang; Jie Zhou; Jin‐Rong Xu; et al. (Environmental Microbiology, 2018)
Summary SR protein‐specific kinases (SRPKs) uniquely with a spacer region are important splicing factors from yeast to human. However, little is known about their biological functions in filamentous fungi. Therefore, we characterized a SRPK called SRK1 in wheat scab fungus Fusarium graminearum . Our data showed that Srk1 is required for vegetative growth, sexual reproduction and plant infection, and plays critical roles in pre‐mRNA alternative splicing and gene expression. Remarkably, we found that Srk1 displayed dynamic shuttling between cytoplasm and the nucleus, which is regulated by the divergent spacer domain rather than its kinase activity, suggesting a regulatory mechanism for Srk1. Interestingly, Srk1‐GFP also localized to the septal pores, indicating a possible role of Srk1 unrelated to mRNA processing. Although both K1 and K2 lobes of the kinase domain are essential for Srk1 functions, the K2 but not K1 lobe is responsible for the septal pore localization. Lastly, we established that Srk1 physically interacts with the two SR proteins, FgNpl3 and FgSrp1. Overall, our results indicated that SRK1 regulates fungal development, plant infection and mRNA processing by phosphorylation of other splicing factors including SR proteins, and the spacer domain regulates the functions of Srk1 by modulating its nucleocytoplasmic shuttling.

Spinal Cord Stimulation Frequency Influences the Hemodynamic Response in Patients with Disorders of Consciousness - Juanning Si; Yuanyuan Dang; Yujin Zhang; Yaxin Li; Wenyue Zhang; Yi Yang; Yue Cui; Xiaoping Lou; Jianghong He; Tianzi Jiang (Neuroscience Bulletin, 2018)

Luteolin alleviates cardiac ischemia/reperfusion injury in the hypercholesterolemic rat via activating Akt/Nrf2 signaling - Jin-Ting Yang; Jue Wang; Xin-Ru Zhou; Chi Xiao; Yang-Yun Lou; Li-Hui Tang; Feng-Jiang Zhang; Ling-Bo Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Pentachlorophenol dissipation and ferrous iron accumulation in flooded paddy soils with contrasting organic matter contents and incorporation of legume green manures - Yong Liu; Sifan Wang; Lian Zhu; Yunsheng Xia; Huihua Zhang; Shan Wang; Xiongsheng Yu; Jun Lou; Fangbai Li; Jianming Xu (Journal of Soils and Sediments, 2018)

Comparative study on Artemisia halodendron Turcz. and its two related plants by GC-MS analysis and protective effect against carbon tetrachloride-induced hepatotoxicity in mice - Yayu Wang; Lu Lou; Jing Wang; Jincai Lu; Jing Li; Lingyun Jia (Natural Product Research, 2018)

Ethanol Alters APP Processing and Aggravates Alzheimer-Associated Phenotypes - Daochao Huang; Mengjiao Yu; Shou Yang; Dandan Lou; Weitao Zhou; Lingling Zheng; Zhe Wang; Fang Cai; Weihui Zhou; Tingyu Li; Weihong Song (Molecular Neurobiology, 2018)

Traumatic Brain Injury Alters the Metabolism and Facilitates Alzheimer’s Disease in a Murine Model - Dandan Lou; Yao Du; Daochao Huang; Fang Cai; Yun Zhang; Tinyu Li; Weihui Zhou; Hongchang Gao; Weihong Song (Molecular Neurobiology, 2018)

Effects of Fall Height and Impact Strategy on Energy Absorption Ratio Between Shoulder Joint and Elbow Joint - Paul Pei-Hsi Chou; Shu-Zon Lou; Yen-Po Huang; Hon-Yu Chen; You-Li Chou (Journal of Medical and Biological Engineering, 2018)

The potential effects of aeolian processes on the vegetation in a semiarid area: geochemical evidence from plants and soils - Junpeng Lou; Xunming Wang; Bingqi Zhu; Danfeng Li; Linlin Jiao; Wenyong Ma; Diwen Cai (Arabian Journal of Geosciences, 2018)

Physical and chemical characteristics of PM2.5 and its toxicity to human bronchial cells BEAS-2B in the winter and summer - Hui-hui Zhang; Zheng Li; Yu Liu; Ping Xinag; Xin-yi Cui; Hui Ye; Bao-lan Hu; Li-ping Lou (Journal of Zhejiang University-SCIENCE B, 2018)

Experiment and Capillary Bundle Network Model of Micro Polymer Particles Propagation in Porous Media - Weiyao Zhu; Jianhui Li; Yu Lou; Hongqing Song (Transport in Porous Media, 2018)

Microbial community shifts trigger loss of orthophosphate in wetland soils subjected to experimental warming - Hang Wang; ChangYun Teng; HongYi Li; XingZhao Sun; ChengLiang Jiang; LiPing Lou; ChunLei Yue; ZhiJian Zhang (Plant and Soil, 2018)

A 3-D DDA damage analysis of brick masonry buildings under the impact of boulders in mountainous areas - Shu-guang Liu; Zhu-jun Li; Hong Zhang; Wei Wu; Gui-hui Zhong; Sha Lou (Journal of Mountain Science, 2018)

Do aeration conditions affect arsenic and phosphate accumulation and phosphate transporter expression in rice (Oryza sativa L.)? - Chuan Wu; Qiongli Wang; Shengguo Xue; Weisong Pan; Laiqing Lou; Daojun Li; William Hartley (Environmental Science and Pollution Research, 2018)

Summer drought index using SPEI based on 10-day temperature and precipitation data and its application in Zhejiang Province (Southeast China) - Weiping Lou; Shanlei Sun; Ke Sun; Xiangzhu Yang; Songping Li (Stochastic Environmental Research and Risk Assessment, 2017)

CLOCK rs1801260 Polymorphism is Associated with Susceptibility to Parkinson’s Disease in a Chinese Population - Fan Lou; Ming Li; Yan Ren; Xiao-Guang Luo; Na Liu; Xiaohong Li (Neuroscience Bulletin, 2017)

Relationships of relative humidity with PM2.5 and PM10 in the Yangtze River Delta, China - Cairong Lou; Hongyu Liu; Yufeng Li; Yan Peng; Juan Wang; Lingjun Dai (Environmental Monitoring and Assessment, 2017)

Organization and evolution of four differentially amplified tandem repeats in the Cucumis hystrix genome - Shuqiong Yang; Xiaodong Qin; Chunyan Cheng; Ziang Li; Qunfeng Lou; Ji Li; Jinfeng Chen (Planta, 2017)

The aflatoxin-detoxifizyme specific expression in the parotid gland of transgenic pigs - An-gang Lou; Jin-shun Cai; Xue-mei Zhang; Cheng-dou Cui; Ying-shu Piao; Li-zeng Guan (Transgenic Research, 2017)

Parental attendance of Chestnut Thrush reduces nest predation during the incubation period: compensation for low nest concealment? - Yun-Biao Hu; Qing-Shan Zhao; Ying-Qiang Lou; Li-Jun Chen; Manuel Antonio González; Yue-Hua Sun (Journal of Ornithology, 2017)

Assessment of PPP integer ambiguity resolution using GPS, GLONASS and BeiDou (IGSO, MEO) constellations - Yanyan Liu; Yidong Lou; Shirong Ye; Rui Zhang; Weiwei Song; Xing Zhang; Qingquan Li (GPS Solutions, 2017)

Over-expression of GmSN1 enhances virus resistance in Arabidopsis and soybean - Hongli He; Xiangdong Yang; Hongwei Xun; Xue Lou; Shuzhen Li; Zhibin Zhang; Lili Jiang; Yingshan Dong; Shucai Wang; Jinsong Pang; Bao Liu (Plant Cell Reports, 2017)

Regulation of SET Gene Expression by NFkB - Yi Feng; Xiaoyong Li; Weitao Zhou; Dandan Lou; Daochao Huang; Yanhua Li; Yu Kang; Yan Xiang; Tingyu Li; Weihui Zhou; Weihong Song (Molecular Neurobiology, 2017)

Assessment and potential sources of metals in the surface sediments of the Yellow River Delta, Eastern China - Qingli Cheng; Guangyan Lou; Wenhai Huang; Xudong Li (Environmental Science and Pollution Research, 2017)

Impact of GPS differential code bias in dual- and triple-frequency positioning and satellite clock estimation - Haojun Li; Bofeng Li; Lizhi Lou; Ling Yang; Jiexian Wang (GPS Solutions, 2017)

Variations of winter precipitation over southeastern China in association with the North Atlantic Oscillation - Maoyuan Lou; Chao Li; Shifeng Hao; Juan Liu (Journal of Meteorological Research, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

The bamboo aquaporin gene PeTIP4;1–1 confers drought and salinity tolerance in transgenic Arabidopsis - Huayu Sun; Lichao Li; Yongfeng Lou; Hansheng Zhao; Yihong Yang; Sining Wang; Zhimin Gao (Plant Cell Reports, 2017)

Intra-individual comparison of different gadolinium-based contrast agents in the quantitative evaluation of C6 glioma with dynamic contrast-enhanced magnetic resonance imaging - Ying Li; Gang Liu; Xin Lou; Zhiye Chen; Lin Ma (Science China Life Sciences, 2017)

T2 relaxation time measurements in the brains of scalded rats - Tao Jiang; Liqi Xie; Xin Lou; Dawei Li; Zhiye Chen; Huafeng Xiao; Lin Ma (Science China Life Sciences, 2017)

miR-21 is involved in skeletal deficiencies of zebrafish embryos exposed to polychlorinated biphenyls - Li Ju; Zhiwen Zhou; Bo Jiang; Yue Lou; Zhiqun Zhang (Environmental Science and Pollution Research, 2017)

Identification of an iron permease, cFTR1, in cyanobacteria involved in the iron reduction/re‐oxidation uptake pathway - Ning Xu; Guo‐Wei Qiu; Wen‐Jing Lou; Zheng‐Ke Li; Hai‐Bo Jiang; Neil M. Price; Bao‐Sheng Qiu (Environmental Microbiology, 2016)
Summary Cyanobacteria are globally important primary producers and abundant in many iron‐limited aquatic environments. The ways in which they take up iron are largely unknown, but reduction of Fe 3+ is an important step in the process. Here we report a special iron permease in Synechocystis , cFTR1, that is required for Fe 3+ uptake following Fe 2+ re‐oxidation. The expression of cFTR1 is induced by iron starvation, and a mutant lacking the gene is abnormally sensitive to iron starvation. The cFTR1 protein localizes to the plasma membrane and contains the iron‐binding motif “REXXE”. Point‐directed mutagenesis of the REXXE motif results in a sensitivity to Fe‐deficiency. Measurements of iron ( 55 Fe) uptake rate show that cFTR1 takes up Fe 3+ rather than Fe 2+ . The function of cFTR1 in Synechocystis could be genetically complemented by the iron permease, Ftr1p, of Saccharomyces cerevisiae , that is known to transport Fe 3+ produced by the oxidation of Fe 2+ via a multicopper oxidase. Unlike yeast Ftr1p, cyanobacterial cFTR1 probably obtains Fe 3+ primarily from the oxidation of Fe 2+ by oxygen. Growth assays show that the cFTR1 is required during oxygenic, photoautotrophic growth but not when oxygen production is inhibited during photoheterotrophic growth. In cyanobacteria, iron reduction/re‐oxidation uptake pathway may represent their adaptation to oxygenated environments.

Genome-wide scans reveal variants at EDAR predominantly affecting hair straightness in Han Chinese and Uyghur populations - Sijie Wu; Jingze Tan; Yajun Yang; Qianqian Peng; Manfei Zhang; Jinxi Li; Dongsheng Lu; Yu Liu; Haiyi Lou; Qidi Feng; Yan Lu; Yaqun Guan; et al. (Human Genetics, 2016)

Undifferenced Cycle Slip Estimation of Triple-Frequency BeiDou Signals with Ionosphere Prediction - Bofeng Li; Yanan Qin; Zhen Li; Lizhi Lou (Marine Geodesy, 2016)

The Roles of Genes in the Neuronal Migration and Neurite Outgrowth Network in Developmental Dyslexia: Single- and Multiple-Risk Genetic Variants - Shanshan Shao; Rui Kong; Li Zou; Rong Zhong; Jiao Lou; Jie Zhou; Shengnan Guo; Jia Wang; Xiaohui Zhang; Jiajia Zhang; Ranran Song (Molecular Neurobiology, 2016)

Comparative genomic analysis of Lactobacillus plantarum ZJ316 reveals its genetic adaptation and potential probiotic profiles - Ping Li; Xuan Li; Qing Gu; Xiu-yu Lou; Xiao-mei Zhang; Da-feng Song; Chen Zhang (Journal of Zhejiang University-SCIENCE B, 2016)

Efficient biodegradation of phenanthrene by a novel strain Massilia sp. WF1 isolated from a PAH-contaminated soil - Haizhen Wang; Jun Lou; Haiping Gu; Xiaoyan Luo; Li Yang; Laosheng Wu; Yong Liu; Jianjun Wu; Jianming Xu (Environmental Science and Pollution Research, 2016)

Characterization and primary functional analysis of a bamboo NAC gene targeted by miR164b - Lili Wang; Hansheng Zhao; Dongliang Chen; Lichao Li; Huayu Sun; Yongfeng Lou; Zhimin Gao (Plant Cell Reports, 2016)

Genome-wide identification and characterization of aquaporin gene family in moso bamboo (Phyllostachys edulis) - Huayu Sun; Lichao Li; Yongfeng Lou; Hansheng Zhao; Zhimin Gao (Molecular Biology Reports, 2016)

Genotyping of Nocardia farcinica with multilocus sequence typing - P. Du; X. Hou; Y. Xie; S. Xu; L. Li; J. Zhang; K. Wan; Y. Lou; Z. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Platelet-mediated adhesion facilitates leukocyte sequestration in hypoxia-reoxygenated microvessels - Senfeng Zheng; Yanting Cao; Wenjian Zhang; Honglin Liu; Jia You; Yiqing Yin; Jinning Lou; Chenghui Li (Science China Life Sciences, 2016)

Genome-wide Screening of Human Papillomavirus-Specific CTL Epitopes Presented by HLA-A Alleles in Cervical Cancer - Qiao-Hong Wang; Xiang-Yang Gao; Xue-Ling Lou; Li Yao; Zhan-Xin Zhang; Xi-Hong Zhang; Yu-Hong Xia; Bei-Bei Liu; Li-Li Zhang (International Journal of Peptide Research and Therapeutics, 2016)

Pretreatment of Miscanthus by NaOH/Urea Solution at Room Temperature for Enhancing Enzymatic Hydrolysis - Hongming Lou; Qiaoyan Hu; Xueqing Qiu; Xiuli Li; Xuliang Lin (BioEnergy Research, 2016)

Neuroprotective Effect Is Driven Through the Upregulation of CB1 Receptor in Experimental Autoimmune Encephalomyelitis - Zhi-Yin Lou; Wen-Bo Yu; Jie Chen; Lin Li; Li-Sheng Jiang; Bao-Guo Xiao; Zhen-Guo Liu (Journal of Molecular Neuroscience, 2016)

Expression of Shewanella frigidimarina fatty acid metabolic genes in E. coli by CRISPR/cas9-coupled lambda Red recombineering - Jun Xia; Ling Wang; Jian-bo Zhu; Cheng-jun Sun; Ming-gang Zheng; Li Zheng; Ying-hua Lou; Lei Shi (Biotechnology Letters, 2016)

Radiative effects on torrential rainfall during the landfall of Typhoon Fitow (2013) - Lingyun Lou; Xiaofan Li (Advances in Atmospheric Sciences, 2016)

Elevated Serum Mannose-Binding Lectin Levels Are Associated with Poor Outcome After Acute Ischemic Stroke in Patients with Type 2 Diabetes - Fang-Yu Song; Meng-Hai Wu; Li-hua Zhu; Zhi-Qiang Zhang; Qin-De Qi; Chang-li Lou (Molecular Neurobiology, 2015)

Identification of two novel critical mutations in PCNT gene resulting in microcephalic osteodysplastic primordial dwarfism type II associated with multiple intracranial aneurysms - Fei-Feng Li; Xu-Dong Wang; Min-Wei Zhu; Zhi-Hong Lou; Qiong Zhang; Chun-Yu Zhu; Hong-Lin Feng; Zhi-Guo Lin; Shu-Lin Liu (Metabolic Brain Disease, 2015)

Molecular characterization and primary functional analysis of PeMPEC, a magnesium-protoporphyrin IX monomethyl ester cyclase gene of bamboo (Phyllostachys edulis) - Li Yang; Yongfeng Lou; Zhenhua Peng; Hansheng Zhao; Huayu Sun; Zhimin Gao (Plant Cell Reports, 2015)

CmpacC regulates mycoparasitism, oxalate degradation and antifungal activity in the mycoparasitic fungus C oniothyrium minitans - Yi Lou; Yongchao Han; Long Yang; Mingde Wu; Jing Zhang; Jiasen Cheng; Moying Wang; Daohong Jiang; Weidong Chen; Guoqing Li (Environmental Microbiology, 2015)
Summary The PacC /Rim101 pH ‐responsive transcription factor is an important pathogenicity element for many plant‐pathogenic fungi. In this study, we investigated the roles of a PacC homologue, CmpacC , in the mycoparasitic fungus C oniothyrium minitans . CmpacC was confirmed to have the transcriptional activation activity by the transcriptional activation test in S accharomyces cerevisiae . Disruption of CmpacC resulted in impaired fungal responses to ambient pH . Compared to the wild‐type, the CmpacC ‐disruption mutant Δ CmpacC ‐29 was significantly suppressed for activities of chitinase and β‐1,3‐glucanase at pH 5 and 7, consistent with reduced expression levels of Cmch1 and Cmg1 coding for the two enzymes respectively. However, the mutant displayed acidity‐mimicking phenotypes such as improved oxalate degradation and increased antifungal activity at pH 6 or higher. Improved efficacy in oxalate degradation by Δ CmpacC ‐29 was consistent with the enhanced expression level of Cmoxdc1 coding for oxalate decarboxylase. CmpacC transcriptional activation of Cmch1 and Cmg1 and repression of Cmoxdc1 were verified by the presence of the PacC /Rim101 consensus binding‐motifs in gene promoter regions and by the promoter DNA ‐binding assays. This study suggests that CmpacC plays an activator role in regulation of C . minitans mycoparasitism, whereas plays a repressor role in regulation of oxalate degradation and possibly antifungal activity of C . minitans .

Inhibition of myosin light chain kinase reduces NADPH oxidase-mediated oxidative injury in rat brain following cerebral ischemia/reperfusion - Hong-Feng Zhang; Ting-Bo Li; Bin Liu; Zheng Lou; Jie-Jie Zhang; Jing-Jie Peng; Xiao-Jie Zhang; Qi-Lin Ma; Jun Peng; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Diversity and space–time dynamics of endophytic archaea from sugar beet in the north slope of Tianshan Mountain revealed by 454 pyrosequencing and T-RFLP - YingWu Shi; MuSi TaPa; Chun Li; HongMei Yang; Tao Zhang; Yan Gao; Jian Sun; Jun Zeng; Qing Lin; ZhenHua Cao; KuEr OuTi; YuGuo Li; et al. (World Journal of Microbiology and Biotechnology, 2015)

23-year manure and fertilizer application increases soil organic carbon sequestration of a rice–barley cropping system - Yidong Wang; Ning Hu; Minggang Xu; Zhongfang Li; Yilai Lou; Yi Chen; Chunyan Wu; Zhong-Liang Wang (Biology and Fertility of Soils, 2015)

Stat3 promotes invasion of esophageal squamous cell carcinoma through up-regulation of MMP2 - Xaioyan Xuan; Shanshan Li; Xi Lou; Xianzhao Zheng; Yunyun Li; Feng Wang; Yuan Gao; Hongyan Zhang; Hongliu He; Qingru Zeng (Molecular Biology Reports, 2015)

The effect of SCF and ouabain on small intestinal motility dysfunction induced by gastric cancer peritoneal metastasis - Dan Kong; Jing Li; Baoshan Zhao; Bairong Xia; Lei Zhang; Yan He; Xiuli Wang; Lei Gao; Yufu Wang; Xiaoming Jin; Ge Lou (Clinical & Experimental Metastasis, 2015)

Current evidences on the XPG Asp1104His polymorphism and melanoma susceptibility: a meta-analysis based on case–control studies - Yuanzhi Xu; Guangjun Jiao; Li Wei; Ning Wang; Yajun Xue; Jin Lan; Yajie Wang; Chuan Liu; Meiqing Lou (Molecular Genetics and Genomics, 2015)

Primary succession of soil enzyme activity and heterotrophic microbial communities along the chronosequence of Tianshan Mountains No. 1 Glacier, China - Jun Zeng; Xiao-xia Wang; Kai Lou; Moniruzzaman Khan Eusufzai; Tao Zhang; Qing Lin; Ying-wu Shi; Hong-mei Yang; Zhong-qing Li (Antonie van Leeuwenhoek, 2015)

Late Permian–Triassic siliciclastic provenance, palaeogeography, and crustal growth of the Songpan terrane, eastern Tibetan Plateau: evidence from U–Pb ages, trace elements, and Hf isotopes of detrital zircons - Yu-Xiu Zhang; Lu Zeng; Zhi-Wu Li; Cheng-Shan Wang; Kai-Jun Zhang; Wen-Guang Yang; Tong-Lou Guo (International Geology Review, 2015)

Effects of doubled carbon dioxide on rainfall responses to radiative processes of water clouds - Xiaofan Li; Tingting Li; Lingyun Lou (Journal of Meteorological Research, 2014)

Cenozoic tectonic and sedimentary evolution of southern Qaidam Basin, NE Tibetan Plateau and its implication for the rejuvenation of Eastern Kunlun Mountains - LiGuang Mao; AnCheng Xiao; Lei Wu; BenLiang Li; LiQun Wang; QianQian Lou; YouPu Dong; SuHua Qin (Science China Earth Sciences, 2014)

Secretomes are a potential source of molecular targets for cancer therapies and indicate that APOE is a candidate biomarker for lung adenocarcinoma metastasis - Zan Liu; Yuan Gao; Fengxia Hao; Xiaomin Lou; Xiuwei Zhang; Yang Li; Di Wu; Ting Xiao; Longhai Yang; Qingchang Li; Xueshan Qiu; Enhua Wang (Molecular Biology Reports, 2014)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

Erratum to: Inhibition of Notch signaling facilitates the differentiation of human-induced pluripotent stem cells into neural stem cells - Chun-Yuan Chen; Wei Liao; Yuan-Lei Lou; Qing Li; Bin Hu; Yang Wang; Zhi-Feng Deng (Molecular and Cellular Biochemistry, 2014)

Inhibition of Notch signaling facilitates the differentiation of human-induced pluripotent stem cells into neural stem cells - Chun-Yuan Chen; Wei Liao; Yuan-Lei Lou; Qing Li; Bin Hu; Yang Wang; Zhi-Feng Deng (Molecular and Cellular Biochemistry, 2014)

Molecular characterization of the hippeastrum chlorotic ringspot virus L segment and its protein - Ye Xu; Shi-gao Lou; Qiu-fang Li; Qing Hu; Li-peng Sun; Zheng-yue Li; Yong-zhong Li; Ya-ting Liu (Archives of Virology, 2014)

Protective effect of vitexin compound B-1 against hypoxia/reoxygenation-induced injury in differentiated PC12 cells via NADPH oxidase inhibition - Zhong-Bao Yang; Bin Tan; Ting-Bo Li; Zheng Lou; Jun-Lin Jiang; Ying-Jun Zhou; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Denitrification controls in urban riparian soils: implications for reducing urban nonpoint source nitrogen pollution - Yangjie Li; Zhenlou Chen; Huanjie Lou; Dongqi Wang; Huanguang Deng; Chu Wang (Environmental Science and Pollution Research, 2014)

Carbon sequestration effects of shrublands in Three-North Shelterbelt Forest region, China - Wenhui Liu; Jiaojun Zhu; Quanquan Jia; Xiao Zheng; Junsheng Li; Xuedong Lou; Lile Hu (Chinese Geographical Science, 2014)

Evaluating the Effects of Silent Discharge Plasma on Remediation of Acid Scarlet GR-Contaminated Soil - Na Lu; Jing Lou; Cui Hua Wang; Jie Li; Yan Wu (Water, Air, & Soil Pollution, 2014)

Distribution and geochemical characteristics of fluids in Ordovician marine carbonate reservoirs of the Tahe Oilfield - Mei Li; Zhanghua Lou; Rong Zhu; Aimin Jin; Ying Ye (Journal of Earth Science, 2014)

Akt and Erk1/2 activate the ornithine decarboxylase/polyamine system in cardioprotective ischemic preconditioning in rats: the role of mitochondrial permeability transition pores - Hao Zhang; Guo Xue; Weihua Zhang; Lina Wang; Hong Li; Li Zhang; Fanghao Lu; Shuzhi Bai; Yan Lin; Yu Lou; Changqing Xu; Yajun Zhao (Molecular and Cellular Biochemistry, 2014)

High-level soluble expression of the hemA gene from Rhodobacter capsulatus and comparative study of its enzymatic properties - Jia-wei Lou; Li Zhu; Mian-bin Wu; Li-rong Yang; Jian-ping Lin; Pei-lin Cen (Journal of Zhejiang University-SCIENCE B, 2014)

Overexpression of a Xylanase Inhibitor Gene, OsHI-XIP, Enhances Resistance in Rice to Herbivores - Zhaojun Xin; Qi Wang; Zhaonan Yu; Liucheng Hu; Jiancai Li; Caiyu Xiang; Baohui Wang; Yonggen Lou (Plant Molecular Biology Reporter, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Late Palaeozoic and early Mesozoic tectonic and palaeogeographic evolution of central China: evidence from U–Pb and Lu–Hf isotope systematics of detrital zircons from the western Qinling region - Yu-Xiu Zhang; Lu Zeng; Kai-Jun Zhang; Zhi-Wu Li; Cheng-Shan Wang; Tong-Lou Guo (International Geology Review, 2014)

Identification and Expression Analysis of D-type Cyclin Genes in Early Developing Fruit of Cucumber (Cucumis sativus L.) - Li Cui; Ji Li; Tinglin Zhang; Qinwei Guo; Jian Xu; Qunfeng Lou; Jinfeng Chen (Plant Molecular Biology Reporter, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Quantitative measurement of hip protector use and compliance - Katherine R. Evans; Edmond Lou; Chris Woloschuk; Doug Hill; Meng Li; Man-Sang Wong (Medical & Biological Engineering & Computing, 2014)

Cloning and expression analysis of Cs-TIR1/AFB2: the fruit development-related genes of cucumber (Cucumis sativus L.) - Li Cui; Tinglin Zhang; Ji Li; Qunfeng Lou; Jinfeng Chen (Acta Physiologiae Plantarum, 2014)

Anatomical and biochemical studies of bicolored flower development in Muscari latifolium - Yinyan Qi; Qian Lou; Huibo Li; Juan Yue; Yali Liu; Yuejin Wang (Protoplasma, 2013)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Effects of Recombinant Human AMH on SCF Expression in Human Granulosa Cells - Rong Hu; Yan Lou; Fei-Miao Wang; Hui-Ming Ma; Xing Wu; Xiao-Mei Zhang; Juan Li; Ying-Pu Sun (Cell Biochemistry and Biophysics, 2013)

Differential Responses of two Bamboo Species (Phyllostachys Auresulcata `Spectabilis' and Pleioblastus Chino `Hisauchii') to Excess Copper - Li Jiang; Gangrong Shi; Yulong Ding; Laiqing Lou; Qingsheng Cai (BioEnergy Research, 2013)

The complete S RNA and M RNA nucleotide sequences of a hippeastrum chlorotic ringspot virus (HCRV) isolate from Hymenocallis littoralis (Jacq.) Salisb in China - Ye Xu; Shi-gao Lou; Xiao-lin Li; Yuan-xian Zheng; Wen-cheng Wang; Ya-ting Liu (Archives of Virology, 2013)

Angiopep-Conjugated Nanoparticles for Targeted Long-Term Gene Therapy of Parkinson’s Disease - Rongqin Huang; Haojun Ma; Yubo Guo; Shuhuan Liu; Yuyang Kuang; Kun Shao; Jianfeng Li; Yang Liu; Liang Han; Shixian Huang; Sai An; Liya Ye; et al. (Pharmaceutical Research, 2013)

Cytochrome P450 2A6 deletion polymorphism and risk of lung cancer: a meta-analysis - Zheng-Bing Liu; Jun Shu; Li-Ping Wang; Cheng Jin; Zhi-Xia Lou (Molecular Biology Reports, 2013)

Differentiation of hUC-MSC into dopaminergic-like cells after transduction with hepatocyte growth factor - Jin-Feng Li; Hong-Lei Yin; Adam Shuboy; Hai-Feng Duan; Ji-Yu Lou; Jing Li; Hong-wei Wang; Yun-Liang Wang (Molecular and Cellular Biochemistry, 2013)

Effects of perfluorooctanesulfonate and perfluorobutanesulfonate on the growth and sexual development of Xenopus laevis - Qin-Qin Lou; Yin-Feng Zhang; Zhen Zhou; Ya-Li Shi; Ya-Nan Ge; Dong-Kai Ren; Hai-Ming Xu; Ya-Xian Zhao; Wu-Ji Wei; Zhan-Fen Qin (Ecotoxicology, 2013)

Local responses to macro development policies and their effects on rural system in China’s mountainous regions: the case of Shuanghe Village in Sichuan Province - Yu-rui Li; Yan-sui Liu; Hua-lou Long; Jie-yong Wang (Journal of Mountain Science, 2013)
China has promulgated a series of policies including the Western Development Program, the Grain for Green Project, agricultural support policies and building a new countryside strategy to eliminate east-west differences and urban-rural disparities since the late 1990s. This paper gives a holistic examination on local responses to the four typical macro socio-economic development policies and their effects on rural system based on a case study of a mountainous village in southern Sichuan Province. The results showed that the policies have not moved the case study village from its historically marginal status. To some extent, its socio-economic situation might have been worsened by accelerated out-migration of the youth, loss of agricultural land due to afforestation and industrial plants, increased fire hazard due to afforestation and reforestation, increased environmental pollution due to industrial enterprises attracted to the village and a steep decline in agricultural production due to loss of and inefficient use of cultivated land. Factors causing local villages’ dilemmas include the nonuniformity of actors’ objectives, finiteness of villagers’ abilities, and the imperfect incentive and restraint mechanism for local government’s activities under existing policy framework composed of uncoordinated one-size-fits-all policies. We suggest that China’s rural policy in the new period should gradually shift from a sectoral to a place-based one, from top-down incentives to the development of bottom-up projects, and fully recognize the diversity of rural space, so as to lift local capacities and make good use of the knowledge shared by different actors. Moreover, it is also necessary to integrate the various sectoral policies, and improve the interministerial and interdepartmental coordination of rural policies at regional and local levels.

OsMPK3 positively regulates the JA signaling pathway and plant resistance to a chewing herbivore in rice - Qi Wang; Jiancai Li; Lingfei Hu; Tongfang Zhang; Guren Zhang; Yonggen Lou (Plant Cell Reports, 2013)

β1-adrenoceptor gene Arg389Gly polymorphism and essential hypertension risk in general population: a meta-analysis - Hao Wang; Jielin Liu; Kuo Liu; Ya Liu; Zuoguang Wang; Yuqing Lou; Qiuli Niu; Wei Gu; Lijuan Wang; Mei Li; Xiaoling Zhu; Shaojun Wen (Molecular Biology Reports, 2013)

Reducing the oxidative stress mediates the cardioprotection of bicyclol against ischemia-reperfusion injury in rats - Jie Cui; Zhi Li; Ling-bo Qian; Qin Gao; Jue Wang; Meng Xue; Xiao-e Lou; Iain C. Bruce; Qiang Xia; Hui-ping Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Evaluating one- and two-source energy balance models in estimating surface evapotranspiration from Landsat-derived surface temperature and field measurements - Ronglin Tang; Zhao-Liang Li; Yuanyuan Jia; Chuanrong Li; Kun-Shan Chen; Xiaomin Sun; Jinyong Lou (International Journal of Remote Sensing, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Isolation and Characterization of Male-Specific DNA Markers in the Rock Bream Oplegnathus fasciatus - Dongdong Xu; Bao Lou; Hanxiang Xu; Sanlei Li; Zhi Geng (Marine Biotechnology, 2013)

Toxic effects, uptake, and translocation of Cd and Pb in perennial ryegrass - Yanhong Lou; Hongji Luo; Tao Hu; Huiying Li; Jinmin Fu (Ecotoxicology, 2013)

Dynamic responses of top tensioned riser under combined excitation of internal solitary wave, surface wave and vessel motion - Haiyan Guo; Li Zhang; Xiaomin Li; Min Lou (Journal of Ocean University of China, 2013)

Secondary metabolites from Marchantia paleacea calluses and their allelopathic effects on Arabidopsis seed growth - Lei Wang; Li-Ning Wang; Yu Zhao; Hong-Xiang Lou; Ai-Xia Cheng (Natural Product Research, 2013)

A functional polymorphism, rs28493229, in ITPKC and risk of Kawasaki disease: an integrated meta-analysis - Jiao Lou; Sanqing Xu; Li Zou; Rong Zhong; Ti Zhang; Yu Sun; Xuzai Lu; Li Liu; Chuanqi Li; Li Wang; Guanglian Xiong; Wei Wang; et al. (Molecular Biology Reports, 2012)

Spatial distribution of sponge spicules in sediments around Taiwan and the Sunda Shelf - Yalan Chou; Jiann Yuh Lou; Chen-Tung Arthur Chen; Li-Lian Liu (Journal of Oceanography, 2012)

Effects of epigeic earthworm (Eisenia fetida) and arbuscular mycorrhizal fungus (Glomus intraradices) on enzyme activities of a sterilized soil–sand mixture and nutrient uptake by maize - Huan Li; Dan Xiang; Chong Wang; Xiaolin Li; Yi Lou (Biology and Fertility of Soils, 2012)

Specific herbivore‐induced volatiles defend plants and determine insect community composition in the field - Y. Xiao; Q. Wang; M. Erb; T. C. J. Turlings; L. Ge; L. Hu; J. Li; X. Han; T. Zhang; J. Lu; G. Zhang; Y. Lou (Ecology Letters, 2012)
In response to insect attack, plants release complex blends of volatile compounds. These volatiles serve as foraging cues for herbivores, predators and parasitoids, leading to plant‐mediated interactions within and between trophic levels. Hence, plant volatiles may be important determinants of insect community composition. To test this, we created rice lines that are impaired in the emission of two major signals, S‐ linalool and ( E )‐β‐caryophyllene. We found that inducible S‐ linalool attracted predators and parasitoids as well as chewing herbivores, but repelled the rice brown planthopper Nilaparvata lugens , a major pest. The constitutively produced ( E )‐β‐caryophyllene on the other hand attracted both parasitoids and planthoppers, resulting in an increased herbivore load. Thus, silencing either signal resulted in specific insect assemblages in the field, highlighting the importance of plant volatiles in determining insect community structures. Moreover, the results imply that the manipulation of volatile emissions in crops has great potential for the control of pest populations.

Construction of a stable genetically engineered rhamnolipid-producing microorganism for remediation of pyrene-contaminated soil - Li Cao; Qian Wang; Ji Zhang; Chao Li; Xin Yan; Xu Lou; Yali Xia; Qing Hong; Shunpeng Li (World Journal of Microbiology and Biotechnology, 2012)

Promoter variants in the MSMB gene associated with prostate cancer regulate MSMB/NCOA4 fusion transcripts - Hong Lou; Hongchuan Li; Meredith Yeager; Kate Im; Bert Gold; Thomas D. Schneider; Joseph F. Fraumeni; Stephen J. Chanock; Stephen K. Anderson; Michael Dean (Human Genetics, 2012)

Validation of a reduced combustion mechanism for light hydrocarbons - Helen H. Lou; Daniel Chen; Christopher B. Martin; Xianchang Li; Kyuen Li; Hitesh Vaid; Anjan Tula Kumar; Kanwar Devesh Singh (Clean Technologies and Environmental Policy, 2012)

Precise orbit determination of Beidou Satellites with precise positioning - Chuang Shi; QiLe Zhao; Min Li; WeiMing Tang; ZhiGang Hu; YiDong Lou; HongPing Zhang; XiaoJi Niu; JingNan Liu (Science China Earth Sciences, 2012)

A functional variant of the collagen type III alpha1 gene modify risk of sporadic intracranial aneurysms - Jingzhou Chen; Yufang Zhu; Yuhua Jiang; Hui Yu; Kai Sun; Weihua Song; Liming Luan; Kejia Lou; Youxiang Li; Peng Jiang; Qi Pang; Rutai Hui (Human Genetics, 2012)

Pyrosequencing of a short fragment of the amelogenin gene for gender identification - Shujin Li; Ting Feng; Lihong Fu; Zhenhua Li; Chunguang Lou; Xiaojing Zhang; Chunling Ma; Bin Cong (Molecular Biology Reports, 2012)

Spatiotemporal Expression of Testicular Protein Kinase 1 After Rat Sciatic Nerve Injury - Dong Lou; Binbin Sun; Haixiang Wei; Xiaolong Deng; Hailei Chen; Dawei Xu; Guodong Li; Hua Xu; Youhua Wang (Journal of Molecular Neuroscience, 2012)

A reduced reaction mechanism for the simulation in ethylene flare combustion - Helen H. Lou; Christopher B. Martin; Daniel Chen; Xianchang Li; Kyuen Li; Hitesh Vaid; Anjan Tula Kumar; Kanwar Devesh Singh; Doyle P. Bean (Clean Technologies and Environmental Policy, 2012)

SLC39A2 and FSIP1 polymorphisms as potential modifiers of arsenic-related bladder cancer - Margaret R. Karagas; Angeline S. Andrew; Heather H. Nelson; Zhongze Li; Tracy Punshon; Alan Schned; Carmen J. Marsit; J. Steven Morris; Jason H. Moore; Anna L. Tyler; Diane Gilbert-Diamond; Mary-Lou Guerinot; et al. (Human Genetics, 2012)

Muscle injury induced by different types of contractions in dystrophic mdx mice - Jianwei Lou; Wenbo Bi; Wei Li; Yuying Zhao; Shuping Liu; Jinfan Zheng; Chuanzhu Yan (Journal of Muscle Research and Cell Motility, 2012)

Crustal structure of the northwestern sub-basin, South China Sea: Results from a wide-angle seismic experiment - ZhenLi Wu; JiaBiao Li; AiGuo Ruan; Hai Lou; WeiWei Ding; XiongWei Niu; XiBing Li (Science China Earth Sciences, 2012)

Effect of microcystin-LR on protein phosphatase 2A and its function in human amniotic epithelial cells - Jing Liang; Tan Li; Ya-li Zhang; Zong-lou Guo; Li-hong Xu (Journal of Zhejiang University-SCIENCE B, 2011)

CTLA-4 exon 1 +49 polymorphism alone and in a haplotype with −318 promoter polymorphism may confer susceptibility to chronic HBV infection in Chinese Han patients - Shaoqiong Duan; Guoyu Zhang; Qunying Han; Zhu Li; Zhengwen Liu; Jinghong Chen; Yi Lv; Na Li; Yawen Wang; Man Li; Sai Lou; Mingbo Yang; et al. (Molecular Biology Reports, 2011)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Normal epigenetic inheritance in mice conceived by in vitro fertilization and embryo transfer - Lei Li; Fang Le; Li-ya Wang; Xiang-rong Xu; Hang-ying Lou; Ying-ming Zheng; Jiang-zhong Sheng; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

Effects of allitridin on acute and chronic mouse cytomegalovirus infection - Xing-lou Liu; Hui Wang; Ya-nan Li; Hai-xia Ge; Sai-nan Shu; Feng Fang (Archives of Virology, 2011)

Detection of hepatitis C virus by an improved loop-mediated isothermal amplification assay - Jin Yang; Mei-xin Fang; Jie Li; Guo-qiang Lou; Hang-jun Lu; Nan-ping Wu (Archives of Virology, 2011)

Effect of Elevated Ultraviolet-B Radiation on Microbial Biomass Carbon and Nitrogen in Barley Rhizosphere Soil - Yunsheng Lou; Lixuan Ren; Zhongpei Li; Huanyou Cheng; Taolin Zhang (Water, Air, & Soil Pollution, 2011)

QTL mapping of sheath blight resistance in a deep-water rice cultivar - Dong Fu; Liang Chen; Guohui Yu; Yi Liu; Qiaojun Lou; Hanwei Mei; Liang Xiong; Mingshou Li; Xiaoyan Xu; Lijun Luo (Euphytica, 2011)

Growth promotion effects of the endophyte Acinetobacter johnsonii strain 3-1 on sugar beet - Yingwu Shi; Kai Lou; Chun Li (Symbiosis, 2011)

Cell responses and hemocompatibility of g-HA/PLA composites - Jia Li; Wei Zheng; YuFeng Zheng; Xia Lou (Science China Life Sciences, 2011)

HNP-3 enhanced the antimicrobial activity of CIP by promoting ATP efflux from P. aeruginosa cells - Hao Wang; Birong Dong; Li Lou (Molecular Biology Reports, 2011)

Degradation of dye rhodamine B under visible irradiation with Prussian blue as a photo-Fenton reagent - Shou-Qing Liu; Shi Cheng; Li Luo; Hong-Ying Cheng; Song-Jun Wang; Shuai Lou (Environmental Chemistry Letters, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Elevated sICAM-1 levels in patients with hemorrhagic fever with renal syndrome caused by Hantaan virus - Qunying Han; Lei Zhang; Zhengwen Liu; Wen Kang; Sai Lou; Jianming Qiu; Zhu Li; Guoyu Zhang; Yawen Wang; Man Li; Na Li (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

FLT3 and NPM1 mutations in Chinese patients with acute myeloid leukemia and normal cytogenetics - Lei Wang; Wei-lai Xu; Hai-tao Meng; Wen-bin Qian; Wen-yuan Mai; Hong-yan Tong; Li-ping Mao; Yin Tong; Jie-jing Qian; Yin-jun Lou; Zhi-mei Chen; Yun-gui Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

Exposure to lanthanum compound diminishes LPS-induced inflammation-associated gene expression: involvements of PKC and NF-κB signaling pathways - Fei Guo; Yuanlei Lou; Nianhua Feng; Guohui Li; An Xie; Xueming Huang; Yang Wang (BioMetals, 2010)

Growth and photosynthetic efficiency promotion of sugar beet (Beta vulgaris L.) by endophytic bacteria - Yingwu Shi; Kai Lou; Chun Li (Photosynthesis Research, 2010)

Association Analysis of the RET Proto-Oncogene with Hirschsprung Disease in the Han Chinese Population of Southeastern China - Cui-Ping Liu; Qian-Qian Tang; Jin-Tu Lou; Chun-Fen Luo; Xue-Wu Zhou; Dong-Mei Li; Fei Chen; Xiang Li; Ji-Cheng Li (Biochemical Genetics, 2010)

Characterization of Burkholderia cepacia complex from cystic fibrosis patients in China and their chitosan susceptibility - Yuan Fang; Miao-miao Lou; Bin Li; Guan-Lin Xie; Fang Wang; Li-Xin Zhang; Yuan-Chan Luo (World Journal of Microbiology and Biotechnology, 2010)

Expression, purification and characterization of human ubiquitin-activating enzyme, UBE1 - Mei Zheng; Jing Liu; Zhenxing Yang; Xing Gu; Fan Li; Tiantian Lou; Chaoneng Ji; Yumin Mao (Molecular Biology Reports, 2010)

Advanced oxidation protein products decrease expression of nephrin and podocin in podocytes via ROS-dependent activation of p38 MAPK - Li Yang; Min Liang; QiuGen Zhou; Di Xie; AiJu Lou; Xun Zhang; FanFan Hou (Science China Life Sciences, 2010)

Accurate DNA synthesis by Sulfolobus solfataricus DNA polymerase B1 at high temperature - Likui Zhang; Huiqiang Lou; Li Guo; Zhengyan Zhan; Zhenhong Duan; Xin Guo; Li Huang (Extremophiles, 2010)

Charge Transfer Photophysics of Tetra(α-amino) Zinc Phthalocyanine - Xian-Fu Zhang; Xijiang Li; Lihong Niu; Lou Sun; Lu Liu (Journal of Fluorescence, 2009)

Cloning and expression analysis of hsp70 gene from freshwater planarian Dugesia japonica - Ke-Xue Ma; Guang-Wen Chen; Hao Lou; Li-Na Fei (Biologia, 2009)

Prediction of shelled shrimp weight by machine vision - Peng-min Pan; Jian-ping Li; Gu-lai Lv; Hui Yang; Song-ming Zhu; Jian-zhong Lou (Journal of Zhejiang University-SCIENCE B, 2009)

Promotion of plant growth by phytohormone-producing endophytic microbes of sugar beet - Yingwu Shi; Kai Lou; Chun Li (Biology and Fertility of Soils, 2009)

Effect of floral morphology on fruit set in Epimedium sagittatum (Berberidaceae) - Yun-xiang Li; Qiu-mei Quan; Gen-lou Sun (Plant Systematics and Evolution, 2009)

Losartan inhibits monocytic adhesion induced by ADMA via downregulation of chemokine receptors in monocytes - Mei-Fang Chen; Yuan-Jian Li; Tian-Lun Yang; Bin Lou; Xiu-Mei Xie (European Journal of Clinical Pharmacology, 2009)

Molecular Identification of cDNA, Immunolocalization, and Expression of a Putative Odorant-Binding Protein from an Asian Honey Bee, Apis cerana cerana - Hong-Liang Li; Ya-Li Zhang; Qi-Kang Gao; Jia-An Cheng; Bing-Gan Lou (Journal of Chemical Ecology, 2008)

Association of amyloid precursor protein-binding protein, family B, member 1 with nicotine dependence in African and European American smokers - Guo-Bo Chen; Thomas J. Payne; Xiang-Yang Lou; Jennie Z. Ma; Jun Zhu; Ming D. Li (Human Genetics, 2008)

Coastally trapped atmospheric gravity waves on SAR, AVHRR and MODIS images - X. L. Gan; W. G. Huang; X. F. Li; X. J. Chen; X. L. Lou; Z. X. Zhao; J. S. Yang; A. Q. Shi (International Journal of Remote Sensing, 2008)

Anticancer activities of some arylcarbamoylalkyltriphenylphosphonium chlorides - Lou Zhaowen; Zhou Li; Xiao Chunfen; Ye Yong; Zeng Fanbo; Huang Kaixun (Medicinal Chemistry Research, 2007)

A major QTL associated with cold tolerance at seedling stage in rice (Oryza sativa L.) - Qiaojun Lou; Liang Chen; Zongxiu Sun; Yongzhong Xing; Jun Li; Xiaoyan Xu; Hanwei Mei; Lijun Luo (Euphytica, 2007)

Prostaglandin E2 enhances mitogen-activated protein kinase/Erk pathway in human cholangiocarcinoma cells: involvement of EP1 receptor, calcium and EGF receptors signaling - Li Zhang; Li Jiang; Qiuyan Sun; Tao Peng; Kexin Lou; Ningbo Liu; Jing Leng (Molecular and Cellular Biochemistry, 2007)

Cytological and molecular characterization of a novel monogenic dominant GMS in Brassica napus L. - Dao-Jie Wang; Ai-Guang Guo; Dian-Rong Li; Jian-Hua Tian; Fei Huang; Gen-Lou Sun (Plant Cell Reports, 2007)

Application of cDNA array for studying the gene expression profile of mature appressoria of Magnaporthe grisea - Qing-chao Jin; Hai-tao Dong; You-liang Peng; Bao-shan Chen; Jing Shao; Ye Deng; Cheng-en Dai; Yong-qi Fang; Yi-chun Lou; You-zhi Li; De-bao Li (Journal of Zhejiang University-SCIENCE B, 2007)

Effect of Rice Residues on Carbon Dioxide and Nitrous Oxide Emissions from a Paddy Soil of Subtropical China - Yunsheng Lou; Lixuan Ren; Zhongpei Li; Taolin Zhang; Kazuyuki Inubushi (Water, Air, & Soil Pollution, 2007)

Effect of proximal femoral osteoporosis on cementless hip arthroplasty: A short-term clinical analysis - Xian-feng Lou; Yu-hong Li; Xiang-jin Lin (Journal of Zhejiang University-SCIENCE B, 2007)

Gene-based analysis suggests association of the nicotinic acetylcholine receptor β1 subunit (CHRNB1) and M1 muscarinic acetylcholine receptor (CHRM1) with vulnerability for nicotine dependence - Xiang-Yang Lou; Jennie Z. Ma; Thomas J. Payne; Joke Beuten; Karen M. Crew; Ming D. Li (Human Genetics, 2006)

Dynamics of vascular volume and hemodilution of lactated Ringer’s solution in patients during induction of general and epidural anesthesia - Yu-hong Li; Xian-feng Lou; Fang-ping Bao (Journal of Zhejiang University-SCIENCE B, 2006)

Sensory exotropia subsequent to senile cataract - Ding-hua Lou; Ye-sheng Xu; Yu-min Li (Journal of Zhejiang University-SCIENCE B, 2005)

Carbon Dioxide Flux in a Subtropical Agricultural Soil of China - Yunsheng Lou; Zhongpei Li; Taolin Zhang (Water, Air, & Soil Pollution, 2003)

Study of setting up the forest Resources Management Information System based on WEBGIS - Su-li Wu; Quan-sheng Lou; Zhi-jie Quan; Xiao-jun Li (Chinese Geographical Science, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

The use of genetic resources in crop improvement: Lessons from China - Yu Li; Jie Wang; Yongsheng Cao; Weidong Gao; Jiahe Fang; Xizhi Lou (Genetic Resources and Crop Evolution, 1998)